High prevalence and co-existence of SHV and CTX-M genes in extensively drug-resistant (XDR) Gram-negative bacteria isolated from hospital settings in Faisalabad District, Pakistan - Umair Abbas; Huma Sajjad; Amir Shaukat; Zaheer Ahmad; Azfar Sattar; Khurram Shehzad; Mark A. T. Blaskovich; Tania Da Silva Duarte; Johannes Zuegg; Aamir Ali; Yasra Sarwar (Molecular Biology Reports, 2026)

Exploring the effects of lifelong aerobic exercise on early skeletal muscle remodeling between 8 and 14 months in the rat - Alexandra Moreira-Pais; Rita Ferreira; Maria João Neuparth; Margarida Fardilha; Daniel Moreira-Gonçalves; Paula A. Oliveira; José A. Duarte (Journal of Physiology and Biochemistry, 2026)
The insidious onset and progression of sarcopenia make it vital to understand the early skeletal muscle changes and explore therapies to slow its progression. This study explored the gastrocnemius remodeling at an early stage of aging (14 months of age) and the effects of lifelong aerobic exercise. For that, 2-month-old male Wistar rats underwent a 12-month treadmill exercise program. Sedentary age-matched, young sedentary, and young exercised for 6 months rats were considered. The results highlighted an age-related decrease in the relative gastrocnemius muscle mass, suggestive of loss or atrophy of some fibers, which was mitigated by lifelong aerobic exercise. Consequently, an age-related compensatory hypertrophy was suggested to be triggered in the gastrocnemius muscle. Data proposed that aging reduced mitochondrial density, indicated by citrate synthase (CS) activity, which was prevented by lifelong aerobic exercise. The reduced CS activity correlated with increased ATP-dependent 6-phosphofructokinase (PFKM)/ATP synthase subunit beta (ATPB) ratio, suggesting that at an early stage of aging, the skeletal muscle favors the glycolytic metabolism in response to decreased mitochondrial content. The results also pointed to an age-induced AMP-activated protein kinase (AMPK) activation and an AMPK-related apoptosis inhibition, perchance to reduce fiber loss or atrophy. The basal phosphorylated AMPK/AMPK ratio decreased with lifelong aerobic exercise, possibly reflecting the exercise-induced increase in CS activity. This work highlights the importance of studying early skeletal muscle changes in aging for timely disease management and prevention.

Endolithic fungal diversity is present in the unique phosphatized rocks of an environmentally extreme equatorial archipelago revealed by DNA amplicon metagenomics - Laucélly Bárbara Avelar Rocha; Vívian Nicolau Gonçalves; Fábio Soares de Oliveira; Guilherme Resende Corrêa; Eduardo Osório Senra; Eduardo Baudson Duarte; Fabyano A. C. Lopes; Micheline C. Silva; Peter Convey; Paulo E. A. S. Câmara; Luiz Henrique Rosa (Brazilian Journal of Microbiology, 2026)
We evaluated endolithic fungal diversity associated with rocks sampled at the polyextreme Brazilian São Pedro and São Paulo archipelago using a DNA amplicon metagenomics approach. We detected 808,547 fungal DNA reads grouped into 92 amplicon sequence variants (ASVs). The rocks sampled were geologically characterized as mylonitized peridotites, serpentinized peridotites, and carbonate-matrix sedimentary breccias. Ascomycota was the dominant phylum, followed by Basidiomycota , Mucoromycota , Mortierellomycota and Chytridiomycota . Hortaea werneckii , Cladosporium sp., Simplicillium sp., Blastobotrys serpentis , Penicillium sp., P. simplicissimum , Malassezia restricta , Ascomycota sp., Verrucariaceae sp., and Fungal sp. were the dominant assigned taxa. The endolithic assemblages displayed moderate to low diversity indices. Among the fungal community, only the dominant Fungal sp. occurred in all samples. The data obtained in our environmental DNA (eDNA) amplicon metagenomics approach suggest that the rocks of the isolated equatorial São Pedro and São Paulo archipelago host a complex fungal diversity, including taxa regarded to be cosmopolitan, extremophilic hypersaline and xerophilic, plant pathogens, and human/animal opportunistic pathogens. As eDNA studies do not confirm the presence of viable organisms or propagules, further research using culturing approaches is now required to develop strategies to recover these fungi for physiological, biogeochemical, genetic and potential biotechnological studies.

Microbial oil production by Yarrowia lipolytica strains using glycerol as carbon source - Elisa Duarte Guerra Coelho; Fernanda Palladino; Elisa A. A. Teixeira; Fernanda L. C. Oliveira; Vânya M. D. Pasa; Luiz H. Rosa; Carlos A. Rosa (Brazilian Journal of Microbiology, 2026)
Yeasts can produce microbial oil from hydrophobic substrates such as glycerol, a byproduct of the biodiesel industry that is often undervalued in the market. Yarrowia lipolytica is capable of degrading glycerol and is considered a model organism for studying lipid accumulation. Different yeast strains and culture conditions can result in varying lipid yields with distinct fatty acid profiles. Thus, in this study, five strains of Y. lipolytica were tested for microbial oil production using pure glycerol at temperatures of 15 °C and 25 °C. None of the isolates were considered oleaginous at 15 °C. However, at 25 °C, the isolates UFMG-CM-Y6114 (from cheese), UFMG-CM-Y4187 (from beach sand), and UFMG-CM-Y6189 (from Antarctica) produced more than 20% lipid content (29.30%, 26.95%, and 34.38%, respectively). No significant differences in lipid content were observed between the UFMG-CM-Y6114 and UFMG-CM-Y4187 strains. The cheese- and Antarctica-derived strains were further tested for their ability to accumulate oil when grown on crude glycerol. Among them, UFMG-CM-Y6189 showed the best performance, producing 9.40 g·L⁻¹ of biomass, 1.90 g·L⁻¹ of lipid yield, and 21.56% lipid content, while consuming 61.3 g·L⁻¹ of glycerol. The fatty acid profile of these lipids was predominantly monounsaturated (59.5%), with oleic acid (49.4%) as the main component. This, combined with a low polyunsaturated fatty acid content (5.2%), makes these lipids particularly suitable for biodiesel production. Therefore, the lipids from the Y. lipolytica strain UFMG-CM-Y6189 represent a promising raw material for biodiesel production from glycerol.

Identification of a highly conserved and surface-exposed B-cell epitope in snake venom L-amino acid oxidases - Thamyres Silva de Assis; Tamara Gabriela Fernandes Costa; Letícia Lopes-de-Souza; Fernanda Costal-Oliveira; Carolina R. Rodrigues; Camila Rosa Campos; Clara Guerra-Duarte; Mírian Ívens Fagundes; Ricardo A. Machado-de-Ávila; Vânia M.M. Braga; Carlos Chávez-Olórtegui (Toxicon, 2026)

An integrative compositional modeling framework for cross-cultural co-creation of multiespecies dulce de leche in the southern cone - Bruna B. Durço; Sofía Vargha; Elson R. Tavares Filho; Eliane Teixeira Mársico; Adriano G. da Cruz; Paula Cardinal; Graciela Rodriguez; Maria Carmela K.H. Duarte; Lorena Garitta; Adriana Gámbaro; Erick A. Esmerino (Food Quality and Preference, 2026)

From egg to adult: combining morphology, bulk metabarcoding and eDNA for comprehensive monthly monitoring of ichthyoplankton in a temperate estuary - André O. Ferreira; Cláudia Machado; Olga M. Azevedo; Cristina Barroso; Sofia Duarte; Conceição Egas; A. Miguel Piecho-Santos; Filipe O. Costa (Estuarine, Coastal and Shelf Science, 2026)

Microplastics abundance in marine sediments and stomach contents of benthic organisms - Alishon Yuliana Estrada-Stabilito; Karen Yicelth Morales-Duarte; Carlos David Rodríguez-Amaranto; Daniel Leonardo Ramírez-Orozco; Luis A. Gómez-Lemos (Hydrobiologia, 2026)
Microplastics are an emerging contaminant in marine ecosystems worldwide. This study evaluated the abundance of microplastics, their relationship with sediment type, and their ingestion by macroinvertebrates in the Eastern South Pacific Ocean and the Southern Caribbean Sea during the rainy and dry seasons. A granulometric analysis was performed applying a Pearson correlation matrix, and microplastics were extracted using the density flotation method and analyzed by type, color, and size. There was an average of 165 ± 22 microplastics/kg in the Eastern South Pacific Ocean and 296 ± 167 microplastics/kg in the Southern Caribbean Sea, however, there were no significant differences among regions or seasons. A negative relationship was found between microplastic abundance and coarser sediment, indicating that they retain fewer microplastics than finer sediments. Blue and red fibers smaller than 2 mm were the most common microplastic types in both regions. There was a higher ingestion of microplastics in the Southern Caribbean Sea (22%) compared to the Eastern South Pacific Ocean (3%), and polychaetes were the main microplastic eaters. Our findings highlight the usefulness of marine polychaetes as bioindicators of microplastic pollution and suggest a relationship between the abundance of microplastics and the ingestion of microplastic by benthic organisms.

Tissue composition and thermal performance in native and invasive mussels from southern chile - Melissa Fernández; Roddy Jara; Oscar Varas; Diego Quintanilla-Ahumada; Pedro A. Quijón; Cristian Duarte; Pablo A. Oyarzún; Marcela Aldana; Roberto García-Huidobro; Gonzalo J. Ruiz-Tagle; José Pulgar (Marine Biology, 2026)

Intestinal Histomorphometric Alterations During Experimental Strongyloidiasis in Mice Treated with Rosmarinus officinalis Essential Oil - Lorena Q. A. Tanaka; Kamilla A. M. Dutra; Nicolas M. H. da Silva; Izadora M. Assis; Gabriela A. C. Duarte; João B. A. Souza; Eleuza R. Machado; Ana Paula S. Perez; Rosângela M. Rodrigues (Acta Parasitologica, 2026)
Purpose Strongyloidiasis is an intestinal helminthiasis that can induce structural alterations in the intestinal mucosa during infection. The present study evaluated histomorphometric alterations of the small intestine in mice experimentally infected with Strongyloides venezuelensis and treated with Rosmarinus officinalis essential oil. Methods Infected animals were treated orally with R. officinalis essential oil (200 or 400 mg/kg), ivermectin or control treatments. Histomorphometric parameters of the small intestine were evaluated, including villus height, epithelial height, crypt depth, muscular layer thickness, brush border height and goblet cell counts. Parasitological parameters were also assessed to characterize the infection model. Results Histomorphometric analysis demonstrated that treatment with essential oil at 200 mg/kg was associated with recovery of villus and epithelial height, increased brush border and goblet cell numbers, as well as attenuation of muscular layer hypertrophy, suggesting preservation of mucosal structure during infection. The 400 mg/kg dose, although associated with greater reduction in parasite burden, was accompanied by increased crypt depth, indicating more intense proliferative remodeling of the intestinal mucosa. Ivermectin promoted the greatest reduction in parasite burden with marked elimination of eggs and females. Conclusion These findings indicate that R. officinalis essential oil modulates intestinal mucosal architecture during experimental strongyloidiasis and highlight its potential influence on host intestinal responses during infection.

Potato protein-based meat analogues fortified with upcycled fruit flours: Functional, textural, and antioxidant insights - Ana Rita Pereira; Vasco Trincão da Silva; Duarte Torres; Ana A. Vilas-Boas; Débora A. Campos; Inês Cruz; Adriana Ferreira; Nuno Mateus; Victor de Freitas; Ana Fernandes (Food Chemistry, 2026)

Anti-environmental political agendas, firearm deregulation and illegal hunting in Brazil - Hani R. El Bizri; Thais Queiroz Morcatty; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Kacie Henson; Camila Alvez Islas; Gabriel Favero Massocato; Arnaud L.J. Desbiez; João Vitor Campos-Silva; Daniel Zani La Laina; et al. (Biological Conservation, 2026)

Predicted effects of climate change on the spatial distribution of soil nematodes at a regional scale - Rui P. Carvalho; A. Carolina Duarte; Carlos A. Guerra; Susana Mendes; Concha Cano-Diaz; Sofia R. Costa (Applied Soil Ecology, 2026)

Redox-Driven mineral formation mediated by imogolite nanotubes: Experimental and DFT insights into Fe2+ oxidation under variable oxygen conditions - R.D. Cuevas-Alfaro; José D. Fabris; José D. Ardisson; Carmen Pizarro; Helio A. Duarte; Lisa Muñoz; Leidy Orozco; Karen Manquián-Cerda; Nicolás Arancibia-Miranda (Applied Clay Science, 2026)

Thalassoporum longitrichum sp. nov., a marine epizoic cyanobacterium with anti-inflammatory potential, and the taxonomic reassessment of Limnothrix Meffert - C. Tenorio Rodas; G.S. Hentschke; F. Oliveira; G. Lopes; A. Duarte; J. Morone; A. Campos; V. Vasconcelos (Algal Research, 2026)

Digestion, absorption and deposition of n-3 polyunsaturated fatty acids in tissues: is the chemical form of supply relevant? - Ignacio Alvear; Lissette Duarte; Camila Farias; Luis A. Videla; Yasna Muñoz; Rodrigo Valenzuela (Critical Reviews in Food Science and Nutrition, 2026)

Biomarkers of acute kidney injury in crotaline envenomation in the Brazilian Amazon - Renato do Carmo Said; Vera Lúcia Teixeira de Freitas; João Guilherme Pontes Lima Assy; Olivia Campos Pinheiro Berreta; Alisson dos Santos Brandão; Isadora Calderaro Soares; Marcelo Ribeiro Duarte; Lia Junqueira Marçal; Emmanuel A. Burdmann; Francisco Oscar de Siqueira França (Toxicon, 2026)

Associations between teat apex, milk microbiota, and udder health in primiparous cows: Effects of decontamination in a low biomass context - José A. Ferronatto; Eduardo M. Ramos-Sanchez; Erika K. Ganda; Marcos B. Heinemann; Juliano L. Gonçalves; Marcos V. dos Santos; Julia A. Arantes; Vinicius S. Duarte; Alessandro S. Guimarães; Marcio C. Costa; Marie Joossens; Sarne De Vliegher; et al. (Research in Veterinary Science, 2026)

Mitigating overload conditions in vibrating screens through fuzzy-controlled feed rate regulation - Alexandre G. Fonseca; Robson A. Duarte; Kaike S. Albuquerque; Thomás Pinto; Thiago A.M. Euzébio (Minerals Engineering, 2026)

A global synthesis of ecosystem services records and their associations with marine and coastal habitats - Joana Martelo; Sandra A. Ferreira; Ronaldo Sousa; Sílvia B. Carvalho; Manuel Hidalgo; Henrique Cabral; Marina Dolbeth; Martin Lindegren; Ana Veríssimo; Anne E. Magurran; Bernardo Duarte; Sofia Henriques; et al. (Ecosystem Services, 2026)

Mitochondrial DNA markers reveal panmixia and new sister lineage in the eastern Red Sea mesopelagic fish - Kah Kheng Lim; Carlos Angulo-Preckler; Lutfi Afiq-Rosli; Vincent A. Pieribone; Mohammad A. Qurban; Carlos M. Duarte (Marine Biodiversity, 2026)
Cryptic diversity in mesopelagic fish is increasingly documented across the Indo-Pacific, but remains understudied in the Red Sea, a region known for its high endemism and unique ecological conditions. We investigated cryptic diversity in Benthosema spp. and population genetic structure in the two most abundant mesopelagic fishes in the eastern Red Sea, the Benthosema pterotum species complex and the endemic Vinciguerria mabahiss . Using concatenated mitochondrial ( 12S , 16S , and COI ) sequences from 275 V. mabahiss and 84 Benthosema specimens, we detected panmictic populations in both species. Both species showed high haplotype diversity and signatures of recent demographic expansion, supported by star-like haplotype networks, negative neutrality tests, and Bayesian skyline plots. Phylogenetic analysis revealed a cryptic lineage ( Benthosema cf. pterotum ) in the eastern Red Sea, forming a sister lineage within the genus. Its genetic similarity with Gulf of Oman populations suggests ongoing gene flow through the Strait of Bab-el-Mandeb. These findings challenge current taxonomic frameworks and highlight the importance of accurate species delimitation for biodiversity monitoring and fisheries management. High genetic connectivity and demographic expansion in both mesopelagic fish species suggest resilience driven by large effective population sizes and high dispersal potential. These results provide the first population genetic baseline for the largest fish stock in the eastern Red Sea and support future efforts to assess adaptive potential in a warming marginal sea.

Electrochemical strategies for lateral flow and LAMP-Based platforms toward pathogen detection: A critical review - Lucas F. de Lima; Paulo Felipe Neves Estrela; Leonardo Lopes-Luz; Lauro A. Pradela-Filho; Jonatas V. Souza; Daniel Júnior Almeida dos Santos; Gabriela R.M. Duarte; Wendell K.T. Coltro; Thiago R.L.C. Paixão (Analytica Chimica Acta, 2026)

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

PROMETHEUS clinical trial protocol: tailoring healthy ageing with lifestyle and nutraceuticals - Ajla Hodzic Kuerec; Lihuan Guan; Weilan Wang; Duarte Barros; Wejdan M. Alenezi; Jozo Grgic; Vanessa K. Wazny; Jordi Morwani-Mangnani; Mazzarine Dotou; Dingding Zhang; Tong Chen; Jiaqiu Wang; et al. (GeroScience, 2026)
The d emographic shift toward an older population is accelerating the prevalence of age-related diseases. Precision geromedicine represents a paradigm shift in targeting the biological processes of ageing to optimise health and healthspan, which likely requires multimodal tailored interventions. PROMETHEUS, as part of the XPRIZE healthspan semi-finalist competition, is an 8-week feasibility and exploratory study including 20 middle-aged-to-older participants who received a multimodal intervention comprising fundamental and augmented interventions. The fundamental interventions include sleep and dietary recommendations; supplementation with whey protein, creatine, and fucoidan; supervised exercise with an exergaming component (dual-task cognitive-physical training); motivational interviewing; and cognitive behavioural therapy. The augmented intervention is further personalised based on predefined gerotypes, reflecting individual ageing patterns beyond chronological age. At baseline, urolithin A, nicotinamide mononucleotide, and/or multivitamin-multimineral were prescribed to participants based on their muscle mass, VO 2 peak, and cognitive performance. At mid-intervention, interventions were adjusted based on individual response, including dose escalation and/or the addition of ergothioneine for inadequate improvement in cognition. Primary outcomes include measures of muscle strength and mass, immune function and cognitive performance, and feasibility indicators such as adherence and trial completion. Secondary outcomes include assessments of other biological, clinical, and digital biomarkers of ageing, as well as qualitative indicators of motivation and personal values. This study is aimed at investigating the recruitment feasibility, safety, adherence, and exploratory outcome trajectories of a multimodal, personalised precision geromedicine intervention protocol based on individual participant’s baseline characteristics and interim responses. These findings will also inform the design of a subsequent 12-month, randomised controlled trial evaluating personalised lifestyle and nutraceutical strategies with the potential to incorporate repurposed pharmacological agents to optimise age-related health outcomes.

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Life cycle and economic assessment of inverted p-i-n perovskite solar cells - Joana Príncipe; Luísa Andrade; Vera C.M. Duarte; Teresa M. Mata; António A. Martins (Journal of Cleaner Production, 2026)

Scale up coating process of PBAT with modified lignin for paper packaging: Barrier properties, and screening volatile/semi-volatile compounds - Francisco A. G. Soares Silva; Joel Pereira; Carlos Granadeiro; Tomás Duarte; Fátima Poças (Food Packaging and Shelf Life, 2026)

From agro-industrial waste to microbial pigments: advances in production substrates and extraction technologies - J. C. Ramos; A. S. Jabur de Assis; G. M. Pegoraro; T. Mendes Silva; I. C. S. Duarte (Systems Microbiology and Biomanufacturing, 2026)
Microbial pigments have been gaining prominence as sustainable alternatives to synthetic dyes, which are often associated with environmental impacts and potential health risks. A wide range of microorganisms, including bacteria, fungi and yeasts, are capable of producing pigments of industrial interest. Despite their potential, large-scale production still faces challenges related to cultivation costs and, in particular, extraction steps, which traditionally rely on the use of organic solvents and may present low yields and limited sustainability. In this context, the use of agro-industrial residues as alternative nutrient sources for microbial growth and pigment biosynthesis emerges as a promising strategy for sustainable valorisation, contributing to reduced production costs, mitigation of environmental impacts and strengthening of the circular bioeconomy. However, the recovery of microbial pigments remains a technological obstacle, as many of these compounds are intracellular or associated with cellular structures, making extraction and purification challenging and affecting industrial feasibility. To overcome these limitations, recent advances have focused on improving extraction techniques in order to increase yield, purity and sustainability. This review addresses the main microbial pigments and their producers, highlighting the potential of agro-industrial residues for sustainable production. In addition, it synthesises recent advances in extraction strategies, emphasising approaches that combine efficiency, reduced environmental impact and economic viability. In an integrated perspective, the discussion demonstrates that the combination of low-cost substrates and more sustainable extraction technologies represents a promising pathway to expand production and meet the growing demand for natural colourants in the food, cosmetic and pharmaceutical industries.

Intrinsic constraints on budding in the deep-sea coral Dendrophyllia cf. horsti from the Red Sea - Eleonora Re; Federica Barreca; Tullia I. Terraneo; Francesca Benzoni; Domingo A. Lattanzi Sanchez; M. Rodrigue; V. Pieribone; M. Qurban; Carlos M. Duarte (Marine Biology, 2026)
Colonial corals display diverse growth forms shaped by both environmental conditions and intrinsic developmental mechanisms. Understanding these internal morphogenetic rules is critical for accurately modeling coral colony formation. In this study, we investigated the intrinsic budding patterns of Dendrophyllia cf. horsti , an azooxanthellate deep-sea coral from the Red Sea. Using detailed morphological analyses of colony architecture, we identified consistent intrinsic constraints that govern colony development. Lateral corallites bud at a consistent angle (mean 15.9°) relative to the growth axis, and the orientation of the directive septa in daughter corallites remains stable across generations (mean 19.8°). Budding was consistently restricted to two specific sites per internode located near the lateral primary septa. In most colonies, budding occurred on the same side at successive internodes, although occasional observations suggested variation in the relative position of budding sites. These findings suggest that even in deep-sea, non-photosynthetic species, colony morphology is strongly regulated by intrinsic developmental constraints, as previously demonstrated in congeneric species. The results contribute valuable data for simulating coral growth and highlight the importance of intrinsic constraints in shaping colonial forms across Scleractinia.

Additive and non-additive effects of artificial light at night and ocean warming on the physiology and behavior of an intertidal fish - Diego Quintanilla-Ahumada; Diego Maturana; K. Devon Lynn; Nicol Zúñiga-Cueto; Cristian Miranda-Benabarre; Nicole Jahnsen-Guzmán; José Pulgar; Pedro A. Quijón; Cristian Duarte (Marine Pollution Bulletin, 2026)

Aluminum tolerance and secondary metabolites modulation in Ilex paraguariensis: implications for mate composition - Thalía P. Birck; Gerâne S. Wertonge; Allan A. Kokkonen; Patrícia G. Machado; Andressa D.W.V. Martinez; Felipe K. Ricachenevsky; Jean M. Moura-Bueno; Cristiano A. Ballus; Fabio A. Duarte; Gustavo Brunetto; Luciane A. Tabaldi; Ana Lúcia A. Segatto (Food Research International, 2026)

Maternal chromium propionate supplementation in late gestation and its association with cow performance and skeletal muscle programming in beef calves - Emily A. Knapper; Luiza V. Kladt; Ivan I. Avalos-Rosario; Sarah E. Dean; Walmir Silva; Nicola V.L. Serão; Jerilyn E. Hergenreder; Elliot L. Neto; Katharine M. Wood; Michael A. Steele; Matheus P. Gionbelli; Marcio S. Duarte (Animal Feed Science and Technology, 2026)

Examining the structure of visual analogue scales to capture motivation to eat in fasting and post-meal conditions - Clarissa A. Dakin; Cristiana Duarte; Kristine Beaulieu; Nicola Buckland; Michelle Dalton; Anna Myers; Catherine Gibbons; Mark Hopkins; Graham Finlayson; Molly Blakemore; R. James Stubbs (Appetite, 2026)

Veterinary perspectives on biosecurity measures in small-scale farming systems across European countries: Results from a cross-national survey - F. Duarte; J. Prodanov-Radulović; B. Mehmedi; A. Piccirillo; M. Stukelj; E. Kldiashvili; V. Nedosekov; B. Milovanovic; N.D. Ayaz; R. Yildiz; S. Meling; I. Toftaker; et al. (Research in Veterinary Science, 2026)

From waste to resources: Integrating advanced oxidation and hydrochar production for potassium recovery and carbon retention - Jefferson E. Silveira; Jose L.S. Duarte; Alyson R. Ribeiro; Jose A. Casas; Juan A. Zazo (Bioresource Technology, 2026)

Chloride determination in crude oil by potentiometric titration after reversed-phase dispersive liquid-liquid microextraction - Mariele S. Nascimento; Cristian R. Andriolli; Gabriel T. Druzian; Fabio A. Duarte; Paola A. Mello; Rochele S. Picoloto; Eder L.M. Flores; Erico M.M. Flores (Analytica Chimica Acta, 2026)

Synergistic use of NADES and assisted extraction technologies for recovery and stabilization of bioactive compounds in Beta vulgaris L. peels - D. Rente; R. Craveiro; A. Paiva; Ana Rita C. Duarte (Food and Bioproducts Processing, 2026)

Corrigendum to “Prior autonomous self-pollination as a reproductive assurance mechanism in a high-Andean orchid” [Flora, 336 (2026), 152914] - Carlos A. Matallana-Puerto; João C.F. Cardoso; Laura J. Pérez Uscategui; Mariana O. Duarte (Flora, 2026)

Prior autonomous self-pollination as a reproductive assurance mechanism in a high-Andean orchid - Carlos A. Matallana-Puerto; João C․F. Cardoso; Laura J․Pérez Uscategui; Mariana O. Duarte (Flora, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Flow Mediates the Outcome of Predator-Prey Interactions in a Marine Soft Bottom System - Diego Quintanilla-Ahumada; Patricia A. Ramey-Balci; Cristian Duarte; Pedro A. Quijón (Estuaries and Coasts, 2026)

Traffic and functional polarization of macrophages in the areas of programmed interdigital cell death in the embryonic chick - G. Moran; C. Duarte-Olivenza; J. M. Hurle; C. I. Lorda-Diez; J. A. Montero (Apoptosis, 2026)
In this study, we show that during digit development, the embryonic limb contains an abundant and widespread population of “resident macrophages” that precede the onset of interdigital cell death responsible for the separation of digit primordia. The use of cultures of interdigital mesoderm at different remodeling stages, and GFP+ transgenic embryos in which the distal part of the autopodium has been surgically replaced by a fragment with identical characteristics from wild-type embryos, indicate that “transient macrophages” are also recruited at the beginning of interdigital death. The expression of the Pu.1 gene in coincidence with the onset of interdigital death suggests that primary yolk-sac macrophages are later complemented by macrophages of hematopoietic origin. Q-PCR analysis revealed a predominant M2/anti-inflammatory gene signature in the interdigits during the whole remodeling process that correlated with an interdigital transcriptome including Csf1 , Il-34 , Igf1 , Igfbp5 , Tgfβ4 ( Tgfβ1 in mammals), P 75 NTR / T nfrsf16 , Hgf , Vegfa , that presumably stabilizes the macrophage M2 phenotype. However, M1-proinflammatory genes, including Tnfα and Tlr4 , are expressed at very low levels prior to the onset of cell death but become up-regulated at the end of tissue remodeling. Together, our findings support the existence of “Tissue-Resident” and “Passenger/Transitory” macrophage populations of distinct origin and molecular profile participating in tissue remodeling processes associated with embryonic morphogenesis.

Seasonal and dietary determinants of metal and metalloid exposure in riverine communities of the Brazilian Amazon: A study on temporal variation - Lucas Cassulatti dos Santos; Nathália de Assis Aguilar Duarte; Marília Ladeira de Araújo; Bruno Alves Rocha; Alexey A. Tinkov; Michael Aschner; Fernando Barbosa (Chemosphere, 2026)

Ohmic heating-assisted extraction of ginger bioactives: Synergistic impacts on extract composition and on the quality of high-protein milk beverages - Gabrielle P. Vieira; Carolina P.C. Martins; Thaís Regina C. Pereira; Lévison C. Cipriano; Maria B. Goulart; Jonas T. Guimarães; Mônica M. Pagani; Maria Carmela K.H. Duarte; Adriano G. Cruz; Sérgio B. Mano; Eliane T. Mársico; Erick A. Esmerino (Food Research International, 2026)

Unravelling the molecular mechanisms of vegetative-to-reproductive transition in Cynara cardunculus by RNA-Seq analysis - A. Paulino; I. Fernandes; R. C. Pires; A. Usié; A. Faustino; J. Santos; T. Brás; D. Rosa; O. S. Paulo; M. F. Duarte; L. Marum (Plant Molecular Biology, 2026)
Cynara cardunculus inflorescence plays a significant role in cheese manufacturing and human consumption due to the milk-clotting capacity and the production of edible immature capitula. Consequently, it is crucial to understand the complex cellular and molecular processes involved in the development of cardoon flowers. The current study used western wild cardoon in two developmental stages, vegetative and reproductive, to understand the molecular mechanisms mediating cardoon`s vegetative-to-reproductive transition. Transcriptome profiling identified 552 differentially expressed genes (DEGs) between vegetative and reproductive stages, with 321 upregulated in stage 4 (vegetative state) and 231 in stages 5/6 (reproductive state). Gene Ontology (GO) analysis revealed DEGs involved in biological processes such as oxidation-reduction, lipid metabolism, and defense responses. Metabolic pathways, including phenylpropanoid biosynthesis and anther/pollen development, were significantly enriched. Genes associated with lignin formation, flavonoid synthesis, and acetyltransferase activity were upregulated in the vegetative stage. At the same time, those related to flower development and sesquiterpene lactone biosynthesis were prominent in the reproductive stage. Transcription factors, including MADS-box and ethylene-responsive families, were critical in regulating developmental transitions. This study provides comprehensive insights into the morphological, chemical, and molecular dynamics of C. cardunculus across its phenological stages, underscoring the plant’s adaptability and potential for pharmaceutical and industrial applications. The findings highlight the importance of seasonal and developmental timing in optimizing the production of valuable secondary metabolites, such as cynaropicrin.

Assessing Prokaryotic Benthic Communities in the Red Sea - Christopher A. Hempel; Larissa Frühe; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Diego E. Rivera Rosas; Amal A. Bajaffer; Wajitha J. R. M. Sait; Alexandra Steckbauer; Taiba Alamoudi; Jacqueline V. Alva García; Shannon G. Klein; et al. (Environmental Microbiology, 2026)
Marine sediments host diverse benthic prokaryotic communities that are integral to global biogeochemical cycles. However, the spatial distribution and environmental drivers of these communities, particularly in unique environments like the Red Sea, remain largely underexplored. In this study, we examine benthic prokaryotic communities sampled during the Red Sea Decade Expedition (RSDE) using 16S rRNA gene sequencing across five major regions along the Red Sea's latitudinal gradient and three depth strata. Our findings reveal distinct biogeographical patterns shaped by depth, latitude, and oxygen availability, with clear shifts in microbial community composition across the epibenthic, mesobenthic and bathybenthic zones. Bathybenthic communities exhibited consistently low levels of OTU richness throughout the Red Sea, likely due to uniform niche environmental conditions at depth, while shallower communities showed higher OTU richness towards the Southern Red Sea. The southern region harboured higher relative abundances of Chloroflexi and reduced relative abundances of Proteobacteria and Acidobacteriota relative to the northern regions. Extreme environments, such as the Atlantis II brine pool, supported specialised microbial communities likely adapted to extreme conditions like hypersalinity. This study established a critical baseline for understanding the responses of marine microbial communities to climate change and their roles in biogeochemical processes.

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Megabenthic bivalves in the subtidal area of the Gulf of Cádiz (SW Spain): Diversity and assemblages patterns - S. Román; M.M. González-Duarte; A. Rodríguez-Rúa; L. Silva; M. Delgado (Regional Studies in Marine Science, 2025)

Natural regeneration of native woodlands in drylands subjected to disturbances: A basis for their ecological restoration - Yamila J. Duarte; Bárbara Guida-Johnson; Leandro M. Alvarez; María Agustina Aranda; Brian Leonardo A. Rios; Pablo E. Villagra (Forest Ecology and Management, 2025)

Cryopreservation going digital - Using computational fluid dynamics to optimize formulations and methods - Rafaela Neves; Andreia Duarte; Vitor Geraldes; Miguel A. Rodrigues (Cryobiology, 2025)

Geological and geomechanical properties of soft rocks from the Lower Jurassic Vale Das Fontes Formation (Lusitanian Basin, Portugal): an exploratory study - P. F. Moreira; C. F. Rodrigues; L. V. Duarte; J. P. Temporão de Sousa; A. Vega y de La Fuente; A. Maldonado-Zamora; M. J. Lemos de Sousa; H. I. Chaminé (Mediterranean Geoscience Reviews, 2025)

Quantitative summary of nine years of fungicide efficacy data for managing white spot and protecting yield in maize - MonalisaC. De Cól; Karla Braga; AdrianoA.P. Custódio; Marcelo G. Canteri; Lucas H. Fantin; Carlos M. Utiamada; Hércules D. Campos; Dagma D. Silva-Araújo; Rodrigo V. Costa; InêsF.U. Yada; Aildson P. Duarte; Alfredo R. Dias; et al. (Crop Protection, 2025)

Corrigendum to “Effects of artificial light at night on the early benthic stages of the prominent sea urchin Loxechinus albus” [Mar. Pollut. Bull. 219 (2025) 118289 (1–11)] - Patricio H. Manríquez; Diego Quintanilla-Ahumada; Claudio P. González; Paolo Domenici; Jorge Bravo; Andrés Camaño; José Pulgar; Pedro A. Quijón; Cristian Duarte (Marine Pollution Bulletin, 2025)

Biocontrol in action: Assessing the impact of a biocontrol agent on invasive plant seed dynamics - Liliana Neto Duarte; Hélia Marchante; Francisco A. López-Núñez; Fiona Impson; Francisco M. Moreira; Elizabete Marchante (Journal of Environmental Management, 2025)

A novel liquid-phase plasma discharge process for single-step emulsification and continuous biodiesel production - Maíra O. Palm; Lucas Y. Pavani; Luciano Senff; Diego A. Duarte; Rafael C. Catapan (Fuel, 2025)

Ohmic heating for attenuation of Lactobacillus acidophilus LA-5 in Minas Frescal cheese: probiotic survival, biological activity, and in vitro antimicrobial activity - Cássia P. Barros; Tatiana C. Pimentel; Ramon Silva; Maria Carmela K.H. Duarte; Eliane T. Mársico; Erick A. Esmerino; Pedro Henrique C. Felix; Carlos Augusto F. Oliveira; Beatriz L. Valente; Marcelo Cristianini; Mônica Q. Freitas; Adriano G. Cruz (Food Research International, 2025)

The role of Penicillium brevicompactum in bioprocessing plastic and metals from printed circuit boards - Diogo A. Ferreira-Filipe; Marta Carvalho; António J.S. Fernandes; Florinda M. Costa; Carla Patinha; Pedro Pato; Armando C. Duarte; Teresa Rocha-Santos; Ana L. Patrício Silva (Environmental Pollution, 2025)

Projected cooling and pCO2 conditions in upwelling zones and their influence on a prominent rocky shore ecosystem engineer - Nicole Jahnsen-Guzmán; Nelson A. Lagos; Marco A. Lardies; Pedro A. Quijón; Diego Quintanilla-Ahumada; M. Roberto García-Huidobro; Claudio García; Nicol Zúñiga-Cueto; Cristian Duarte (Estuarine, Coastal and Shelf Science, 2025)

Fast combustion digestion for determination of halogens in makeup for eye region by ion chromatography - Marcia F. Mesko; Alisson A. Silva; Filipe S. Rondan; Mariele S. Nascimento; Fabio A. Duarte; Erico M.M. Flores (Analytica Chimica Acta, 2025)

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

Association Between Spanish-Language Patient Navigation and Adherence to Multi-Target Stool DNA Testing Among Spanish-Speaking Patients at Sanitas Medical Center - Mallik Greene; Timo Pew; Shrey Gohil; A. Burak Ozbay; Juliana Vanessa Rincón López; Paul Limburg; Martha Duarte (Journal of Cancer Education, 2025)
Colorectal cancer (CRC) screening rates remain low among Spanish-speaking populations, in part due to language barriers. This study examined the association between Spanish-language patient navigation on adherence to multi-target stool DNA (mt-sDNA) testing among Spanish-speaking patients at Sanitas Medical Center (SMC). This retrospective analysis utilized data from Exact Sciences Laboratories LLC. It included Spanish-speaking individuals aged 45 to 75 years who received an mt-sDNA test kit between October 1, 2021, and August 1, 2022. Patients were categorized based on Spanish-language outreach (SLO) or English-language outreach (ELO). Adherence was defined as the percentage of kits that were returned with completed tests and successful results within 365 days of the initial shipment date. Chi-square tests and multivariable logistic regression were used to compare adherence between groups and identify factors associated with adherence. The final sample included 3,101 patients in the SLO group and 1,331 in the ELO group. The SLO group showed a 4.4% absolute increase in adherence compared to the ELO group (64.3% vs. 59.9%, p = 0.006). At 30 days, adherence was already higher among SLO patients (45.1% vs. 41.5%), and this difference persisted throughout the 12-month follow-up period. The increase in adherence was consistent across subgroups, including patients aged 50–64 years (64.4% vs. 58.5%, p = 0.002), males (62.2% vs. 55.5%, p = 0.008), and those seen by primary care providers (64.9% vs. 59.8%, p = 0.029). In adjusted logistic regression, SLO was associated with 20% higher odds of adherence compared to ELO (OR = 1.20, 95% CI 1.05–1.37, p = 0.007). Spanish-language patient navigation was associated with a 4.4% higher adherence to mt-sDNA CRC screening among Spanish-speaking patients. These findings suggest that culturally and linguistically tailored communication may support improved screening participation in underserved populations.

Effects of artificial light at night on the early benthic stages of the prominent sea urchin Loxechinus albus - Patricio H. Manríquez; Diego Quintanilla-Ahumada; Claudio P. González; Paolo Domenici; Jorge Bravo; Andrés Camaño; José Pulgar; Pedro A. Quijon; Cristian Duarte (Marine Pollution Bulletin, 2025)

Isolation and bioactivity evaluation of sesquiterpenes from soft corals of the genus Lemnalia collected in the Red Sea - Aikaterini Koutsaviti; Georgios Spyropoulos; Mohamed A. Tammam; Marie Kvasnicová; Gabriel Gonzalez; Tereza Štenclová; Susana Agusti; Carlos M. Duarte; Lucie Rarová; Miroslav Strnad; Vassilios Roussis; Efstathia Ioannou (Phytochemistry Letters, 2025)

Functionalized diterpenes featuring the cembrane skeleton from soft corals of the genus Sarcophyton collected in the Red Sea - Mohamed A. Tammam; Stefanos Kikionis; Susana Agusti; Carlos M. Duarte; Vassilios Roussis; Efstathia Ioannou (Phytochemistry Letters, 2025)

C15 acetogenins and sesquiterpenes with anti-inflammatory activity from red algae of the genus Laurencia collected in the Red Sea - Mohamed A. Tammam; Aikaterini Koutsaviti; Susana Agusti; Carlos M. Duarte; Efstathia Ioannou; Vassilios Roussis (Phytochemistry Letters, 2025)

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Comparative analysis of bacterial and microalgal natural astaxanthin: Part II — Biocompatibility, bioaccessibility, encapsulation, mutagenicity, and aquatic toxicity - Cassamo U. Mussagy; Ana L.R. Gini; Cauê B. Scarim; Jonatas L. Duarte; Marlus Chorilli; Gabriely F.G. Militão; Amanda dos Santos; Nayara P. Lima; Isabela S. Ribeiro; Charles W.I. Haminiuk; Fabiane O. Farias; Gisela de A. Umbuzeiro; et al. (Algal Research, 2025)

Aiding sea turtle conservation through coastal management - Jakob C. Christiaanse; Ad J. H. M. Reniers; Stefan G. J. Aarninkhof; Elias F. Ostertag; Ronel Nel; Carlos M. Duarte; José A. A. Antolínez (Frontiers in Marine Science, 2025)
Climate change and human activity pose increasing challenges to endangered sea turtles, which are key species in many marine ecosystems worldwide. Among these challenges are the flooding and erosion of nesting beaches. In this perspective, we argue that existing methods and tools from coastal science and management hold significant, yet underused, potential for sea turtle conservation. We introduce a stepwise framework for integrating sea turtle ecology and coastal management to address these coastal threats. The framework follows an Observe–Understand–Predict–Intervene cycle and links ecological thresholds, coastal processes, and management interventions across scales, from Regional Management Units (RMUs) to individual beaches. We illustrate how state-of-the-art monitoring, modeling, and nature-based solutions (NBS) can be embedded within this framework to inform when and how to intervene. Increased in-situ data collection and interdisciplinary collaboration will be critical to apply and refine this approach, thereby enhancing the long-term resilience of nesting habitats.

Influence of agronomic and processing factors on bioactive compounds of yerba mate (Ilex paraguariensis A. St.- Hil): A systematic review - Jéssica de Cássia Tomasi; Renata de A. Maggioni; Mônica Moreno Gabira; Natália Saudade de Aguiar; Manoela Mendes Duarte; Leandro Marcolino Vieira; Cristiane Vieira Helm; Ivar Wendling (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Network analysis reveals humans as top predators and the key role of cuttlefish in the food web structure of a marine protected area (Arrábida Natural Park) - Catarina Vinagre; Luís Almeida; Pilar Ronquillo; Vanessa Mendonça; Duarte Frade; Emanuel J. Gonçalves; Karim Erzini; Ester A. Serrão (Ecological Complexity, 2025)

Insights on microalgae-based technologies with potential impact on global methane budget – Perspectives for industrial applications - Leandro Madureira; Ana Soares; M. Salomé Duarte; Francisco Pereira; Diogo Francisco; Filipe Maciel; António A. Vicente; Vítor Vasconcelos; M. Alcina Pereira; Pedro Geada (Bioresource Technology, 2025)

Infection by colombian datura virus induces leaf deformation associated with Indigenous selection of angel’s trumpet (Brugmansia spp.) - Sergio A. Hernández-Duarte; Oscar A. Oliveros-Garay; Adriana González; Maria C. Delgado-Niño; Federico Roda (VirusDisease, 2025)
Angel’s trumpets ( Brugmansia spp.) are important medicinal and ornamental plants belonging to the Solanaceae family, domesticated in the Andean region of South America. Indigenous communities in the Colombian Andes have created unique medicinal cultivars exhibiting a variety of unusual shapes in leaves, and specific uses for ritual or medicinal procedures. These cultivars exhibit leaf symptoms typically associated with viral infections, including mosaic, vein chlorosis, and morphological deformities. Colombian datura virus (CDV) is one of the most studied viruses in Brugmansia , which is distributed globally and affects even other agriculturally significant hosts. The present study aimed to evaluate the viral infections in Colombian cultivars of the Brugmansia genus and the relationship between the presence of viruses and the symptom expression in their leaves. We searched for CDV in the transcriptomes from a set of Solanaceae species and found it mainly in Brugmansia medicinal cultivars and wild solanaceous species. Plant material from B. × candida with different symptoms was collected and inoculated into plants of representative genera in the Solanaceae family, to evaluate symptom expression. We confirmed the sap of CDV-infected Brugmansia ability to cause infections through mechanical inoculation and the CDV presence in the inoculated plants by RT-PCR and Sanger sequencing. Symptoms expressed by these plants included severe leaf deformations in agriculturally important plants such as Physalis peruviana , Solanum lycopersicum , and for the first time, reported the symptoms of the infection in S. melongena and S. quitoense .

Supramolecular environment and androgen receptor binding of taraxerol: from molecular structure to potential bioactivity function - Lara L. G. C. Rodrigues; Vitor S. Duarte; Antônio S. N. Aguiar; Vitória A. M. Silva; Hamilton B. Napolitano; Leonardo L. Borges (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Whole Genome Resequencing Reveals Origins and Global Invasion Pathways of the Japanese Beetle Popillia japonica - Rebecca Funari; Elahe Parvizi; Claudio Cucini; Sara Boschi; Elena Cardaioli; Daniel A. Potter; Shin‐ichiro Asano; Duarte Toubarro; Luca Jelmini; Francesco Paoli; Antonio Carapelli; Angela McGaughran; et al. (Molecular Ecology, 2025)
Invasive species are an increasing global threat given their ability to rapidly spread and adapt to novel environments. The adverse ecological and economic impacts of invasive species highlight the critical need to understand the mechanisms that underpin invasion processes and success. The Japanese beetle, Popillia japonica , is an invasive pest of remarkable interest, as it feeds on hundreds of economically valuable plant species. It has been expanding outside of its native range in Japan since the first decades of the 20th century, colonising large areas of North America and, more recently, Europe. Here, we compared whole‐genome resequencing data from individuals encompassing the entire species distribution to study the geographic differentiation of P. japonica populations and reconstruct expansion routes from Japan to the USA and Europe. We found six genomically distinguishable clusters, corresponding to the approximate colonisation areas at a continental scale. Our analysis supported an ancestral divergence between South and North/Central Japan, with the latter being the source of the initial invasion to the USA. Coalescent simulations supported independent bridgehead events from the USA to the Azores and Italy. We also investigated possible signals of selection to better understand the adaptive mechanisms that underlie the invasion success of P. japonica . However, the absence of strong selection signatures suggested that the beetle's adaptive ability might be embedded in pre‐existing genomic features. Our comprehensive genome‐wide dataset allowed a detailed inference of the invasion process and may be useful in determining the origin of P. japonica individuals in future invasion events.

Late Quaternary population expansion in gray brocket deer [ Subulo gouazoubira (G. Fisher, 1814), Cervidae, Mammalia] in Brazil - Alex Hubbe; Mark Hubbe; Elver Luiz Mayer; Eliane Nunes Chim; Paulo Miguel Haddad‐Martim; Augusto S. Auler; Luís B. Piló; William J. Pestle; Alba Rey‐Iglesia; Isac dos Santos Antônio Machado; Paulo C. F. Giannini; Eluzai Dinai Pinto Sandoval; et al. (Journal of Quaternary Science, 2025)
There is little information about the changes in the abundance of mammalian species in South America during the late Quaternary, which is a key parameter to understanding past ecological and evolutionary dynamics. Here, we describe a conspicuous increase in the abundance of the gray brocket deer ( Subulo gouazoubira G. Fisher, 1814; Mammalia) during the late Quaternary in Brazil based on paleontological evidence. We studied the material retrieved from pitfall deposits in Cuvieri Cave (Brazil) representing three time intervals (Late Pleistocene, Pleistocene/Holocene transition, and Holocene). The deposits in this cave were previously characterized in terms of facies composition, chronology, and overall taxa and taphonomy. We combined previous data with taxonomic identification at the species level for deer (morphological and ancient DNA analyses), quantification of the number of individuals for large mammals (>10 kg), taphonomic analyses, and stratigraphic distribution of specimens. Our results show that while in the Late Pleistocene gray brocket deer corresponded to up to 18% of 38 individuals, in the Holocene they represented at least 82% of 78 individuals. We interpret this change in frequency as a considerable increase in abundance in the surroundings of the cave, after excluding major taphonomical biases. The causes for this phenomenon are uncertain but could have involved a surplus of food availability and predation release due to the late Quaternary extinction event.

One-year concurrent training improves physical performance and handgrip strength in nursing home residents - Duarte Barros; Jonas Johansson; Tom Wilsgaard; José Magalhães; Joana Carvalho; Elisa A. Marques (GeroScience, 2025)

Multi-walled carbon nanotubes green-functionalized with iron nanoparticles for continuous removal of pharmaceutical pollutants through fixed-bed adsorption: Integrated experimental and machine learning approaches - Heloisa P. S. Costa; Mariana G. Oliveira; Emanuele D. V. Duarte; Lharissa Gomes; Rangabhashiyam Selvasembian; Meuris G. C. da Silva; Melissa G. A. Vieira (Environmental Science and Pollution Research, 2025)

Isa2p is essential in Saccharomyces cerevisiae for mitochondrial function and stress resistance by allowing Rip1p subunit assembly into cytochrome bc1 complex - Luis A Sánchez-Briones; Mauricio Gomez-Gallardo; Christian Cortes-Rojo; Elizabeth Sánchez-Duarte; Jesús Campos-García (Journal of Biosciences, 2025)

Cleaning validation in pharmaceutical quality control laboratories: a structured protocol for contamination risk mitigation - Maria J. Moura; André D. Pereira; Daniel J. F. Santos; Ana G. Silva; Carla C. A. D. Paiva; Belmiro P. M. Duarte (DARU Journal of Pharmaceutical Sciences, 2025)
Background Cleaning activities are critical in pharmaceutical manufacturing to prevent cross-contamination of Active Pharmaceutical Ingredients (APIs). Traditionally, cleaning validation protocols have focused on production lines. However, there is a growing trend toward extending these protocols to Quality Control (QC) laboratories, encompassing both glassware and stainless-steel equipment. Objectives This paper presents a systematic approach for developing cleaning validation protocols specifically designed for QC laboratory equipment, aimed at improving cleaning effectiveness and ensuring regulatory compliance. Methods The proposed methodology includes: (i) identifying the worst-case API; (ii) performing recovery studies to optimize sampling methods and solvent selection; and (iii) employing statistical tools such as descriptive analysis and hypothesis testing to refine the protocol in line with current industry standards. Results A case study involving Oxcarbazepine demonstrates the application of the proposed protocol, evaluating surface contamination across various QC instruments and assessing detergent residues to validate cleaning effectiveness. Conclusion The proposed strategy provides a structured, statistically grounded framework for developing cleaning validation protocols in QC laboratories, promoting effective contamination control and adherence to regulatory standards. Graphical abstract

Not regionally extinct: Rediscovery of Ruppia drepanensis in Portugal, the westernmost range edge in Europe - Duarte G. Frade; João Neiva; Jose Martínez-Garrido; Anne Davison; Luca Caminiti; Gonçalo G. Ramos; Gareth A. Pearson; Ester A. Serrão (Aquatic Botany, 2025)

Sesquiterpenes from the Saudi Arabian Red Sea sponge Lamellodysidea herbacea - Mohamed A. Tammam; Leto-Aikaterini Tziveleka; Carlos M. Duarte; Efstathia Ioannou; Vassilios Roussis (Phytochemistry Letters, 2025)

Artificial Light at Night (ALAN) alters the behavior and physiology of a sandy beach isopod. Are these effects reversible? - Valentina A. Galaz-Guajardo; Diego Quintanilla-Ahumada; Pedro A. Quijón; Josué Navarrete-Meneses; Nicole Jahnsen-Guzmán; Cristián Miranda-Benabarre; Nicol Zúñiga-Cueto; José Pulgar; Patricio H. Manríquez; Cristian Duarte (Marine Environmental Research, 2025)

Redefining innovation: the role of co-creation in collaborative new food product strategies - Bruna B Durço; Camile OL Farias; Tatiana C Pimentel; Elson R Tavares Filho; Adriana Gámbaro; Adriano G Cruz; Maria C KH Duarte; Erick A Esmerino (Current Opinion in Food Science, 2025)

Highly Efficient Bio-Based Composites from Natural Fibers for Fauna Protection and Oil Spill Remediation - Islla M. C. Silvino; Beatriz S. Alves; Eduardo J. Fonseca; Vanderson B. Bernardo; Carmem L. P. S. Zanta; Josealdo Tonholo; Laís F. A. M. Oliveira; José L. S. Duarte; Leonardo M. T. M. Oliveira (Environmental Processes, 2025)

Impacts of fluorite dissolution in semiarid endemic soil and ecotoxic effect estimated in Allium cepa - Ángel R. Díaz-Duarte; Gerardo A. Anguiano-Vega; Patricia Ponce-Peña; Roberto Briones-Gallardo; Antonio Aragón-Piña; Ma. Guadalupe Nieto-Pescador; Estela Ruiz-Baca; Fabiola S. Sosa-Rodríguez; Israel Labastida; René H. Lara (Environmental Geochemistry and Health, 2025)

The effects of agroforestry and conventional banana plantations on multiple dimensions of butterfly diversity in the Atlantic Forest - Dirleane O. Rossato; Cristiano A. Iserhard; Gabriel Nakamura; Leandro Duarte; Nicola Nadeau (Biodiversity and Conservation, 2025)
Environmental changes, particularly in agriculture, contribute significantly to biodiversity loss, with habitat fragmentation hindering dispersal and reducing biological diversity. Specific land uses can confine evolutionary groups to certain areas, decreasing local genetic and phylogenetic diversity but potentially increasing them at a larger spatial scale. Utilising genetic information at the population level, along with richness, phylogenetic and composition data at the community level, offers a comprehensive understanding of agriculture’s impact on biodiversity. In this study, we compared the effects of conventional and agroforestry banana plantations on butterflies’ dispersal and diversity relative to native forests. Analysing ddRAD genomic data from Heliconius ethilla narcaea at the population level and assessing richness, abundance, phylogenetic and species diversity of the Nymphalidae family at the community level, we found that agroforestry plantations exhibited the highest butterfly abundance and maintained the rarest genetic groups from H. ethilla narcaea . These genetic groups appeared in both native forests and agroforestry areas, more often in native forests, but were absent in conventional plantations despite evidence for extensive genetic dispersal. Regarding species composition, both banana plantations shared similar species but differed from the native forest, which contained a distinct and phylogenetically clustered group of species, possibly due to its unique microhabitat conditions and more complex structure. The presence of the rarest genetic groups in the population and the occurrence of distinct biological species emphasise the critical role of native forests within an anthropogenic landscape. Agroforestry demonstrates the potential to sustain biodiversity alongside food production.

Management intensity does not affect the ecological indicators of coffee agroforestry systems in agricultural landscapes of the Atlantic forest zone in Brazil - Vitoria Duarte Derisso; Ricardo Gomes César; Catherine Torres de Almeida; Pedro H. S. Brancalion; Danilo R. A. Almeida; Paulo G. Molin; Aline Souza; Edson Vidal (Agroforestry Systems, 2025)

Staying hooked: effective science engagement and communication in recreational fisheries - Pablo Pita; Sean Tracey; Robert Arlinghaus; Eneko Bachiller; Filipa Pinho-Duarte; Keno Ferter; Filipe Henriques; Samantha Hook; Kieran Hyder; Alejo Irigoyen; María P. Jiménez; Martín Laporta; et al. (Frontiers in Marine Science, 2025)
● This abstract summarizes the results of two expert consultations conducted to gather insights into effective communication and engagement strategies in recreational fisheries. ● Effective science communication fosters knowledge, understanding, and trust in both science and management decisions. ● Public involvement and stakeholder engagement are essential for effective management. ● Simplifying complex research findings and using diverse communication tools enhance awareness and understanding. ● Strong communication strategies are necessary to implement sustainable recreational fisheries management frameworks. ● Funding for communication efforts is often insufficient but remains crucial for success. ● Participatory workshops and data-sharing arrangements enhance collaboration and involvement. ● Multi-stakeholder consortiums and tailored communication strategies strengthen stakeholder engagement and promote adaptive governance. Interdisciplinary outreach and strategic social media use play vital roles in raising environmental awareness.

Enantioselective toxicity of propranolol on marine diatoms: Assessing growth, energy metabolism and oxidative damage in Phaeodactylum tricornutum - Marina Arenas; Eduardo Feijão; Irina A. Duarte; Vanessa F. Fonseca; Irene Aparicio; Esteban Alonso; Bernardo Duarte (Marine Pollution Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Monitoring the stability of aerobic granular sludge under increasing fractions of slowly biodegradable substrate using quantitative image analysis - Sérgio A. Silva; M. Salomé Duarte; António L. Amaral; Eugénio C. Ferreira; M. Madalena Alves; Daniela P. Mesquita (Chemosphere, 2025)

Impacts of Artificial Light at Night (ALAN) on coastal ecosystems: A study on the herbivore Ampithoe valida with focus on sex-dependent responses - Nicole Jahnsen-Guzmán; Diego Quintanilla-Ahumada; Ricarda Blum; Alejandro F. Gadda; Oriana A. Amorin; Cristian Miranda-Benabarre; José Pulgar; Cristian Duarte; Macarena S. Valiñas (Marine Pollution Bulletin, 2025)

Ingestive behaviour, performance, and methane emissions of pregnant alpacas grazing cultivated pastures in the high Peruvian Andes - Laura B. Gualdrón-Duarte; Cecilia Loza; José I. Gere; Nancy F. Huanca-Marca; Francisco E. Franco; Yemi Sanca Uscamayta; Rubén García‐Ticllacuri; Guadalupe Orellana Ligas; Diannett Benito López; Feliciano Rivera Pachiño; Juan E. Moscoso-Muñoz; Medardo A. Díaz-Céspedes; et al. (Livestock Science, 2025)

An engineered PD1-Fc fusion produced in N. benthamiana plants efficiently blocks PD1/PDL1 interaction - Shiva Izadi; Rafaela Abrantes; Simon Gumpelmair; Vinny Kunnummel; Henrique O. Duarte; Peter Steinberger; Celso A. Reis; Alexandra Castilho (Plant Cell Reports, 2025)
Key message Plant-made PD1–Fc fusions engineered for optimized glycosylation and Fc-receptor engagement are highly efficient in blocking PD1/PDL1 interactions and can be cost-effective alternatives to antibody-based immune checkpoint inhibitors. Abstract Immune checkpoint inhibitors (ICIs) are antibodies to receptors that have pivotal roles during T-cell activation processes. The programmed cell death 1 (PD1) can be regarded as the primary immune checkpoint and antibodies targeting PD1 or its ligand PDL1 have revolutionized immunotherapy of cancer. However, the majority of patients fail to respond, and treatment resistance as well as immune-related adverse events are commonly associated with this therapy. Alternatives to antibody-based ICIs targeting the PD1 pathway may bear the potential to overcome some of these shortcomings. Here, we have used a plant expression platform based on the tobacco relative Nicotiana benthamiana to generate immunoglobulin fusion proteins harboring the wild type or an affinity-enhanced PD1 ectodomain. We have exploited the versatility of our system to generate variants that differed regarding their glycosylation profile as well as their capability to engage Fc-receptors. Unlike its wild-type counterpart, the affinity-enhanced versions showed strongly augmented capabilities to engage PDL1 in both protein- and cell-based assays. Moreover, in contrast with clinical antibodies, their binding is not affected by the glycosylation status of PDL1. Importantly, we could demonstrate that the plant-made PD1 fusion proteins are highly efficient in blocking inhibitory PD1 signaling in a T cell reporter assay. Taken together, our study highlights the utility of our plant-based protein expression platform to generate biologics with therapeutic potential. Targeting PDL1 with plant derived affinity-enhanced PD1 immunoglobulin fusion proteins may reduce overstimulation associated with antibody-based therapies while retaining favorable features of ICIs such as long serum half-life.

Entropy-based assessment of complexity structural effects of the third dimension, case seismic nest of Los Santos (Colombia) - Carlos A. Mantilla-Duarte; José M. Angulo (Stochastic Environmental Research and Risk Assessment, 2025)
This paper focuses on analysing, from an entropy-based approach, the implications on structural complexity associated with the third dimension (depth), considering along with latitude and longitude as part of the spatial distribution of earthquakes recorded in the Los Santos seismic nest within the Bucaramanga geologic complex, Santander, Colombia, during the period from January 2018 to December 2021. Highlighting entropy as a measure of uncertainty and system organisation, variations between two and three dimensions of significant characteristics of spatio-temporal patterns of registered seismic events are explored. After a preliminary descriptive analysis, simulations and randomisations are performed to validate the observed effects. The study proposes future directions, such as the consideration of non-linear distance measures and the inclusion of released energy in the entropy calculation, to contribute to the understanding of the spatial complexity of seismic phenomena and provide a solid basis for future research in this critical area.

Particle‐Associated Bacterioplankton Communities Across the Red Sea - Larissa Frühe; Shannon G. Klein; Carlos Angulo‐Preckler; Anastasiia Martynova; Taiba Alamoudi; Jacqueline V. Alva García; Silvia Arossa; Jessica Breavington; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Anieka J. Parry; et al. (Environmental Microbiology, 2025)
Pelagic particle‐associated bacterioplankton play crucial roles in marine ecosystems, influencing biogeochemical cycling and ecosystem functioning. However, their diversity, composition, and dynamics remain poorly understood, particularly in unique environments such as the Red Sea. In this study, we employed eDNA metabarcoding to comprehensively characterise bacterioplankton communities associated with pelagic particles in a three‐dimensional assessment spanning depths from the surface to a depth of 2300 m along the full length of the eastern Red Sea within the exclusive economic zone of the Kingdom of Saudi Arabia. Our results reveal a diverse assemblage of taxa, with Pseudomonadota, Cyanobacteriota, and Planctomycetota being the dominant phyla. We identified pronounced spatial variability in community composition among five major Red Sea geographical regions, with a third of all amplicon sequence variants being unique to the Southern Red Sea in contrast to a relatively homogenous distribution along the water column depth gradient. Our findings contribute to a deeper understanding of microbial ecology in the Red Sea and provide valuable insights into the factors governing pelagic particle‐associated bacterioplankton communities in this basin.

Molecular responses in the intestine of Atlantic salmon (Salmo salar) following light and diet stimulation of smoltification: Potential molecular markers for a seawater-ready smolt - Pasqualina Gaetano; Vilma Duarte; Anja Striberny; David G. Hazlerigg; Even H. Jørgensen; Marco A. Campinho; Juan Fuentes (Aquaculture, 2025)

Thuwalamides A–E: Polychlorinated amides from the marine sponge Lamellodysidea herbacea collected from the Saudi Arabian Red Sea - Mohamed A. Tammam; Nikolaos Tsoureas; Dafni-Ioanna Diakaki; Carlos M. Duarte; Vassilios Roussis; Efstathia Ioannou (Phytochemistry, 2025)

The importance of upwelling conditions as drivers of feeding behavior and thermal tolerance in a prominent intertidal fish - Melissa Fernández; Cristian Duarte; Marcela Aldana; Joaquín Delgado-Rioseco; Francisca Blanco-Herrera; Oscar Varas; Pedro A. Quijón; Diego Quintanilla-Ahumada; M Roberto García-Huidobro; José Pulgar (Marine Environmental Research, 2025)

Exploring the relationship between upwelling intensity and socio-ecological attributes of marine exploitation areas for benthic resources (MEABRs), along the southern Humboldt Current system - Melissa Fernández; Marcela Aldana; Cristian Duarte; M. Roberto García-Huidobro; Oscar Varas; Rodrigo A. Estévez; Javiera Pulgar; Pedro A. Quijón; José Pulgar (Journal of Environmental Management, 2025)

Differentially spliced mitochondrial CYP419A1 contributes to ethiprole resistance in Nilaparvata lugens - B. Zeng; A.J. Hayward; A. Pym; A. Duarte; W.T. Garrood; S-F Wu; C-F Gao; C. Zimmer; M. Mallott; T.G.E. Davies; R. Nauen; C. Bass; et al. (Insect Biochemistry and Molecular Biology, 2025)

Glacial-interglacial changes in Antarctic Intermediate Water advection in the Southeast Pacific during the last 787 kyr - Karol O. Duarte; Igor M. Venancio; Rodrigo A. Nascimento; Ana Luiza S. Albuquerque; Thiago P. Santos; Stefano Crivellari; Cristiano M. Chiessi (Global and Planetary Change, 2025)

Bayesian networks facilitate updating of species distribution and habitat suitability models - Adam Duarte; Robert S. Spaan; James T. Peterson; Christopher A. Pearl; Michael J. Adams (Ecological Modelling, 2025)

A new way to use nonlocal symmetries to determine first integrals of second-order nonlinear ordinary differential equations - A. Braz; L.G.S. Duarte; H.S. Ferreira; A.C.S. Guabiraba; L.A.C.P. da Mota; I.S.S. Nascimento (Computer Physics Communications, 2025)

Recent developments on aerial lab-on-a-drone platforms for remote environmental monitoring: A review - Habdias A. Silva-Neto; Danielle da Silva Sousa; Lucas C. Duarte; João Flávio da Silveira Petruci; Wendell K.T. Coltro (Analytica Chimica Acta, 2025)

Age, cancer, and the dual burden of cancer and doxorubicin in skeletal muscle wasting in female rats: which one to blame? - Alexandra Moreira-Pais; Rita Ferreira; Inês Aires; Cláudia Sousa-Mendes; Rita Nogueira-Ferreira; Fernanda Seixas; Adelino Leite-Moreira; Paula A. Oliveira; José A. Duarte (Biogerontology, 2025)

First report of Colletotrichum musicola causing anthracnose on Dioscorea alata - Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Anthony Carlos da Silva; Fernanda Oliveira da Silva; Willie Anderson dos Santos Vieira; Stephan Miller; Lisa A. Castlebury; Marcos Paz Saraiva Camara (Journal of Plant Pathology, 2025)

Empowering informed choices: How computer vision can assists consumers in making decisions about meat quality - Guilherme L. Menezes; Dante T. Valente Junior; Rafael E.P. Ferreira; Dario A.B. Oliveira; Julcimara A. Araujo; Marcio Duarte; Joao R.R. Dorea (Meat Science, 2025)

Porvac® subunit vaccine induces neutralizing antibodies against all three main classical swine fever virus genotypes - Yusmel Sordo-Puga; Elaine Santana-Rodríguez; Danny Pérez-Pérez; Mary Karla Méndez-Orta; Talía Sardina-González; Milagros Vargas-Hernández; Carlos A. Duarte; María Pilar Rodríguez-Moltó; Mario P. Estrada; Aruna Ambagala; Marisela Suárez-Pedroso (Archives of Virology, 2025)

Unravelling the Universal Spatial Properties of Coral Reefs - Àlex Giménez‐Romero; Manuel A. Matías; Carlos M. Duarte (Global Ecology and Biogeography, 2025)
Aim To characterise the size and geometry of coral reefs on a global scale. Location Global. Time Period Present. Major Taxa Studied Coral reefs. Methods We process the Allen Coral Atlas database of shallow‐water tropical reefs to obtain a comprehensive and unprecedented inventory of coral reefs worldwide. We analyse different macroecological and morphological patterns, including size distribution, the area‐perimeter relationship, inter‐reef distance distribution, and the fractal dimension of individual reefs and coral provinces. Results We identified a total of 1,579,772 individual reefs worldwide (> 1000 m 2 ), extending over a total of 52,423 km 2 of ocean area with mean and median sizes of 3.32 and 0.3 ha, respectively. We unravelled three universal laws that are common to all coral reef provinces: the size‐frequency distribution and the inter‐reef distance distribution follow power laws with an exponent of 1.8 and 2.33, respectively. At the same time, the area‐perimeter relationship conforms to a power‐law with an exponent of 1.26. Furthermore, we demonstrate that coral reefs develop fractal patterns characterised by a perimeter fractal dimension of and a surface fractal dimension of . Our analysis suggests that coral reefs tend to evolve from simple rounded filled shapes to more complex, elongated and less compact forms, developing into fractal structures with a consistent surface fractal dimension and an increasing perimeter fractal dimension as they grow. Main Conclusions Coral reefs display intricate fractal‐like geometries and exhibit universal macroecological patterns, largely independent of their geographical location. The universality of the observed patterns suggests that these features possibly stem from the highly conserved interactions of biological, physical and chemical processes. Over geological scales, these processes lead to reef landscape patterns common among all provinces, providing new information relevant to reef growth modelling.

Ohmic pasteurization of probiotic chocolate dairy desserts and its quality attributes - Gabriela R.A. Silva; Wanessa P. da Silva; Elson R. Tavares Filho; Louise de A. Sobral; Carolina P.C. Martins; Benjamin Mahieu; Jonas T. Guimarães; Maria Carmela K.H. Duarte; Mônica M. Pagani; Ramon Silva; Monica Q. Freitas; Eliane T. Mársico; et al. (Food Research International, 2024)

Residential relocation and changes in patterns of environmental exposures by health determinants among children and adolescents in Catalonia, Spain - A. Pistillo; S. Warkentin; A. Abellan; J. de Bont; T. Ranger; L. Pérez-Crespo; M. Cirach; A. Perramon-Malavez; S. Khalid; M. Nieuwenhuijsen; M. Vrijheid; T. Duarte-Salles (Environmental Research, 2024)

Leaf architecture and functional traits for 122 species at the University of California Botanical Garden at Berkeley - Ilaine Silveira Matos; Mickey Boakye; Monica Antonio; Sonoma Carlos; Ashley Chu; Miguel A. Duarte; Andrea Echevarria; Adrian Fontao; Lisa Garcia; LeeAnn Huang; Breanna Carrillo Johnson; Shama Joshi; et al. (Ecology, 2024)
The dataset contains leaf venation architecture and functional traits for a phylogenetically diverse set of 122 plant species (including ferns, basal angiosperms, monocots, basal eudicots, asterids, and rosids) collected from the living collections of the University of California Botanical Garden at Berkeley (37.87° N, 122.23° W; CA, USA) from February to September 2021. The sampled species originated from all continents, except Antarctica, and are distributed in different growth forms (aquatic, herb, climbing, tree, shrub). The functional dataset comprises 31 traits (mechanical, hydraulic, anatomical, physiological, economical, and chemical) and describes six main leaf functional axes (hydraulic conductance, resistance and resilience to damages caused by drought and herbivory, mechanical support, and construction cost). It also describes how architecture features vary across venation networks. Our trait dataset is suitable for (1) functional and architectural characterization of plant species; (2) identification of venation architecture‐function trade‐offs; (3) investigation of evolutionary trends in leaf venation networks; and (4) mechanistic modeling of leaf function. Data are made available under the Open Data Commons Attribution License.

The impacts of artificial light at night (ALAN) spectral composition on key behavioral traits of a sandy beach isopod - Diego Quintanilla-Ahumada; Pedro A. Quijón; Nicole Jahnsen-Guzmán; Nicol Zúñiga-Cueto; Cristian Miranda-Benabarre; K. Devon Lynn; José Pulgar; Javier Palma; Patricio H. Manríquez; Cristian Duarte (Marine Pollution Bulletin, 2024)

Bioaccumulation, biodistribution, and transformation of polyvinylpyrrolidone-coated silver nanoparticles in edible seaweeds - Monica Quarato; Laura Rodriguez-Lorenzo; Ivone Pinheiro; Juan José López-Mayán; Mick Mackey; Antonio Moreda-Piñeiro; Miguel Spuch-Calvar; Julie Maguire; Pilar Bermejo-Barrera; Miguel A. Correa-Duarte; Begoña Espiña (Science of The Total Environment, 2024)

Rediscovery of Althenia (Potamogetonaceae) in Portugal, 168 years after the last collection - Duarte G. Frade; João Neiva; Anne Davison; Gareth A. Pearson; Ester A. Serrão (Aquatic Botany, 2024)

Effect of ohmic heating on the structure and properties of flexible multilayer packaging - Luís Marangoni Júnior; Rui M. Rodrigues; Ricardo N. Pereira; Pedro Esteves Duarte Augusto; Danielle Ito; Fábio Gomes Teixeira; Marisa Padula; António A. Vicente (Food Chemistry, 2024)

Agricultural drainage pipe in Guadua angustifolia: implications of Manning roughness in Pitalito forest stands - M. Duarte-Toro; J. M. Silva-Chavarro; J. A. Gil-Hernandez (International Journal of Environmental Science and Technology, 2024)
Water extraction in agricultural fields with high saturation levels requires drainage systems that increase land preparation costs, so looking for new options for materials that function as drainage pipes that provide a better technical–economic relationship is crucial. In this study, Manning roughness values were analyzed in the culms of Guadua angustifolia considering three factors: flow, section, and location site of the forest stands. This study was carried out in the rural area of the municipality of Pitalito; the characterization of culms was made based on the Colombian technical standards (NTC) 5726 and 5727, the cutting and elaboration of test pieces according to the NTC 5525, and finally, the hydraulic tests were carried out. The roughness values oscillated between 0.1089 and 0.0337 according to the different flow evaluated values in the laboratory tests, between 0.1004 and 0.0356 for the sections analyzed, and between 0.0909 and 0.0533 according to the sample extraction area. The multifactor ANOVA established a significant relationship for the flow and section on the Manning n roughness, while the zone was insignificant.

The potential application of Czenspinskia transversostriata in biological control - Dominiek Vangansbeke; Marcus V. A. Duarte; Jonas Merckx; Alfredo Benavente; Ian Stevens; Heidi Debie; Nikolaas Viaene; Manon Guilbaud; Juliette Pijnakker; Hanne Steel; Felix Wäckers (Experimental and Applied Acarology, 2024)

Exposing illegal hunting and wildlife depletion in the world's largest tropical country through social media data - Hani R. El Bizri; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Lauren Coad; Thais Queiroz Morcatty; Gabriel Favero Massocato; Arnaud L. J. Desbiez; João Vitor Campos‐Silva; Daniel Zani La Laina; José Maurício Barbanti Duarte; et al. (Conservation Biology, 2024)
Globally, illegal sport hunting can threaten prey populations when unregulated. Due to its covert nature, illegal sport hunting poses challenges for data collection, hindering efforts to understand the full extent of its impacts. We gathered social media data to analyze patterns of illegal sport hunting and wildlife depletion across Brazil. We collected data for 2 years (2018–2020) across 5 Facebook groups containing posts depicting pictures of illegal sport hunting events of native fauna. We described and mapped these hunting events by detailing the number of hunters involved, the number of species, the mean body mass of individuals, and the number and biomass of individuals hunted per unit area, stratified by Brazilian biome. We also examined the effects of defaunation on hunting yield and composition via regression models, rank–abundance curves, and spatial interpolation. We detected 2046 illegal sport hunting posts portraying the hunting of 4658 animals (∼29 t of undressed meat) across all 27 states and 6 natural biomes of Brazil. Of 157 native species targeted by hunters, 19 are currently threatened with extinction. We estimated that 1414 hunters extracted 3251 kg/million km 2 . Some areas exhibited more pronounced wildlife depletion, in particular the Atlantic Forest and Caatinga biomes. In these areas, there was a shift from large mammals and reptiles to small birds as the main targeted taxa, and biomass extracted per hunting event and mean body mass across all taxonomic groups were lower than in other areas. Our results highlight that illegal sport hunting adds to the pressures of subsistence hunting and the wild meat trade on Brazil's wildlife populations. Enhanced surveillance efforts are needed to reduce illegal sport hunting levels and to develop well‐managed sustainable sport hunting programs. These can support wildlife conservation and offer incentives for local communities to oversee designated sport hunting areas.

P15-03 Immunotoxicity as an endpoint: on the lookout for contaminants of emerging concern for drinking water quality - S.M. Shaikh; R. Hoondert; T. Pronk; D. Duarte; A. Reus; C. Houtman; M. Schriks; R. van der Oost; J. Ezendam; R. Pieters; M.M.L. Dingemans (Toxicology Letters, 2024)

P14-06 The cytotoxicity of bortezomib in AC16 cardiac cells and possible therapeutic options involving Nrf2 - C. Vitorino-Oliveira; S. Kahremany; L. Nisim; M. Duarte-Araújo; F. Carvalho; A. Gruzman; V.M. Costa (Toxicology Letters, 2024)

P13-31 Characterization of human isogenic epithelial cell lines as a relevant tool to study colon carcinogenesis and interaction between genes and environment - A. Tête; L. Arnaud; H. Le Mentec; N. Poupin; I. Gallais; N. Tournade; C. Duarte Hospital; Y. Lippi; F. Mathevet; C. Pilati; G. Lefort; C. Lavau; et al. (Toxicology Letters, 2024)

P13-20 Exposure to mixtures of fungicides promotes hallmarks of cancer in human colon cancer cells - K. Debizet; A. Tête; C. Duarte-Hospital; J. Imler; X. Coumoul; S. Bortoli (Toxicology Letters, 2024)

P13-18 Succinate Dehydrogenase inhibitors (SDHi) fungicides induce mitochondrial dysfunction and metabolic reprogramming in human colon cells - C. Duarte-Hospital; A. Tête; K. Debizet; C. Rives; J. Imler; L. Galès; F. Bellvert; J. Dairou; R. Barouki; J.W. Shay; J. Bastin; S. Mouillet-Richard; et al. (Toxicology Letters, 2024)

Splitting light pollution: Wavelength effects on the activity of two sandy beach species - Diego Quintanilla-Ahumada; Pedro A. Quijón; Nicole Jahnsen-Guzmán; K. Devon Lynn; José Pulgar; Javier Palma; Patricio H. Manríquez; Cristian Duarte (Environmental Pollution, 2024)

Global trends in applying decision science in mangrove restoration: are we missing some dimensions? - J. Alexandra Rodríguez-Rodríguez; Micheli Duarte de Paula Costa; Melissa Wartman; A. Rifaee Rasheed; Maria Palacios; Peter Macreadie (Ocean & Coastal Management, 2024)

Bacterial septicemia and herpesvirus infection in Antarctic fur seals (Arctocephalus gazella) stranded in the São Paulo coast, Brazil - Aricia Duarte-Benvenuto; A. M. Sánchez-Sarmiento; A. C. Ewbank; R. Zamana-Ramblas; S. Costa-Silva; N. Silvestre; T. Faita; L. B. Keid; R. M. Soares; C. F. Pessi; J. R. Sabbadini; M. F. Borges; et al. (Veterinary Research Communications, 2024)
In August 2021, two juvenile male Antarctic fur seals ( Arctocephalus gazella ) stranded in the southeastern Brazilian coast and were referred to rehabilitation centers. The animals presented increased body temperature, prostration, respiratory distress and despite treatment died. A necropsy following a standardized protocol was performed, and formalin-fixed tissues were processed for microscopic examination. Samples were screened for morbillivirus, herpesvirus, and Brucella spp. by molecular analyses (PCR, RT-PCR). Bacteriological culture was performed in samples collected from the lungs, trachea, and lymph nodes of both cases. The main histopathologic findings were of infectious nature, including multifocal necrotizing and fibrinous mixed interstitial pneumonia, bronchiolitis, and bronchitis, with intralesional myriad bacteria associated with vascular fibrinoid necrosis. Pseudomonas aeruginosa was isolated from tracheal and lung swabs of Case 1, and Klebsiella oxytoca was found in nostril swabs, tracheobronchial lymph nodes, and lung of Case 2. Gammaherpesvirus infection was detected in both cases, and the sequences retrieved were classified into the genus Percavirus . All tested samples were PCR-negative for Brucella spp. and morbillivirus. We hypothesize that the deficient immunological status in association with starvation predisposed the reactivation of herpesvirus and secondary bacterial co-infections. To the authors’ knowledge, this is the first molecular detection of herpesvirus in an Antarctic pinniped. These findings reinforce that Otariid gammaherpesvirus circulating in the Southern Hemisphere are likely endemic in the Arctocephalus genus. This report contributes to the current knowledge of health aspects affecting wild pinnipeds, especially in the poorly studied Antarctic species.

Retention of per- and polyfluoroalkyl substances by syringe filters - Ke He; Anna Feerick; Hongyue Jin; Jahir A. Batista Andrade; Marylia Duarte Batista; Caitlyn Dugan; Lee Blaney (Environmental Chemistry Letters, 2024)
Per- and polyfluoroalkyl substances (PFAS) are being increasingly measured in water and wastewater due to emerging toxicity concerns and strict regulatory limits. Previous studies have filtered water samples to remove suspended solids before PFAS analysis. However, filtration may introduce negative bias to measured PFAS concentrations. Using a well-controlled syringe pump assembly, we evaluated retention of six perfluoroalkyl carboxylates, three perfluoroalkyl sulfonates, one fluorotelomer sulfonate, and two perfluorooctane sulfonamides by glass-fiber, glass-fiber cellulose acetate, nylon, polyethersulfone, polypropylene, polyvinylidene fluoride/ difluoride, and surfactant-free cellulose acetate filters. The impacts of water quality and operational parameters were also investigated for select filter types. We found that PFAS were retained on all filters, with the glass-fiber cellulose acetate filters demonstrating the lowest retention. For all filters, PFAS retention was linearly related to chain length and hydrophobicity above certain thresholds ( i.e. , log D higher than 1.5). Importantly, more PFAS were retained at low filtrate volumes, and ~ 30 mL filtrate was required before the retention efficiencies stabilized. Solution pH only affected the retention of perfluorooctane sulfonamides. Pore size ( i.e. , 0.20, 0.45, 0.70 µm), filtration rate ( i.e. , 0.5, 1.0 mL min −1 ), and PFAS concentration ( i.e. , 10, 100 µg L −1 ), did not exert major influences on PFAS retention. The presence of dissolved organic matter improved PFAS permeation. Based on the reported results, filtration introduces bias and is not recommended for sample pretreatment.

Biodegradation of e-waste microplastics by Penicillium brevicompactum - Diogo A. Ferreira-Filipe; Leila Oliveira; Ana Paço; António J.S. Fernandes; Florinda M. Costa; Armando C. Duarte; Teresa Rocha-Santos; Ana L. Patrício Silva (Science of The Total Environment, 2024)

Interplay between diphenyl diselenide and copper: Impact on D. melanogaster survival, behavior, and biochemical parameters - G.S. Rieder; T. Duarte; C.P. Delgado; A. Rodighiero; P.A. Nogara; L. Orian; M. Aschner; C.L. Dalla Corte; J.B.T. Da Rocha (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A sedimentary DNA record of the Atacama Trench reveals biodiversity changes in the most productive marine ecosystem - Diego Elihú Rivera Rosas; Nathan R. Geraldi; Ronnie N. Glud; Kazumasa Oguri; Sophie A. Haond; Carlos M. Duarte (Global Change Biology, 2024)
The hadopelagic environment remains highly understudied due to the inherent difficulties in sampling at these depths. The use of sediment environmental DNA (eDNA) can overcome some of these restrictions as settled and preserved DNA represent an archive of the biological communities. We use sediment eDNA to assess changes in the community within one of the world's most productive open‐ocean ecosystems: the Atacama Trench. The ecosystems around the Atacama Trench have been intensively fished and are affected by climate oscillations, but the understanding of potential impacts on the marine community is limited. We sampled five sites using sediment cores at water depths from 2400 to ~8000 m. The chronologies of the sedimentary record were determined using 210 Pb ex . Environmental DNA was extracted from core slices and metabarcoding was used to identify the eukaryote community using two separate primer pairs for different sections of the 18S rRNA gene (V9 and V7) effectively targeting pelagic taxa. The reconstructed communities were similar among markers and mainly composed of chordates and members of the Chromista kingdom. Alpha diversity was estimated for all sites in intervals of 15 years (from 1842 to 2018), showing a severe drop in biodiversity from 1970 to 1985 that aligns with one of the strongest known El Niño events and extensive fishing efforts during the time. We find a direct impact of sea surface temperature on the community composition over time. Fish and cnidarian read abundance was examined separately to determine whether fishing had a direct impact, but no direct relation was found. These results demonstrate that sediment eDNA can be a valuable emerging tool providing insight in historical perspectives on ecosystem developments. This study constitutes an important step toward an improved understanding of the importance of environmental and anthropogenic drivers in affecting open and deep ocean communities.

Phytochemical study of Magonia pubescens A. St.-Hil. and cytotoxicity of branches aqueous extract on breast cancer and leukemia cells - Acácio R. A. Moraes; Ezequias P. Siqueira; Markus Kohlhoff; Fernanda C. G. Evangelista; Adriano P. Sabino; Sidney A. Vieira Filho; Antônio F. C. Alcântara; Lucienir P. Duarte; Grasiely F. Sousa (Natural Product Research, 2024)

ENSO effects on the relationship between aerosols and evapotranspiration in the south of the Amazon biome - Rafael Palácios; Daniela Castagna; Luzinete Barbosa; Adilson P. Souza; Breno Imbiriba; Cornélio A. Zolin; Danielle Nassarden; Leilane Duarte; Fernando G. Morais; Marco A. Franco; Glauber Cirino; Paulo Kuhn; et al. (Environmental Research, 2024)

Freezing and thawing in Antarctica: characterization of antifreeze protein (AFP) producing microorganisms isolated from King George Island, Antarctica - J. C. Lopes; V. P. Veiga; B. Seminiuk; L. O. F. Santos; A. M. C. Luiz; C. A. Fernandes; C. T. Kinasz; V. H. Pellizari; R. T. D. Duarte (Brazilian Journal of Microbiology, 2024)

Precipitation masks the effect of temperature on Birch airborne pollen start, and previous summer temperature affects pollen intensity; A 31-year study at its southwestern distribution boundary - Guillermo Guada; María Fernández-González; Rubén Amigo; Duarte A. Dias-Lorenzo; Kenia C. Sánchez Espinosa; Francisco Javier Rodríguez-Rajo (Agricultural and Forest Meteorology, 2024)

Contributions of the IUCN Red List of Ecosystems to risk‐based design and management of protected and conserved areas in Africa - David A. Keith; Somaya Magdy M. Ghoraba; Eric Kaly; Kendall R. Jones; Ané Oosthuizen; David Obura; Hugo M. Costa; Fahiema Daniels; Eleutério Duarte; Hedley Grantham; Mishal Gudka; Juliet Norman; et al. (Conservation Biology, 2024)
Protected and conserved areas (PCAs) are key ecosystem management tools for conserving biodiversity and sustaining ecosystem services and social cobenefits. As countries adopt a 30% target for protection of land and sea under the Global Biodiversity Framework of the United Nations Convention on Biological Diversity, a critical question emerging is, which 30%? A risk‐based answer to this question is that the 30% that returns the greatest reductions in risks of species extinction and ecosystem collapse should be protected. The International Union for Conservation of Nature (IUCN) Red List protocols provide practical methods for assessing these risks. All species, including humans, depend on the integrity of ecosystems for their well‐being and survival. Africa is strategically important for ecosystem management due to convergence of high ecosystem diversity, intense pressures, and high levels of human dependency on nature. We reviewed the outcomes (e.g., applications of ecosystem red‐list assessments to protected‐area design, conservation planning, and management) of a symposium at the inaugural African Protected Areas Congress convened to discuss roles of the IUCN Red List of Ecosystems in the design and management of PCAs. Recent progress was made in ecosystem assessment, with 920 ecosystem types assessed against the IUCN Red List criteria across 21 countries. Although these ecosystems spanned a diversity of environments across the continent, the greatest thematic gaps were for freshwater, marine, and subterranean realms, and large geographic gaps existed in North Africa and parts of West and East Africa. Assessment projects were implemented by a diverse community of government agencies, nongovernmental organizations, and researchers. The assessments have influenced policy and management by informing extensions to and management of formal protected area networks supporting decision‐making for sustainable development, and informing ecosystem conservation and threat abatement within boundaries of PCAs and in surrounding landscapes and seascapes. We recommend further integration of risk assessments in environmental policy and enhanced investment in ecosystem red‐list assessment to fill current gaps.

Artificial light at night alters the feeding activity and two molecular indicators in the plumose sea anemone Metridium senile (L.) - K. Devon Lynn; Diego Quintanilla-Ahumada; Cristian Duarte; Pedro A. Quijón (Marine Pollution Bulletin, 2024)

Assessing the euryhaline characteristics and metabolic responses of meagre (Argyrosomus regius) when reared under different salinities: Opportunities for aquaculture refinement - Marco F.L. Lemos; Cátia S.E. Silva; Lénia D. Rato; Alexandre F.S. Marques; Ricardo Passos; Irina A. Duarte; Bernardo Duarte; Vanessa F. Fonseca; Sara C. Novais (Aquaculture, 2024)

Hydrologic Evaluation of the Global Precipitation Measurement Mission over the U.S.: Effect of Spatial and Temporal Scales - Devon Woods; Pierre-Emmanuel Kirstetter; Humberto Vergara; Jorge A. Duarte; Jeffrey Basara (Journal of Hydrology, 2024)

Endophytic species of Colletotrichum associated with cashew tree in northeastern Brazil - Diana Gissell Barreto Ramos; Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Anthony Carlos da Silva; Willie Anderson dos Santos Vieira; Lisa A. Castlebury; Marcos Paz Saraiva Câmara (Fungal Biology, 2024)

Lost in the dark: Antipatharia-Symbiodiniaceae association in the deep waters of the Red Sea - Silvia Vicario; Tullia I. Terraneo; Carolina Bocanegra Castano; Giovanni Chimienti; Nicolas Oury; Silvia Vimercati; Benjamin C. C. Hume; Fabio Marchese; Megan K. B. Nolan; Ameer A. Eweida; Sam J. Purkis; Mattie Rodrigue; et al. (Frontiers in Marine Science, 2024)
Black corals (Hexacorallia: Antipatharia) are a major component of mesophotic and deep marine ecosystems. Due to their preference for light deprived environments, black corals have historically been considered azooxanthellate, yet recent works have found them in association with dinoflagellates of the family Symbiodiniaceae down to 396 m depth. While corals and Symbiodiniaceae generally establish a symbiotic relationship in shallow water environments, the implications of this association is less well understood at deeper depths, where low light penetration cannot sustain efficient photosynthetic activity for the algae. However, Symbiodinaceae are not obligate autotrophs, and their capacity for heterotrophic feeding categorizes them as mixotrophs. In this study, we investigated the presence and diversity of Symbiodiniaceae associated with the deep-sea black coral Bathypathes thermophila (Antipatharia: Schizopathidae), collected from 204 to 655 m depth in the Saudi Arabian Red Sea. Using high-throughput sequencing of the ITS2 region, we report (1) the deepest record to date of Symbiodiniaceae associated with an anthozoan from 655 m, and (2) the first Red Sea record of Antipatharia in association with Symbiodiniaceae. Our analyses revealed that 14 out of 27 colonies of B. thermophila were associated with Symbiodiniaceae of the genera Cladocopium and Durusdinium . We unveiled 16 novel ITS2 type profiles, possibly unique to black corals and/or to these depths, along with seven profiles that were already known from shallow-water hard corals. No significant pattern was detected in terms of community diversity in relation to depth or sampling locality. Our study supports the existence of black corals-Symbiodiniaceae association and warrants further research to better understand the evolutionary processes and physiological mechanisms driving this association, specifically in light deprived environments.

Novel behavioral observations and body scarring for the bluntnose sixgill shark (Hexanchus griseus) offer clues to reproductive patterns and potential mating events - Austin J. Gallagher; Christine de Silva; Denley Delaney; S. David Harris; Brennan T. Phillips; Oliver N. Shipley; James A. Sulikowski; Carlos M. Duarte; Jonatha Giddens (Frontiers in Marine Science, 2024)

Antimicrobial prophylaxis in companion animal surgery: A scoping review for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - T.M. Sørensen; K. Scahill; J. Espinel Ruperez; M. Olejnik; F. Swinbourne; D.R. Verwilghen; M.C. Nolff; S. Baines; C. Marques; A. Vilen; E.L. Duarte; M. Dias; et al. (The Veterinary Journal, 2024)

In vitro plantlet production of Ilex paraguariensis adult plants using BIT bioreactors - Claudia V. Luna; María J. Duarte; Elsa A. Brugnoli; Paula G. Ayala; Fabiana D. Espasandin; Aldo C. Bernardis; Luis A. Mroginski; Pedro A. Sansberro (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Diversity and distribution of coral gall crabs associated with Red Sea mesophotic corals - Silvia Vimercati; Tullia I. Terraneo; Fabio Marchese; Ameer A. Eweida; Mattie Rodrigue; Vincent Pieribone; Mohammed Qurban; Carlos M. Duarte; Francesca Benzoni (Frontiers in Marine Science, 2024)
Coral-dwelling gall crabs (Cryptochiridae) live in an obligate symbiosis with reef-building corals from shallow to deep waters. In particular, crabs of the genus Opecarcinus are known to occur across the tropical belt in association with the scleractinian family Agariciidae, down to a depth of 89 m. The Red Sea is a semi-enclosed basin that has long been recognized as a region of high marine biodiversity and endemism, with more than 230 decapod species recorded so far. There, nine Opecarcinus species are recorded from shallow and mesophotic corals. However, the occurrence of Opecarcinus below 30 m depth is documented only in the Saudi Arabian coast of the Northern Red Sea, and the rest of the Saudi Arabian Red Sea has remained unstudied. In this work, we assess the diversity and distribution of Opecarcinus from the mesophotic waters of the Saudi Arabian Red Sea. Through Remotely Operated Vehicles (ROV) and Submarines explorations, we collected 10 gall crab specimens associated with Agariciidae corals at mesophotic depths between 47 and 89 m. Two mitochondrial and one nuclear markers were used to obtain crab phylogenetic tree showing that three of the Opecarcinus species known from Red Sea shallow-water corals can also live at mesophotic depths. This is the first assessment of the depth distribution of the genus Opecarcinus in the Red Sea. It provides further evidence of the depth range adaptability of the Opecarcinus -Agariciidae association and highlights the need for a more in-depth investigation of the largely overlooked mesophotic coral-associated fauna.

Consistent Symbiodiniaceae community assemblage in a mesophotic-specialist coral along the Saudi Arabian Red Sea - Silvia Vimercati; Tullia I. Terraneo; Carolina Bocanegra Castano; Federica Barreca; Benjamin C. C. Hume; Fabio Marchese; Mustapha Ouhssain; Alexandra Steckbauer; Giovanni Chimienti; Ameer A. Eweida; Christian R. Voolstra; Mattie Rodrigue; et al. (Frontiers in Marine Science, 2024)
Introduction The Red Sea is a narrow rift basin characterized by latitudinal environmental gradients which shape the diversity and distribution of reef-dwelling organisms. Studies on Symbiodiniaceae associated with select hard coral taxa present species- specific assemblages and concordant variation patterns from the North to southeast Red Sea coast at depths shallower than 30 m. At mesophotic depths, however, algal diversity studies are rare. Here, we characterize for the first-time host-associated algal communities of a mesophotic specialist coral species, Leptoseris cf. striatus , along the Saudi Arabian Red Sea coast. Methods We sampled 56 coral colonies spanning the eastern Red Sea coastline from the Northern Red Sea to the Farasan Banks in the South, and across two sampling periods, Fall 2020 and Spring 2022. We used Next Generation Sequencing of the ITS2 marker region in conjunction with SymPortal to denote algal assemblages. Results and discussion Our results show a relatively stable coral species-specific interaction with algae from the genus Cladocopium along the examined latitudinal gradient, with the appearance, in a smaller proportion, of presumed thermally tolerant algal taxa in the genera Symbiodinium and Durusdinium during the warmer season (Fall 2020). Contrary to shallow water corals, our results do not show a change in Symbiodiniaceae community composition from North to South in this mesophotic specialist species. However, our study highlights for the first time that symbiont communities are subject to change over time at mesophotic depth, which could represent an important phenomenon to address in future studies.

Novel community data in ecology-properties and prospects - Florian Hartig; Nerea Abrego; Alex Bush; Jonathan M. Chase; Gurutzeta Guillera-Arroita; Mathew A. Leibold; Otso Ovaskainen; Loïc Pellissier; Maximilian Pichler; Giovanni Poggiato; Laura Pollock; Sara Si-Moussi; et al. (Trends in Ecology & Evolution, 2024)

High salinity suppresses nitrogen cycle genes and shifts nitrifier communities in the black mangrove rhizosphere - Ingrid Figueroa-Galvis; Orson Mestanza; Andrea Muñoz; Victor A. Ramos-Duarte; Javier Vanegas (Rhizosphere, 2024)

Estimation of ammonia deposition to forest ecosystems in Scotland and Sri Lanka using wind-controlled NH3 enhancement experiments - Ajinkya G. Deshpande; Matthew R. Jones; Netty van Dijk; Neil J. Mullinger; Duncan Harvey; Robert Nicoll; Galina Toteva; Gothamie Weerakoon; Sarath Nissanka; Buddhika Weerakoon; Maude Grenier; Agata Iwanicka; et al. (Atmospheric Environment, 2024)

Bioprospecting the potential of the microbial community associated to Antarctic marine sediments for hydrocarbon bioremediation - Layssa de Melo Carlos; Karine Fernandes Camacho; Alysson Wagner Duarte; Valéria M. de Oliveira; Marcela Boroski; Luiz Henrique Rosa; Rosemary Vieira; Arthur A. Neto; Júlia Ronzella Ottoni; Michel R. Z. Passarini (Brazilian Journal of Microbiology, 2024)

Water aging and the quality of organic carbon sources drive niche partitioning of the active bathypelagic prokaryotic microbiome - Marta Sebastián; Pablo Sánchez; Guillem Salazar; Xosé A. Álvarez‐Salgado; Isabel Reche; Xosé Anxelu G. Morán; Maria Montserrat Sala; Carlos M. Duarte; Silvia G. Acinas; Josep M. Gasol (Limnology and Oceanography, 2024)
Due to the scarcity of organic matter (OM) sources in the bathypelagic (1000–4000 m depth), prokaryotic metabolism is believed to be concentrated on particles originating from the surface. However, the structure of active bathypelagic prokaryotic communities and how it changes across environmental gradients remains unexplored. Using a combination of 16S rRNA gene and transcripts sequencing, metagenomics, and substrate uptake potential measurements, here we aimed to explore how water masses aging and the quality of OM influence the structure of the active microbiome, and the potential implications for community function. We found that the relative contribution of taxa with a free‐living lifestyle to the active microbiome increased in older water masses that were enriched in recalcitrant OM, suggesting that these prokaryotes may also play a substantial role in the bathypelagic metabolism of vast areas of the ocean. In comparison to particle‐associated prokaryotes, free‐living prokaryotes exhibited lower potential metabolic rates, and harbored a limited number of two‐component sensory systems, suggesting they have less ability to sense and respond to environmental cues. In contrast, particle‐associated prokaryotes carried genes for particle colonization and carbohydrate utilization that were absent in prokaryotes with a free‐living lifestyle. Consistently, we observed that prokaryotic communities inhabiting older waters displayed reduced abilities to colonize particles, and higher capabilities to use complex carbon sources, compared to communities in waters with a higher proportion of labile OM. Our results provide evidence of regionalization of the bathypelagic active prokaryotic microbiome, unveiling a niche partitioning based on the quality of OM.

Microplastics from agricultural mulch films: Biodegradation and ecotoxicity in freshwater systems - Diogo A. Ferreira-Filipe; Ana Paço; Bruna Pinho; Rafael Silva; Sara A.M. Silva; Fátima Jesus; Joana L. Pereira; Armando C. Duarte; Teresa A.P. Rocha-Santos; Ana L. Patrício-Silva (Science of The Total Environment, 2024)

Potential brewer’s spent grain as a carbon source alternative for biosurfactant production by Rhodotorula mucilaginosa (LBP4) - Mariana A. Azevedo; Maria dos R. Vieira-Neta; Letícia P. do Nascimento; Gabriela F. da Silva; João G.P. Vicente; Iolanda C.S. Duarte (Journal of Environmental Chemical Engineering, 2024)

Population genomics unveils the century-old invasion of the Seagrass Halophila stipulacea in the Mediterranean Sea - Catalina A. García-Escudero; Costas S. Tsigenopoulos; Tereza Manousaki; Alexandros Tsakogiannis; Núria Marbà; Salvatrice Vizzini; Carlos M. Duarte; Eugenia T. Apostolaki (Marine Biology, 2024)
The tropical seagrass Halophila stipulacea invaded the Eastern Mediterranean Sea in the late nineteenth century and progressively spread throughout the basin ever since. Its spread is expected to continue north-westward as the Mediterranean Sea becomes warmer, potentially changing the seagrass biogeography of the basin. Given the power of genomics to assess invasion dynamics in non-model species, we report the first ddRAD-seq study of H. stipulacea and small-scale population genomic analysis addressing its century-old Mediterranean invasion. Based on 868 SNPs and 35 genotyped native (Red Sea) and exotic (from Cyprus, Greece, and Italy) samples, results suggest that genetic structure was high, especially between major geographic discontinuities, and that exotic populations maintain comparably lower genetic diversity than native populations, despite 130 years of invasion. The evidence of high heterozygosity excess, coupled with previously reported male-dominated and rare flowering records in the exotic range, suggests that clonal propagation likely played a pivotal role in the successful colonization and spread of H. stipulacea in the Mediterranean. This shift in reproductive strategy, particularly evident in the Italian populations located closest to the western boundary and representing more recent establishments, underscores the importance of this cost-effective mode of reproduction, especially during the initial stages of invasion, raising questions about the species future expansion trajectory. Our findings serve as a catalyst for future research into the species’ invasion dynamics, including deciphering the intricate roles of acclimatization and rapid adaptation, important for a comprehensive assessment of invasion risks and improving management strategies aimed at conserving seagrass ecosystems.

Rapid diversification of grey mangroves ( Avicennia marina ) driven by geographic isolation and extreme environmental conditions in the Arabian Peninsula - Guillermo Friis; Edward G. Smith; Catherine E. Lovelock; Alejandra Ortega; Alyssa Marshell; Carlos M. Duarte; John A. Burt (Molecular Ecology, 2024)
Biological systems occurring in ecologically heterogeneous and spatially discontinuous habitats provide an ideal opportunity to investigate the relative roles of neutral and selective factors in driving lineage diversification. The grey mangroves ( Avicennia marina ) of Arabia occur at the northern edge of the species' range and are subject to variable, often extreme, environmental conditions, as well as historic large fluctuations in habitat availability and connectivity resulting from Quaternary glacial cycles. Here, we analyse fully sequenced genomes sampled from 19 locations across the Red Sea, the Arabian Sea and the Persian/Arabian Gulf (PAG) to reconstruct the evolutionary history of the species in the region and to identify adaptive mechanisms of lineage diversification. Population structure and phylogenetic analyses revealed marked genetic structure correlating with geographic distance and highly supported clades among and within the seas surrounding the Arabian Peninsula. Demographic modelling showed times of divergence consistent with recent periods of geographic isolation and low marine connectivity during glaciations, suggesting the presence of (cryptic) glacial refugia in the Red Sea and the PAG. Significant migration was detected within the Red Sea and the PAG, and across the Strait of Hormuz to the Arabian Sea, suggesting gene flow upon secondary contact among populations. Genetic‐environment association analyses revealed high levels of adaptive divergence and detected signs of multi‐loci local adaptation driven by temperature extremes and hypersalinity. These results support a process of rapid diversification resulting from the combined effects of historical factors and ecological selection and reveal mangrove peripheral environments as relevant drivers of lineage diversity.

Improvement of ferrioxalate assisted Fenton and photo-Fenton processes for paracetamol degradation by hydrogen peroxide dosage - Bárbara N. Giménez; Leandro O. Conte; Sofía A. Duarte; Agustina V. Schenone (Environmental Science and Pollution Research, 2024)

CowScreeningDB: A public benchmark database for lameness detection in dairy cows - Shahid Ismail; Moises Diaz; Cristina Carmona-Duarte; Jose Manuel Vilar; Miguel A. Ferrer (Computers and Electronics in Agriculture, 2024)

Cross-examining the influence of upwelling and seaweed quality on herbivores’ feeding behavior and growth - Felipe Sepúlveda; Pedro A. Quijón; Diego Quintanilla-Ahumada; Juan Vargas; Marcela Aldana; Melissa Fernández; Oscar Varas; Javier Zapata; José Pulgar; Cristian Duarte (Marine Environmental Research, 2024)

Effects of protected areas on soil nematode communities in forests of the North of Portugal - A. Carolina Duarte; Carlos A. Guerra; Concha Cano-Díaz; Romy Zeiss; Cláudia Carvalho-Santos; Rui P. Carvalho; Sofia R. Costa (Biodiversity and Conservation, 2024)
Nature conservation policy is mainly concerned with aboveground terrestrial species and soil biodiversity has been largely ignored, resulting in a lack of information about the conservation status of most soil organisms and about the effects that nature conservation policies have on soil systems. Forests in Northern Portugal are characterized by a remarkable diversity of ecosystems and provide habitat for an enormous diversity of living organisms. This study aims to investigate whether and to what extent protected areas and forest typology (native vs. exotic) affect soil nematode biodiversity and functions in forest ecosystems. We studied soil nematode communities, which have been widely used for their bioindicator value, to: (i) assess differences in soil biodiversity and functions between protected and non-protected areas, and between native and exotic forest types; and (ii) infer how protected areas deal with pressures and drivers of soil biodiversity and functions. We showed that current work done by nature conservation in Northern Portugal is producing some significant effects on the soil system, showing a larger Structure and Omnivore footprints and greater abundance of fungivorous and omnivorous nematodes in protected areas. Furthermore, native forest areas are better suited to ensure soil biodiversity and ecological functioning and should have a greater importance in nature conservation measures. Soil organic carbon, apparent density, soil moisture, and deciduous forest cover mainly influenced soil functional biodiversity with higher nematode trophic groups being positively associated with soil organic carbon and moisture and negatively associated with apparent density. Finally, conservation efforts targeted at the protection of native forests need to better consider effects on soil biodiversity and function, to provide an integrated protection of both aboveground and belowground components.

Correction to: Functional mobility and physical fitness are improved through a multicomponent training program in institutionalized older adults - Sergio López‑López; Vanesa Abuín‑Porras; Luis A. Berlanga; Michelle Matos‑Duarte; Luis Perea‑Unceta; Carlos Romero‑Morales; Helios Pareja‑Galeano (GeroScience, 2023)

Facemasks: An insight into their abundance in wetlands, degradation, and potential ecotoxicity - Ana Paço; Ana M. Oliveira; Diogo A. Ferreira-Filipe; Andreia C.M. Rodrigues; Rui J.M. Rocha; Amadeu M.V.M. Soares; Armando C. Duarte; Ana L. Patrício Silva; Teresa Rocha-Santos (Science of The Total Environment, 2023)

The spatio-temporal diversification of SRK alleles in an Arabidopsis polyploid hybrid and introgression zone - Christiane Kiefer; Paola Ruiz Duarte; Roswitha Schmickl; Marcus A. Koch (Perspectives in Plant Ecology, Evolution and Systematics, 2023)

A simple, low cost and fast sample preparation method for fluorine determination by ISE in leguminous seeds and oilseeds - Paola C. Crestani; Thiago C. Pereira; Eliana T.F. Larruscain; Conrado R. Laureano; Erico M.M. Flores; Fabio A. Duarte (Food Chemistry, 2023)

APGW/AKH Precursor from Rotifer Brachionus plicatilis and the DNA Loss Model Explain Evolutionary Trends of the Neuropeptide LWamide, APGWamide, RPCH, AKH, ACP, CRZ, and GnRH Families - Cristian E. Cadena-Caballero; Nestor Munive-Argüelles; Lina M. Vera-Cala; Carlos Barrios-Hernandez; Ruben O. Duarte-Bernal; Viviana L. Ayus-Ortiz; Luis A. Pardo-Díaz; Mayra Agudelo-Rodríguez; Lola X. Bautista-Rozo; Laura R. Jimenez-Gutierrez; Francisco Martinez-Perez (Journal of Molecular Evolution, 2023)
In the year 2002, DNA loss model (DNA-LM) postulated that neuropeptide genes to emerged through codons loss via the repair of damaged DNA from ancestral gene namely Neuropeptide Precursor Predictive ( NPP ), which organization correspond two or more neuropeptides precursors evolutive related. The DNA-LM was elaborated according to amino acids homology among LWamide, APGWamide, red pigment-concentrating hormone (RPCH), adipokinetic hormones (AKHs) and in silico APGW/RPCH NPP APGW/AKH NPP were proposed. With the above principle, it was proposed the evolution of corazonin (CRZ), gonadotropin-releasing hormone (GnRH), AKH, and AKH/CRZ (ACP), but any NPP never was considered. However, the evolutive relation via DNA-LM among these neuropeptides precursors not has been established yet. Therefore, the transcriptomes from crabs Callinectes toxotes and Callinectes arcuatus were used to characterized ACP and partial CRZ precursors, respectively. BLAST alignment with APGW/RPCH NPP and APGW/AKH NPP allow identified similar NPP in the rotifer Brachionus plicatilis and other invertebrates. Moreover, three bioinformatics algorithms and manual verification were used to purify 13,778 sequences, generating a database with 719 neuropeptide precursors. Phylogenetic trees with the DNA-LM parameters showed that some ACP, CRZ, AKH2 and two NPP share nodes with GnRH from vertebrates and some of this neuropeptide had nodes in invertebrates. Whereas the phylogenetic tree with standard parameters do not showed previous node pattern. Robinson-Foulds metric corroborates the differences among phylogenetic trees. Homology relationship showed four putative orthogroups; AKH4, CRZ, and protostomes GnRH had individual group. This is the first demonstration of NPP in species and would explain the evolution neuropeptide families by the DNA-LM.

Mapping socio-environmental pressures to assess Portuguese soil vulnerability - Concha Cano-Díaz; Romy Zeiss; Claudia Carvalho-Santos; Rui P. Carvalho; Sofia R. Costa; A. Carolina Duarte; Paulo Fernandes; Carlos A. Guerra (Applied Geography, 2023)

Hydrologic Evaluation of the Global Precipitation Measurement Mission over the U.S.: Error Budget Analysis - Devon Woods; Pierre-Emmanuel Kirstetter; Humberto Vergara; Jorge A. Duarte; Jeffrey Basara (Journal of Hydrology, 2023)

A common variant close to the “tripwire” linker region of NLRP1 contributes to severe COVID-19 - Vinicius N. C. Leal; Leandro M. Paulino; Raylane A. G. Cambui; Thiago G. Zupelli; Suemy M. Yamada; Leonardo A. T. Oliveira; Valéria de F. Dutra; Carolina B. Bub; Araci M. Sakashita; Ana Paula H. Yokoyama; José M. Kutner; Camila A. Vieira; et al. (Inflammation Research, 2023)

Fishery Closures, More Than Predator Release, Increased Persistence of Nearshore Fishes and Invertebrates to the Deepwater Horizon Oil Spill - Kiva L. Oken; Kenneth W. Able; Kim de Mutsert; F. Joel Fodrie; Paola C. López-Duarte; Charles W. Martin; Michael J. McCann; Jill A. Olin; Michael J. Polito; Brian J. Roberts; Olaf P. Jensen (Estuaries and Coasts, 2023)

Intraspecific color diversity and camouflage associated with ontogeny in an insular land crab - Marcio C. A. João; Rafael C. Duarte; Andrea S. Freire; Marcelo A. A. Pinheiro (Behavioral Ecology and Sociobiology, 2023)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

Subsistence swine farming: seroprevalence and risk factors associated with Lawsonia intracellularis infection in the state of Minas Gerais Brazil in 2016 - J. C. R. Barbosa; R. R. Nicolino; M. P. Gabardo; J. P. M. Gonçalves; M. E. Suarez-Duarte; R. P. Laub; A. G. S. Daniel; G. H. S. Mariano; C. M. Costa; P. A. Correia; M. D. Araújo; R. M. C. Guedes (Tropical Animal Health and Production, 2023)

Getting fat and stressed: Effects of dietary intake of titanium dioxide nanoparticles in the liver of turbot Scophthalmus maximus - Elza Fonseca; María Vázquez; Laura Rodriguez-Lorenzo; Natalia Mallo; Ivone Pinheiro; Maria Lígia Sousa; Santiago Cabaleiro; Monica Quarato; Miguel Spuch-Calvar; Miguel A. Correa-Duarte; Juan José López-Mayán; Mick Mackey; et al. (Journal of Hazardous Materials, 2023)

SEM-imaging-based mapping of monofractal and multifractal patterns of the Piper krukoffii Yunck leaf surface architecture - Glenda Quaresma Ramos; Ituany da Costa Melo; Robert S. Matos; Erveton P. Pinto; Marcelo A. Pires; Edgar Aparecido Sanches; Henrique Duarte da Fonseca Filho (Flora, 2023)

Gelatin-based films incorporated with buriti oil (Mauritia flexuosa L.) as active packaging for artisanal cheese conservation - Heriberto A. Anjos; Domingos A.M. Castro; Agenor G. dos Santos-Neto; Jefferson Romáryo Duarte da Luz; Maria das Graças Almeida; Maria Terezinha S. Leite Neta; Narendra Narain; Alessandra A.C. Pagani; Elton Franceschi; Maria Lucila Hernández-Macedo; Jorge A. López (Bioresource Technology Reports, 2023)

Nut yield and infestation of Anacampsis phytomiella Busck (Lepidoptera: Gelechiidae) in progeny of the dwarf cashew - Poliana M. Duarte; Gabriela P. S. Maciel; Wenner V. A. Saraiva; José W. S. Melo; Vitor H. M. Macedo; Dheyne S. Melo; Nívia S. Dias-Pini (Phytoparasitica, 2023)

Determination of Cl and S in crude oil by ICP-OES after sample digestion by microwave-induced combustion in disposable vessels - Jaime S. Mandlate; Alessandra S. Henn; Paola A. Mello; Erico M.M. Flores; Juliano S. Barin; Fabio A. Duarte (Analytica Chimica Acta, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Artificial Light at Night (ALAN) causes size-dependent effects on intertidal fish decision-making - José Pulgar; Patricio H. Manríquez; Stephen Widdicombe; Roberto García-Huidobro; Pedro A. Quijón; Mauricio Carter; Marcela Aldana; Diego Quintanilla-Ahumada; Cristian Duarte (Marine Pollution Bulletin, 2023)

Lessons from the invasion front: Integration of research and management of the lionfish invasion in Brazil - Marcelo O. Soares; Pedro H.C. Pereira; Caroline V. Feitosa; Rodrigo Maggioni; Rafael S. Rocha; Luis Ernesto Arruda Bezerra; Oscar S. Duarte; Sandra V. Paiva; Eurico Noleto-Filho; Maiara Queiroz M. Silva; Mayra Csapo-Thomaz; Tatiane M. Garcia; et al. (Journal of Environmental Management, 2023)

Linking landscape structure and ecosystem service flow - Julia C. Assis; Camila Hohlenwerger; Jean Paul Metzger; Jonathan R. Rhodes; Gabriela T. Duarte; Rafaela A. da Silva; Andrea Larissa Boesing; Paula R. Prist; Milton Cezar Ribeiro (Ecosystem Services, 2023)

Transcriptomic Analyses of Neurotoxic Astrocytes Derived from Adult Triple Transgenic Alzheimer’s Disease Mice - Diego Carvalho; Pablo Diaz-Amarilla; Rosina Dapueto; María Daniela Santi; Pablo Duarte; Eduardo Savio; Henry Engler; Juan A. Abin-Carriquiry; Florencia Arredondo (Journal of Molecular Neuroscience, 2023)

Intrinsic and specific groundwater vulnerability determination as a pre-operational baseline assessment of an unconventional hydrocarbon industry - G. F. C. Lima; V. G. Ferreira; J. S. D. Lima; J. C. M. Duarte; A. C. Dufilho; C. A. de Carvalho Filho (International Journal of Environmental Science and Technology, 2023)

Interactions between clay minerals, bacteria growth and urease activity on biocementation of soils - Rafaela Cardoso; Inês Borges; Joana Vieira; Sofia O.D. Duarte; Gabriel A. Monteiro (Applied Clay Science, 2023)

Functional mobility and physical fitness are improved through a multicomponent training program in institutionalized older adults - Sergio López-López; Vanesa Abuín-Porras; Luis A. Berlanga; Michelle Martos-Duarte; Luis Perea-Unceta; Carlos Romero-Morales; Helios Pareja-Galeano (GeroScience, 2023)
Physical exercise has demonstrated its effectiveness in the management of the deleterious process of aging. However, it is less studied in institutionalized elderly people. This investigation aims to clarify the benefits of a multicomponent training program in institutionalized older adults. A randomized controlled trial was conducted with institutionalized older adults (≥ 70 years old). Intervention group (IG; N = 18) were submitted to a multicomponent training program based on muscle power training and interval endurance exercise, 2 times/week for 12 weeks. Control group (CG; N = 16) continued their usual mobility exercises. Independence was estimated with the Barthel index, and physical fitness and functional mobility were evaluated by the Short Physical Performance Battery (SPPB), the Timed Up and Go (TUG) test, the 6-min Walking Test (6’WT), the 10-Meter Walking Test (10MWT), hand grip strength dynamometry, and lower limb muscle strength and power. The IG improved, compared with the CG, in TUG scores in -7.43 s (95% IC: 3.28, 11.59; p < 0.001); in 10MWT scores in -5.19 s (95% IC: 1.41, 8.97; p = 0.004) and -4.43 s (95% IC: 1.14, 7.73; p = 0.002), 6’WT scores in + 54.54 m (95% IC: 30.24, 78.84; p < 0.001); and SPPB in + 2.74 points (95% IC: 2.10, 3.37; p < 0.001). Maximum muscle power and maximum strength did not show statistically significant differences. The multicomponent training program based on muscle power and interval endurance exercise was shown to be safe, well tolerated and effective for the improvement of functional mobility and physical fitness, but not for independence in institutionalized older adults.

The influence of upwelling on key bivalves from the Humboldt and Iberian current systems - M. Roberto García-Huidobro; Marcela Aldana; Pablo Varela; Claudio García-Herrera; João N. Monteiro; Francisco Leitão; Maria Alexandra Teodósio; Pedro A. Quijón; Oscar Varas; Melissa Fernandéz; Cristian Duarte; José Pulgar (Marine Environmental Research, 2023)

Real-time monitoring of the starch cross-linking with citric acid by chemorheological analysis - Gustavo A. Duarte; Maria C. Bezerra; Sílvia H.P. Bettini; Alessandra A. Lucas (Carbohydrate Polymers, 2023)

Lifelong exercise training promotes the remodelling of the immune system and prostate signalome in a rat model of prostate carcinogenesis - Elisabete Nascimento-Gonçalves; Fernanda Seixas; Carlos Palmeira; Gabriela Martins; Carolina Fonseca; José Alberto Duarte; Ana I. Faustino-Rocha; Bruno Colaço; Maria João Pires; Maria João Neuparth; Daniel Moreira-Gonçalves; Margarida Fardilha; et al. (GeroScience, 2023)
This work aimed to understand how lifelong exercise training promotes the remodelling of the immune system and prostate signalome in a rat model of PCa. Fifty-five male Wistar rats were divided into four groups: control sedentary, control exercised, induced PCa sedentary and induced PCa exercised. Exercised animals were trained in a treadmill for 53 weeks. Pca induction consisted on the sequential administration of flutamide, N-methyl-N-nitrosourea and testosterone propionate implants. Serum concentrations of C-reactive protein (CRP) and tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) were not different among groups. Peripheral levels of γδ T cells were higher in Pca exercised group than in the PCa sedentary group ( p < 0.05). Exercise training also induced Oestrogen Receptor (ESR1) upregulation and Mitogen-activated Protein Kinase 13 (MAPK13) downregulation, changed the content of the phosphorylated (at Ser-104) form of this receptor (coded by the gene ESR1) and seemed to increase Erα phosphorylation and activity in exercised PCa rats when compared with sedentary PCa rats. Our data highlight the exercise-induced remodelling of peripheral lymphocyte subpopulations and lymphocyte infiltration in prostate tissue. Moreover, exercise training promotes the remodelling prostate signalome in this rat model of prostate carcinogenesis.

Renewed environmental governance scenarios in the Brazilian Amazon - Carlos A. Peres; Camila Duarte Ritter; João Campos-Silva (Trends in Ecology & Evolution, 2023)

Quantifying blue carbon stocks and the role of protected areas to conserve coastal wetlands - Micheli Duarte de Paula Costa; Maria Fernanda Adame; Catherine V. Bryant; Jack Hill; Jeffrey J. Kelleway; Catherine E. Lovelock; Anne Ola; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Nathan Waltham; Paul H. York; et al. (Science of The Total Environment, 2023)

Field experimental evidence of sandy beach community changes in response to artificial light at night (ALAN) - Cristian Duarte; Diego Quintanilla-Ahumada; Cristóbal Anguita; Eduardo A. Silva-Rodriguez; Patricio H. Manríquez; Stephen Widdicombe; José Pulgar; Cristian Miranda; Nicole Jahnsen-Guzmán; Pedro A. Quijón (Science of The Total Environment, 2023)

Digital microfluidic platform assembled into a home-made studio for sample preparation and colorimetric sensing of S-nitrosocysteine - Danielly S. Rocha; Richard P.S. de Campos; Habdias A. Silva-Neto; Gerson F. Duarte-Junior; Fethi Bedioui; Wendell K.T. Coltro (Analytica Chimica Acta, 2023)

Photoperiod and dietary treatment in freshwater modulate the short-term intestinal response to seawater in Atlantic salmon (Salmo salar) - Pasqualina Gaetano; Vilma Duarte; Anja Striberny; David Hazlerigg; Even H. Jørgensen; Marco A. Campinho; Juan Fuentes (Aquaculture, 2023)

Evaluating the in vitro digestion of lipids rich in medium-chain fatty acids (MCFAs) using dynamic and static protocols - Ericsem Pereira; Jean-Michel Fernandes; Raquel Gonçalves; Ana C. Pinheiro; M. Salomé Duarte; M. Madalena Alves; Antonio J.A. Meirelles; Guilherme J. Maximo; Antonio A. Vicente (Food Chemistry, 2023)

An evaluation of multistate occupancy models for estimating relative abundance and population trends - Valerie A. Steen; Adam Duarte; James T. Peterson (Ecological Modelling, 2023)

Cryopreservation of mature zygotic embryos, shoot bud regeneration, and field establishment of Pinus elliottii var. elliottii x Pinus caribaea var. hondurensis in vitro-derived plants - Lilian P. E. Ayala; Claudia V. Luna; Elsa A. Brugnoli; Fabiana D. Espasandin; María J. Duarte; Ana M. González; María E. Gauchat; Paloma Moncaleán Guillén; Pedro A. Sansberro (Trees, 2023)

Imperfect diet choice reduces the performance of a predatory mite - Felipe Lemos; Sabina Bajda; Marcus V. A. Duarte; Juan M. Alba; Thomas Van Leeuwen; Angelo Pallini; Maurice W. Sabelis; Arne Janssen (Oecologia, 2023)
Two mutually unexclusive hypotheses prevail in the theory of nutritional ecology: the balanced diet hypothesis states that consumers feed on different food items because they have complementary nutrient and energy compositions. The toxin-dilution hypothesis poses that consumers feed on different food items to dilute the toxins present in each. Both predict that consumers should not feed on low-quality food when ample high-quality food forming a complete diet is present. We investigated the diet choice of Phytoseiulus persimilis , a predatory mite of web-producing spider mites. It can develop and reproduce on single prey species, for example the spider mite Tetranychus urticae . A closely related prey, T. evansi , is of notorious bad quality for P. persimilis and other predator species. We show that juvenile predators feeding on this prey have low survival and do not develop into adults. Adults stop reproducing and have increased mortality when feeding on it. Feeding on a mixed diet of the two prey decreases predator performance, but short-term effects of feeding on the low-quality prey can be partially reversed by subsequently feeding on the high-quality prey. Yet, predators consume low-quality prey in the presence of high-quality prey, which is in disagreement with both hypotheses. We suggest that it is perhaps not the instantaneous reproduction on single prey or mixtures of prey that matters for the fitness of predators, but that it is the overall reproduction by a female and her offspring on an ephemeral prey patch, which may be increased by including inferior prey in their diet.

Sandy beach wrack as a resource: nutrient quality explains amphipod preferences but not temporal variation - Diego Quintanilla-Ahumada; K. Devon Lynn; Cristian Duarte; Pedro A. Quijón (Marine Biology, 2023)

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Interactions between invaders: facilitation of boring bivalves leads to reduced adhesive strength of sun corals - Damián Mizrahi; Rafael C. Duarte; Marcelo V. Kitahara; Augusto A. V. Flores (Coral Reefs, 2023)

Amazon raw clay as a precursor of a clay-based adsorbent: experimental study and DFT analysis for the adsorption of Basic Yellow 2 dye - Emanuele D. V. Duarte; Wedja T. Vieira; Rodrigo O. Góes; Luiz E. C. de Azevedo; Melissa G. A. Vieira; Meuris G. C. da Silva; Samira M. L. de Carvalho (Environmental Science and Pollution Research, 2023)

Modulation of intestinal growth and differentiation by photoperiod and dietary treatment during smoltification in Atlantic salmon (Salmo salar, L.) - Vilma Duarte; Pasqualina Gaetano; Anja Striberny; David Hazlerigg; Even H. Jørgensen; Juan Fuentes; Marco A. Campinho (Aquaculture, 2023)

Remote sensing for cost-effective blue carbon accounting - Martino E. Malerba; Micheli Duarte de Paula Costa; Daniel A. Friess; Lukas Schuster; Mary A. Young; David Lagomasino; Oscar Serrano; Sharyn M. Hickey; Paul H. York; Michael Rasheed; Jonathan S. Lefcheck; Ben Radford; et al. (Earth-Science Reviews, 2023)

Probing cellulose–solvent interactions with self-diffusion NMR: Onium hydroxide concentration and co-solvent effects - B. Medronho; A. Pereira; H. Duarte; L. Gentile; A.M. Rosa da Costa; A. Romano; U. Olsson (Carbohydrate Polymers, 2023)

Reducing natural vegetation loss in Amazonia critically depends on the formal recognition of indigenous lands - Daniela Prioli Duarte; Carlos A. Peres; Edgar Fernando Cifuentes Perdomo; Alejandro Guizar-Coutiño; Bruce Walker Nelson (Biological Conservation, 2023)

Behavior of the adsorption of Allura Red dye by chitosan beads and nanoparticles - Sánchez-Duarte Reyna G.; Villegas-Peralta Yedidia; Martínez-Macias María del Rosario; López-Cervantes Jaime; Sánchez-Machado Dalia I.; Correa-Murrieta Ma. A. (Nanotechnology for Environmental Engineering, 2023)

Saponite-inspired Materials as Remediation Technologies for Water Treatment: an Overview - Dihêgo Henrique L. Damacena; Pollyana Trigueiro; Victor Hugo Monteiro; Luzia Maria C. Honorio; Thiago Marinho Duarte; Robson Cunha; Marcelo B. Furtini; Maria Gardennia Fonseca; Edson C da Silva-Filho; Josy A. Osajima (Environmental Processes, 2023)

Human health risk assessment of metals and arsenic via consumption of commercial bivalves in the Gulf of California, Mexico - Nefertiti Taydé Roldán-Wong; Bertha Patricia Ceballos-Vázquez; Josué Alonso Yee-Duarte; Marian Alejandra Camacho-Mondragón; Karen A. Kidd; Evgueni Shumilin; Marcial Arellano-Martínez (Environmental Science and Pollution Research, 2023)

Novel infrastructure for coral gardening and reefscaping - Sebastian Schmidt-Roach; Rebecca Klaus; Abdulaziz M. Al-Suwailem; Alejandro R. Prieto; Julian Charrière; Charlotte A. E. Hauser; Carlos M. Duarte; Manuel Aranda (Frontiers in Marine Science, 2023)
Since 1950, coral abundance has declined worldwide by an estimated 60%, and further dramatic declines are predicted. Although global reductions in carbon emissions are essential to prevent further loss, coral reef restoration has become imperative to maintain the ecosystem services that coral reefs provide to humans at local scales. Yet, currently coral restoration and gardening efforts are too expensive to scale up due to the labor-intensive nature of the methods and low success rates. Here, we present a suite of technologies that improve coral reef restoration and rehabilitation’s scalability, efficiency, and effectiveness. Our modular technologies are designed to streamline in and ex situ nursery workflows, reduce maintenance times, solve problems in transporting corals to outplanting sites, and enable rapid outplanting on natural and artificial substrates. These novel structures can act as coral seeding hubs, which placed strategically, can have the capacity to enhance coral reproduction and replenish degraded nearby reefs with larvae. They can be applied to coral restoration and reefscaping, complemented by unique eco-friendly, low-carbon-emission structures for the creation of architecturally and visually appealing habitats and underwater landscapes. Our technologies integrate novel monitoring approaches that support intelligent solutions to track genotypes, optimize and control stock management, apply assisted evolution approaches, and adaptive management through long-term monitoring.

Environmental policy at a critical junction in the Brazilian Amazon - Carlos A. Peres; João Campos-Silva; Camila Duarte Ritter (Trends in Ecology & Evolution, 2023)

Quantification of SARS-CoV-2 in wastewater samples from hospitals treating COVID-19 patients during the first wave of the pandemic in Brazil - Juliana Calábria de Araújo; Camila L. Madeira; Thiago Bressani; Cíntia Leal; Deborah Leroy; Elayne C. Machado; Luyara A. Fernandes; Maria Fernanda Espinosa; Gabriel Tadeu O. Freitas; Thiago Leão; Vera Tainá Mota; Alyne Duarte Pereira; et al. (Science of The Total Environment, 2023)

Revealing coastal upwelling impact on the muscle growth of an intertidal fish - Rodrigo Zuloaga; Oscar Varas; Camila Ahrendt; Victor M. Pulgar; Juan A. Valdés; Alfredo Molina; Cristian Duarte; Ángel Urzúa; Fabián Guzmán-Rivas; Marcela Aldana; José Pulgar (Science of The Total Environment, 2023)

Petrogenesis of the Córrego das Campinas Gabbro-Anorthosite Suite: Characterization of a Neoproterozoic massif-type anorthosite in the Goiás Magmatic Arc and its significance in the evolution of the Brasília belt, Brazil - Fernando Santos Diener; Reinhardt A. Fuck; Nilson Francisquini Botelho; Hugo José De Oliveira Polo; Márcio Martins Pimentel; Tiago Bandeira Duarte; Gabriel Veloso Martineli; José Affonso Brod (Journal of South American Earth Sciences, 2023)

Hydrologic evaluation of the global precipitation measurement mission over the U.S.: Flood peak discharge and duration - Devon Woods; Pierre-Emmanuel Kirstetter; Humberto Vergara; Jorge A. Duarte; Jeffrey Basara (Journal of Hydrology, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Colletotrichum karsti causing anthracnose on Dioscorea cayennensis in Brazil - Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Willie Anderson dos Santos Vieira; Ailton Reis; Lisa A. Castlebury; Marcos P. S. Câmara (Journal of Plant Pathology, 2023)

Neuroactive pharmaceuticals in estuaries: Occurrence and tissue-specific bioaccumulation in multiple fish species - Irina A. Duarte; Patrick Reis-Santos; Jerker Fick; Henrique N. Cabral; Bernardo Duarte; Vanessa F. Fonseca (Environmental Pollution, 2023)

Subduction invasion polarity switch from the Pacific to the Atlantic Ocean: A new geodynamic model of subduction initiation based on the Scotia Sea region - W.P. Schellart; V. Strak; A. Beniest; J.C. Duarte; F.M. Rosas (Earth-Science Reviews, 2023)

New sustainable and robust catalytic supports for palladium nanoparticles generated from chitosan/cellulose film and corn stem biochar - Camila P. Grandini; Cristiane R. Schmitt; Fábio A. Duarte; Diego S. Rosa; Clarissa H. Rosa; Gilber R. Rosa (Environmental Science and Pollution Research, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Speciation process on Brazilian continental islands, with the description of a new insular lancehead of the genus Bothrops (Serpentes, Viperidae) - Fausto E. Barbo; William W. Booker; Marcelo R. Duarte; Betina Chaluppe; José A. Portes-Junior; Francisco L. Franco; Felipe G. Grazziotin (Systematics and Biodiversity, 2022)

Fine mapping and candidate gene analysis of a dravet syndrome modifier locus on mouse chromosome 11 - Jennifer A. Kearney; Letonia D. Copeland-Hardin; Samantha Duarte; Nicole A. Zachwieja; Isaiah K. Eckart-Frank; Nicole A. Hawkins (Mammalian Genome, 2022)
Pathogenic variants in SCN1A result in a spectrum of phenotypes ranging from mild febrile seizures to Dravet syndrome, a severe infant-onset epileptic encephalopathy. Individuals with Dravet syndrome have developmental delays, elevated risk for sudden unexpected death in epilepsy (SUDEP), and have multiple seizure types that are often refractory to treatment. Although most Dravet syndrome variants arise de novo, there are cases where an SCN1A variant was inherited from mildly affected parents, as well as some individuals with de novo loss-of-function or truncation mutations that presented with milder phenotypes. This suggests that disease severity is influenced by other factors that modify expressivity of the primary mutation, which likely includes genetic modifiers. Consistent with this, the Scn1a +/− mouse model of Dravet syndrome exhibits strain-dependent variable phenotype severity. Scn1a +/− mice on the 129S6/SvEvTac (129) strain have no overt phenotype and a normal lifespan, while [C57BL/6Jx129]F1. Scn1a +/− mice have severe epilepsy with high rates of premature death. Low resolution genetic mapping identified several Dravet syndrome modifier ( Dsm ) loci responsible for the strain-dependent difference in survival of Scn1a +/− mice. To confirm the Dsm5 locus and refine its position, we generated interval-specific congenic strains carrying 129-derived chromosome 11 alleles on the C57BL/6J strain and localized Dsm5 to a 5.9 Mb minimal region. We then performed candidate gene analysis in the modifier region. Consideration of brain-expressed genes with expression or coding sequence differences between strains along with gene function suggested numerous strong candidates, including several protein coding genes and two miRNAs that may regulate Scn1a transcript.

Stochastic bioeconomic analysis of intensive African Catfish cultivation with three sources of uncertainty - Babatunde Olaseni Musa; Alvaro Hernández-Flores; Oludare Akanni Adeogun; José A. Duarte; Raúl Villanueva-Poot (Aquaculture International, 2022)

A Methodology for Shipping Noise Field Calibration and Excess Noise Estimation: The Azores Case Study - Sérgio M. Jesus; Cristiano Soares; Miriam Romagosa; Irma Cascão; Ricardo Duarte; Friedrich Zabel; Mónica A. Silva (Journal of Marine Science and Engineering, 2022)
Economic globalization and the continuous search for food, energy and raw materials led to an estimated 3 dB/decade increase of ocean noise intensity. Determining the level of anthropogenic noise, the so-called excess noise, and building identifiable meaningful indicators for supporting marine management policies currently requires extensive observation data and computer modeling. For modeling purposes, in this study, anthropogenic noise was reduced to shipping traffic drawn from Automatic Identification System data, and environmental sound was attributed to surface wind only. Data-model comparison allowed introducing a methodology for simple model calibration and estimate excess noise. This methodology was tested on acoustic recordings performed in June 2018 at three locations to the southwest of Faial-Pico Islands in the Azores archipelago. The results show that field-calibrated excess noise sound maps are in line with the shipping distribution in the area, revealing a number of potentially marine life-threatening hotspots. Excess noise addresses the need for a quantifiable measure of ocean noise only and therefore offers a basis for building suitable continuous anthropogenic noise pollution indicators.

Parametric Analysis of the Efficacy of Lysimeter Designs Using Numerical Modelling - O. Ouédraogo; M. Duarte; T. Kahale; T. Abichou; A. R. Cabral (Geotechnical and Geological Engineering, 2022)

Global beta diversity patterns of microbial communities in the surface and deep ocean - Ernesto Villarino; James R. Watson; Guillem Chust; A. John Woodill; Benjamin Klempay; Bror Jonsson; Josep M. Gasol; Ramiro Logares; Ramon Massana; Caterina R. Giner; Guillem Salazar; X. Anton Alvarez‐Salgado; et al. (Global Ecology and Biogeography, 2022)
Aim Dispersal and environmental gradients shape marine microbial communities, yet the relative importance of these factors across taxa with distinct sizes and dispersal capacity in different ocean layers is unknown. Here, we report a comparative analysis of surface and deep ocean microbial beta diversity and examine how these patterns are tied to oceanic distance and environmental gradients. Location Tropical and subtropical oceans (30°N–40°S). Time period 2010–2011. Major taxa studied Prokaryotes and picoeukaryotes (eukaryotes between 0.2 and 3 μm). Methods Beta diversity was calculated from metabarcoding data on prokaryotic and picoeukaryotic microbes collected during the Malaspina expedition across the tropical and subtropical oceans. Mantel correlations were used to determine the relative contribution of environment and oceanic distance driving community beta diversity. Results Mean community similarity across all sites for prokaryotes was 38.9% in the surface and 51.4% in the deep ocean, compared to mean similarity of 25.8 and 12.1% in the surface and deep ocean, respectively, for picoeukaryotes. Higher dispersal rates and smaller body sizes of prokaryotes relative to picoeukaryotes likely contributed to the significantly higher community similarity for prokaryotes compared with picoeukaryotes. The ecological mechanisms determining the biogeography of microbes varied across depth. In the surface ocean, the environmental differences in space were a more important factor driving microbial distribution compared with the oceanic distance, defined as the shortest path between two sites avoiding land. In the deep ocean, picoeukaryote communities were slightly more structured by the oceanic distance, while prokaryotes were shaped by the combined action of oceanic distance and environmental filtering. Main conclusions Horizontal gradients in microbial community assembly differed across ocean depths, as did mechanisms shaping them. In the deep ocean, the oceanic distance and environment played significant roles driving microbial spatial distribution, while in the surface the influence of the environment was stronger than oceanic distance.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Transcriptome Analysis of Immune Response against Streptococcus agalactiae Infection in the Nile Tilapia GIFT Strain - Tao Zhou; Zhihua Fang; Daniel F. C. Duarte; Stefan A. Fernandes; Ying Lu; Jing Guo; Lang Gui; Liangbiao Chen (Fishes, 2022)
Streptococcus agalactiae (group B streptococcus, GBS), a broad-spectrum pathogen, causes great economic losses in fish aquaculture, especially the industry of tilapia. Until now, the knowledge of the immune response mechanism against S. agalactiae infection in tilapia has been limited. In the present study, the gill transcriptome of the tilapia from the GBS and the phosphate buffered saline (PBS) groups were sequenced. The transcriptomic analysis results presented the differentially expressed genes (DEGs) at different time points (DEGs number, 6 h: 2122, 9 h: 1851, 15 h: 1791, and 18 h: 2395) after GBS injection, and significantly enriched immune-related gene ontology (GO) terms such as the innate immune response. The significantly enriched immune pathways included the Toll-like receptor signaling pathway, the nucleotide oligomerization domain (NOD)-like receptor signaling pathway, the cytosolic-DNA sensing pathway, and the intestinal immune network for Immunoglobulin A (IgA) production. Most of the DEGs in Toll-like receptor signaling, NOD-like receptor signaling, and cytosolic-DNA sensing pathways presented upregulations at 18 h, which indicated that the innate immune pathways were activated. Two immune-related pathways (phagosome and cell adhesion molecules) were significantly enriched at all time points, suggesting that these two pathways might also play important roles in the immune response against the GBS infection. The results of HE staining showed that the gills of tilapia were damaged seriously at 9 h post-infection, which might be due to the possibility of pyroptosis resulting from the changes of DEGs in the NOD-like receptor signaling pathway. This study provided new insight into the mechanisms of gill damage in fish infected with S. agalactiae.

Acidification and high-temperature impacts on energetics and shell production of the edible clam Ameghinomya antiqua - Sebastián I. Martel; Carolina Fernández; Nelson A. Lagos; Fabio A. Labra; Cristián Duarte; Juan F. Vivanco; Claudio García-Herrera; Marco A. Lardies (Frontiers in Marine Science, 2022)
Warming and ocean acidification are currently critical global change drivers for marine ecosystems due to their complex and irreversible effects on the ecology and evolution of marine communities. Changes in the chemistry and the temperature of the ocean impact the biological performance of marine resources by affecting their energy budget and thus imposing energetic restrictions and trade-offs on their survival, growth, and reproduction. In this study, we evaluated the interplaying effects of increased p CO 2 levels and temperature on the economically relevant clam Ameghinomya antiqua , an infaunal bivalve inhabiting a wide distributional range along the coast of Chile. Juvenile clams collected from southern Chile were exposed to a 90-day experimental set-up emulating the current and a future scenario projeced to the end of the current century for both high p CO 2 /low-pH and temperature (10 and 15°C) projected for the Chilean coast. Clams showed physiological plasticity to different projected environmental scenarios without mortality. In addition, our results showed that the specimens under low-pH conditions were not able to meet the energetic requirements when increased temperature imposed high maintenance costs, consequently showing metabolic depression. Indeed, although the calcification rate was negative in the high- p CO 2 scenario, it was the temperature that determined the amount of shell loss. These results indicate that the studied clam can face environmental changes for short-term periods modifying energetic allocation on maintenance and growth processes, but with possible long-term population costs, endangering the sustainability of an important benthic artisanal fisheries resource.

Are artificial semi-dry wetlands efficient in wastewater treatment from different fish densities and for lettuce production? - J. de Farias Lima; A. M. Bastos; S. S. Duarte; U. R. A. dos Santos (International Journal of Environmental Science and Technology, 2022)

Influence of temperature on the toxicity of the elutriate from a pesticide contaminated soil to two cladoceran species - Livia Pitombeira de Figueirêdo; Danillo B. Athayde; Thandy Junio da Silva Pinto; Michiel A. Daam; Glauce da Silva Guerra; Paulo José Duarte-Neto; Evaldo L. G. Espíndola (Ecotoxicology, 2022)

Lionfish on the loose: Pterois invade shallow habitats in the tropical southwestern Atlantic - Marcelo O. Soares; Caroline V. Feitosa; Tatiane M. Garcia; Kelly Ferreira Cottens; Bruno Vinicius; Sandra Vieira Paiva; Oscar de Sousa Duarte; Lívio Moreira Gurjão; Grasielle Dayse de Vasconcelos Silva; Rafaela Camargo Maia; Diego M. Previatto; Pedro B. M. Carneiro; et al. (Frontiers in Marine Science, 2022)
Lionfish ( Pterois spp.) evolved in the Indo-Pacific with predators and prey and invaded regions (e.g., the Caribbean Sea and Mediterranean) where no such balance yet exists. In 2020, four lionfish were recorded on mesophotic reefs of the Amazon offshore Coast and Fernando de Noronha Archipelago. However, until now, there were no records of invasive lionfish in Brazilian nearshore waters or even such a high number of individuals. In this article, we report the continuing invasion process along the Brazilian Province by multiple sightings (72) of lionfish from March to May 2022 in estuaries, seagrass beds, and artificial and natural reefs across 240 km of the Brazilian coast. These are the first records of lionfish in coastal northeast Brazil and the shallowest records (1–16 m) from South Atlantic tropical waters. The largest simultaneous records of lionfish in breakwaters, fishing weirs, and marambaias (artificial reefs used as fishing grounds) on the Brazilian Northeastern coast indicate that these man-made structures are suitable habitats for this species. Most of the lionfish (58%) were recorded in artificial reefs and fishing weirs. Moreover, the detection of invasions in marginal reefs, estuaries, and two marine protected areas characterized by moderately turbid water and high sedimentation rates highlights the adaptability of the lionfish, making it extremely difficult for divers and fishers to capture them. We call for an urgent management plan considering that the invaded tropical region hosts a high level of endemism, and rare and/or cryptic taxa, which increases the risk of impacts since these are primary lionfish prey.

Different faces of cigarette butts, the most abundant beach litter worldwide - Maria Christina B. Araújo; Monica F. Costa; Jacqueline S. Silva-Cavalcanti; Armando C. Duarte; Vanessa Reis; Teresa A. Rocha-Santos; João Pinto da Costa; Violeta Girão (Environmental Science and Pollution Research, 2022)

Global estimates of the extent and production of macroalgal forests - Carlos M. Duarte; Jean‐Pierre Gattuso; Kasper Hancke; Hege Gundersen; Karen Filbee‐Dexter; Morten F. Pedersen; Jack J. Middelburg; Michael T. Burrows; Kira A. Krumhansl; Thomas Wernberg; Pippa Moore; Albert Pessarrodona; et al. (Global Ecology and Biogeography, 2022)
Aim Macroalgal habitats are believed to be the most extensive and productive of all coastal vegetated ecosystems. In stark contrast to the growing attention on their contribution to carbon export and sequestration, understanding of their global extent and production is limited and these have remained poorly assessed for decades. Here we report a first data‐driven assessment of the global extent and production of macroalgal habitats based on modelled and observed distributions and net primary production (NPP) across habitat types. Location Global coastal ocean. Time period Contemporary. Major taxa studied Macroalgae. Methods Here we apply a comprehensive niche model to generate an improved global map of potential macroalgal distribution, constrained by incident light on the seafloor and substrate type. We compiled areal net primary production (NPP) rates across macroalgal habitats from the literature and combined this with our estimates of the global extent of these habitats to calculate global macroalgal NPP. Results We show that macroalgal forests are a major biome with a global area of 6.06–7.22 million km 2 , dominated by red algae, and NPP of 1.32 Pg C/year, dominated by brown algae. Main conclusions The global macroalgal biome is comparable, in area and NPP, to the Amazon forest, but is globally distributed as a thin strip around shorelines. Macroalgae are expanding in polar, subpolar and tropical areas, where their potential extent is also largest, likely increasing the overall contribution of algal forests to global carbon sequestration.

Editorial: Emerging Topics in Coastal and Transitional Ecosystems: Science, Literacy, and Innovation - Bernardo Duarte; Célia M. Teixeira; Irene Martins; Aschwin H. Engelen; Raquel L. Costa; Janine Barbara Adams; Maria João Bebianno; Ricardo A. Melo; Vanessa F. Fonseca (Frontiers in Marine Science, 2022)

Expression of Human Immunodeficiency Virus Transactivator of Transcription (HIV-Tat1-86) Protein Alters Nociceptive Processing that is Sensitive to Anti-Oxidant and Anti-Inflammatory Interventions - Thomas J. Cirino; Amy R. Alleyne; Vinicius Duarte; Ariana Figueroa; Chloe A. Simons; Emet M. Anceaume; Justin Kendrick; Olivia Wallman; Shainnel O. Eans; Heather M. Stacy; Jessica M. Medina; Jay P. McLaughlin (Journal of Neuroimmune Pharmacology, 2022)

Feeding and trophic ecology of Antarctic toothfish Dissostichus mawsoni in the Amundsen and Dumont D’Urville Seas (Antarctica) - José P. Queirós; Darren W. Stevens; Matthew H. Pinkerton; Rui Rosa; Bernardo Duarte; Alexandra Baeta; Jaime A. Ramos; José C. Xavier (Hydrobiologia, 2022)

A neuromuscular perspective of sarcopenia pathogenesis: deciphering the signaling pathways involved - Alexandra Moreira-Pais; Rita Ferreira; Paula A. Oliveira; José A. Duarte (GeroScience, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

REE Anomalies Changes in Bottom Sediments Applied in the Western Equatorial Atlantic Since the Last Interglacial - Thiago A. Sousa; Igor Martins Venancio; Eduardo Duarte Marques; Thiago S. Figueiredo; Rodrigo Azevedo Nascimento; Joseph M. Smoak; Ana Luiza S. Albuquerque; Claudio Morisson Valeriano; Emmanoel Vieira Silva-Filho (Frontiers in Marine Science, 2022)
We reconstruct paleoredox conditions in the Western Equatorial Atlantic (WEA) over the glacial-interglacial cycle (~130 ka) by using new high-resolution REEs data and their anomalies from a marine sediment core (GL-1248) collected from the equatorial margin off the continental shelf of NE Brazil. This approach aims to improve the understanding of the dynamics of paleoclimatic and sedimentary inputs on the coast of northeastern Brazil. Marine sediments were analyzed via Mass Spectrometry (ICP-MS) after total digestion with HF/HNO 3 . REEs proxies are a useful tool in understanding the transport and origin of sediments due to their physicochemical properties. Our data showed the Parnaíba River was the main source of REEs content in the western South Atlantic. Fe minerals (Fe-oxyhydroxides) produced via weathering of continental and tropical soils were the principal REE-carrier phase during transportation and ultimate deposition at core site GL-1248. Several regional climatic factors mainly rainfall changes contributed significantly to continental-REEs erosion of sedimentary layers of the Parnaíba Basin, and transport and deposition of the mobilized REEs from the continent to the study site. Furthermore, changes in the negative Ce-anomaly showed low variation along the core indicating a reduction in deep ocean oxygenation during the interglacial relative to the last glacial period. That variation, probably, was associated with glacial-interglacial variations in sea level with the exposure of the continental shelf. The origin of positive Eu anomalies in siliciclastic sediment, also observed in the core, was explained by preferential retention by feldspars such as plagioclases and potassium feldspars mostly from the assimilation of felspar during fractionation crystallization of felsic magma in the Parnaíba basin since the Last Interglacial.

Learning From the Study Fleet: Maintenance of a Large-Scale Reference Fleet for Northeast U.S. Fisheries - Andrew W. Jones; Katie A. Burchard; Anna M. Mercer; John J. Hoey; Michael D. Morin; Giovanni L. Gianesin; Jacob A. Wilson; Calvin R. Alexander; Brooke A. Lowman; Debra G. Duarte; David Goethel; James Ford; et al. (Frontiers in Marine Science, 2022)
Logbook data from commercial fisheries are a vital component in the machinery of management, including tracking the volume of catches and allocating catch spatially. At the same time, logbooks can provide a unique window into the ecological and sociological conditions in marine fisheries, where fishermen interact with marine species and environments frequently and broadly. Traditional logbooks, however, often are not sufficiently standardized (when personal logs), or lack the detail (when regulatory documents) required to adequately understand fisheries ecosystems. The Study Fleet program, operated by the Northeast Fisheries Science Center’s Cooperative Research Branch, was developed to address these shortfalls by engaging members of the fishing industry in collecting high-resolution catch, effort, and environmental data using electronic logbooks. Since its inception, the Study Fleet has expanded from a small project focused on collecting detailed catch information from the New England multispecies groundfish fishery to a program with a wider scope encompassing a variety of fisheries, gears, and environmental parameters from North Carolina to Maine U.S. Over the years, a number of lessons have been learned about recruiting and supporting industry partners, managing the data, evolving technical specifications, and the challenges associated with analyzing and applying self-reported fisheries data. Here we describe the current state of the program and provide summaries of the Study Fleet program operations and outcomes from 2007-2020, with an eye towards successes, challenges, and applicability of the approach in other regions. We suggest other reference fleet programs, as well as other developing fishery dependent data collections (e.g., electronic monitoring programs), develop detailed roadmaps for each data collection to keep participants engaged as collaborators, target specific fisheries to keep resources from being stretched too thin, and partner with data users early. Additionally, we suggest programs invest in the long-term participation of individual fishermen, carefully weigh the pros and cons of involvement in regulatory reporting, and plan data products and applications well in advance to ensure that the sampling scheme and granularity of the data meet the needs of stock assessment, ecosystem, and oceanographic scientists.

Artificial light at night (ALAN) causes variable dose-responses in a sandy beach isopod - Diego Quintanilla-Ahumada; Pedro A. Quijón; Patricio H. Manríquez; José Pulgar; Manuel R. García-Huidobro; Cristian Miranda; Alfredo Molina; Rodrigo Zuloaga; Cristian Duarte (Environmental Science and Pollution Research, 2022)

Decontamination of real urban sewage—comparison between Fenton and electrochemical oxidation - Jenivaldo L. de Araújo; Jaceguai S. da Silva; Fábio A. S. Santos; Cenira M. de Carvalho; José Leandro S. Duarte; Josealdo Tonholo; Carmem L. P. S. Zanta (Environmental Science and Pollution Research, 2022)

Attraction of whitefly Aleurodicus cocois mediated by cashew volatiles - Wenner V. A. Saraiva; Nívia S. Dias-Pini; Elenilson G. Alves Filho; José W. S. Melo; Marilene Fancelli; Cristiane R. Coutinho; Guilherme J. Zocolo; Tigressa H. S. Rodrigues; Poliana M. Duarte; Vitor H. M. Macedo; Elaine S. S. Goiana (Phytoparasitica, 2022)

Exposure to leucine induces oxidative stress in the brain of zebrafish - Bianca Z. de Medeiros; Leticia B. Wessler; Mariane B. Duarte; Isabela S. Lemos; Gabriela Candiotto; Rafael O. Canarim; Paulo C. L. dos Santos; Carolina A. Torres; Giselli Scaini; Eduardo P. Rico; Jaqueline S. Generoso; Emilio L. Streck (Metabolic Brain Disease, 2022)

Global proteomic analysis of the follicular fluid from brown brocket deer (Mazama gouazoubira; Fisher, 1814) - Thais T. S. Souza; Maurício F. van Tilburg; Maria J. B. Bezerra; Luciana D. Rola; Leda M. C. Pereira; José M. B. Duarte; Maiana S. Chaves; Luciana M. Melo; Arlindo A. A. N. Moura; Vicente J. F. Freitas (European Journal of Wildlife Research, 2022)

Global biodiversity patterns of marine forests of brown macroalgae - Eliza Fragkopoulou; Ester A. Serrão; Olivier De Clerck; Mark J. Costello; Miguel B. Araújo; Carlos M. Duarte; Dorte Krause‐Jensen; Jorge Assis (Global Ecology and Biogeography, 2022)
Aim Marine forests of brown macroalgae create essential habitats for coastal species and support invaluable ecological services. Here, we provide the first global analysis of species richness and endemicity of both the kelp and fucoid biomes. Location Global. Time period Contemporary. Major taxa studied Marine forests of brown macroalgae, formed by kelp (here defined as orders Laminariales, Tilopteridales and Desmarestiales) and fucoid (order Fucales), inhabiting subtidal and intertidal environments. Methods We coupled a large dataset of macroalgal observations (420 species, 1.01 million records) with a high‐resolution dataset of relevant environmental predictors (i.e., light, temperature, salinity, nitrate, wave energy and ice coverage) to develop stacked species distribution models (stacked SDMs) and yield estimates of global species richness and endemicity. Results Temperature and light were the main predictors shaping the distribution of subtidal species, whereas wave energy, temperature and salinity were the main predictors of intertidal species. The highest regional species richness for kelp was found in the north‐east Pacific (maximum 32 species) and for fucoids in south‐east Australia (maximum 53 species), supporting the hypothesis that these regions were the evolutionary sources of global colonization by brown macroalgae. Locations with low species richness coincided between kelp and fucoid, occurring mainly at higher latitudes (e.g., Siberia) and the Baltic Sea, where extensive ice coverage and low‐salinity regimes prevail. Regions of high endemism for both groups were identified in the Galapagos Islands, Antarctica, South Africa and East Russia. Main conclusions We estimated the main environmental drivers and limits shaping the distribution of marine forests of brown macroalgae and mapped biogeographical centres of species richness and endemicity, which largely coincided with the expectation from previous evolutionary hypotheses. The mapped biodiversity patterns can serve as new baselines for planning and prioritizing locations for conservation, management and climate change mitigation strategies, flagging threatened marine forest regions under different climate change scenarios.

Trade-offs between succulent and non-succulent epiphytes underlie variation in drought tolerance and avoidance - S. G. Gotsch; C. B. Williams; R. Bicaba; R. Cruz-de Hoyos; A. Darby; K. Davidson; M. Dix; V. Duarte; A. Glunk; L. Green; B. Ferguson; K. Muñoz-Elizondo; et al. (Oecologia, 2022)

Identification of potential new mosquito-associated viruses of adult Aedes aegypti mosquitoes from Tocantins state, Brazil - Matheus A. Duarte; Fabrício S. Campos; Osvaldo F. Araújo Neto; Leonardo A. Silva; Arthur B. Silva; Thalita C. Aguiar; Raissa N. Santos; Ueric J. B. Souza; Giselly B. Alves; Fernando L. Melo; Daniel M. P. Ardisson-Araujo; Raimundo W. S. Aguiar; et al. (Brazilian Journal of Microbiology, 2022)

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Major Expansion of Marine Forests in a Warmer Arctic - Jorge Assis; Ester A. Serrão; Carlos M. Duarte; Eliza Fragkopoulou; Dorte Krause-Jensen (Frontiers in Marine Science, 2022)
Accelerating warming and associated loss of sea ice are expected to promote the expansion of coastal marine forests (macrophytes) along the massive Arctic coastlines. Yet, this region has received much less attention compared to other global oceans. The available future projections of Arctic macrophytes are still limited to few species and regions, and mostly focused at lower latitude ranges, thus precluding well-informed IPCC impact assessments, conservation and management. Here we aim to quantify potential distributional changes of Arctic intertidal and subtidal brown macroalgae and eelgrass by the year 2100, relative to present. We estimate habitat suitability by means of species distribution modeling, considering changes in seawater temperature, salinity, nutrients and sea ice cover under two greenhouse gas emission scenarios, one consistent with the Paris Agreement (RCP 2.6) and the other representing limited mitigation strategies (RCP 8.5). As data on substrate conditions do not exist, the models were restricted to the depth range supporting Arctic macrophytes (down to 5 m for eelgrass and 30 m for brown macroalgae). Models projected major expansions of Arctic macrophytes between 69,940 and 123,360 km 2 , depending on the climate scenario, with polar distribution limits shifting northwards by up to 1.5 latitude degrees at 21.81 km per decade. Such expansions in response to changing climate will likely elicit major changes in biodiversity and ecosystem functions in the future Arctic. Expansions are, however, less intense than those already realized over the past century, indicating an overall slowing down despite accelerated warming as habitats become increasingly occupied.

Patterns and predictors of condition indices in a critically endangered fish - Bruce G. Hammock; Rosemary Hartman; Randy A. Dahlgren; Catherine Johnston; Tomofumi Kurobe; Peggy W. Lehman; Levi S. Lewis; Erwin Van Nieuwenhuyse; Wilson F. Ramírez-Duarte; Andrew A. Schultz; Swee J. Teh (Hydrobiologia, 2022)

The Variscan basement in the western shoulder of the Lusitanian Basin (West Iberian Margin): insights from detrital-zircon geochronology of Jurassic strata - Pedro A. Dinis; Pieter Vermeesch; Luís V. Duarte; Pedro Proença Cunha; Marta Barbarano; Eduardo Garzanti (Journal of Iberian Geology, 2021)

A methanol extract and N,N-dimethyltryptamine from Psychotria viridis Ruiz & Pav. inhibit Zika virus infection in vitro - Thaís F. S. Moraes; Ariane C. Ferraz; Waleska S. da Cruz Nizer; Antônio H. Tótola; Débora B. S. Soares; Lucienir P. Duarte; Sidney A. Vieira-Filho; Cintia L. B. Magalhães; José C. de Magalhães (Archives of Virology, 2021)

Warming Threatens to Propel the Expansion of the Exotic Seagrass Halophila stipulacea - Marlene Wesselmann; Rosa M. Chefaoui; Núria Marbà; Ester A. Serrao; Carlos M. Duarte (Frontiers in Marine Science, 2021)
The spread of exotic species to new areas can be magnified when favored by future climatic conditions. Forecasting future ranges using species distribution models (SDMs) could be improved by considering physiological thresholds, because models solely based on occurrence data cannot account for plasticity due to acclimation of individuals to local conditions over their life-time or to adaptation due to selection within local populations. This is particularly relevant for the exotic seagrass Halophila stipulacea , which colonized the Mediterranean Sea a century ago and shifted its thermal niche, coping with a colder regime. Here, we used two hybrid models combining correlative SDMs with the thermal limits for growth of native and exotic H. stipulacea populations to predict the distribution of the species in its native (Indian Ocean and Red Sea) and exotic ranges (Mediterranean Sea and Caribbean Sea) under two scenarios forecasting limited (RCP 2.6) and severe (RCP 8.5) future climate changes by 2050 and 2100. Then, we assessed the differences between hybrid models based on native Red Sea thermal limits (niche conservatism: 17–36°C) and on exotic Mediterranean thermal limits (local adaptation: 14–36°C). At the Mediterranean exotic range, the local adaptation hybrid model accurately agreed with the present distribution of the species while the niche conservatism-based hybrid model failed to predict 87% of the current occurrences of the species. By contrast, both hybrid models predicted similar species distributions for the native range and exotic Caribbean range at present and projected that H. stipulacea will maintain its current worldwide under all future greenhouse gas emission scenarios. The hybrid model based on Mediterranean thermal limits projected the expansion of H. stipulacea through the western Mediterranean basin (except the gulf of Leon) under the most severe scenario (RCP 8.5) by 2100, increasing its distribution by 50% in the Mediterranean. The future expansion of H. stipulacea is related to its capacity to cope with warm waters and it may become a relevant species in the future, particularly under the projected decline of native Mediterranean seagrasses, resulting in important shifts in seagrass communities and overall ecosystem functions.

Characterization of hydrological features and plankton during neap tides in a subtropical lagoon south of the California Current - René Funes-Rodríguez; Rafael Cervantes-Duarte; María del Carmen Jiménez-Quiroz; Sergio Hernández-Trujillo; Rogelio González-Armas; Sofia A. Barón-Campis; Eduardo Anaya-Godinez; Francisco Barrón-Barraza (Marine Biology Research, 2021)

Biodiversity Assessment and Geographical Affinities of Discards in Clam Fisheries in the Atlantic–Mediterranean Transition (Northern Alboran Sea) - J. Urra; P. Marina; A. Rojas García; E. León Duarte; H. Gallardo-Roldán; B. Orue Montaner; M. Lozano; J. M. Serna; A. Garrido; A. J. Ibáñez Yuste; A. Terrón-Sigler; J. Baro; et al. (Thalassas: An International Journal of Marine Sciences, 2021)

Gabra2 is a genetic modifier of Dravet syndrome in mice - Nicole A. Hawkins; Toshihiro Nomura; Samantha Duarte; Levi Barse; Robert W. Williams; Gregg E. Homanics; Megan K. Mulligan; Anis Contractor; Jennifer A. Kearney (Mammalian Genome, 2021)
Pathogenic variants in epilepsy genes result in a spectrum of clinical severity. One source of phenotypic heterogeneity is modifier genes that affect expressivity of a primary pathogenic variant. Mouse epilepsy models also display varying degrees of clinical severity on different genetic backgrounds. Mice with heterozygous deletion of Scn1a ( Scn1a +/− ) model Dravet syndrome, a severe epilepsy most often caused by SCN1A haploinsufficiency. Scn1a +/− mice recapitulate features of Dravet syndrome, including spontaneous seizures, sudden death, and cognitive/behavioral deficits. Scn1a +/− mice maintained on the 129S6/SvEvTac (129) strain have normal lifespan and no spontaneous seizures. In contrast, admixture with C57BL/6J (B6) results in epilepsy and premature lethality. We previously mapped Dravet Survival Modifier loci ( Dsm1-Dsm5 ) responsible for strain-dependent differences in survival. Gabra2 , encoding the GABA A α2 subunit, was nominated as a candidate modifier at Dsm1 . Direct measurement of GABA A receptors found lower abundance of α2-containing receptors in hippocampal synapses of B6 mice relative to 129. We also identified a B6-specific single nucleotide deletion within Gabra2 that lowers mRNA and protein by nearly 50%. Repair of this deletion reestablished normal levels of Gabra2 expression . In this study, we used B6 mice with a repaired Gabra2 allele to evaluate Gabra2 as a genetic modifier of severity in Scn1a +/− mice. Gabra2 repair restored transcript and protein expression, increased abundance of α2-containing GABA A receptors in hippocampal synapses, and rescued epilepsy phenotypes of Scn1a +/− mice. These findings validate Gabra2 as a genetic modifier of Dravet syndrome, and support enhancing function of α 2 -containing GABA A receptors as treatment strategy for Dravet syndrome.

Sarcopenia versus cancer cachexia: the muscle wasting continuum in healthy and diseased aging - Alexandra Moreira-Pais; Rita Ferreira; Paula A. Oliveira; José A. Duarte (Biogerontology, 2021)

Plant growth–promoting traits of yeasts isolated from the tank bromeliad Vriesea minarum L.B. Smith and the effectiveness of Carlosrosaea vrieseae for promoting bromeliad growth - Andréa R. Marques; Alessandra A. Resende; Fátima C. O. Gomes; Ana Raquel O. Santos; Carlos A. Rosa; Alexandre A. Duarte; José Pires de Lemos-Filho; Vera Lúcia dos Santos (Brazilian Journal of Microbiology, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Quantitative determination of pentacyclic triterpenic acids in Amazonian species Eugenia punicifolia DC by ATR-FTIR - Raphael P. Albuquerque; Glauce C. A. Duarte; Nelise Duarte; Débora T. Ohana; Wilson C. Santos; Thelma B. Machado (Natural Product Research, 2021)

First Application of 360-Degree Camera Technology to Marine Predator Bio-Logging - Austin J. Gallagher; Nourah A. Alsudairy; Brendan D. Shea; Nicholas L. Payne; Carlos M. Duarte (Frontiers in Marine Science, 2021)
Animal-borne video camera systems have long-been used to capture the fine-scale behaviors and unknown aspects of the biology of marine animals. However, their utility to serve as robust scientific tools in the greater bio-logging research community has not been fully realized. Here we provide, for the first time, an application of 360-degree camera technology to a marine organism, using a large tiger shark as a proof-of-concept case study. Leveraging the three-dimensional nature of the imaging technology, we derived 224 seafloor habitat assessments over the course of the nearly 1-h track, whereby the shark was able to survey ∼23,000 square meters of seafloor; over three-times greater than the capacity of non 360-degree cameras. The resulting data provided detailed information on habitat use, diving behavior, and swimming speed, as well seafloor mapping. Our results suggest that 360-degree cameras provide complimentary benefits—and in some cases superior efficiency—than unidirectional video packages, with an enhanced capacity to map seafloor.

Hyperbaric storage at room like temperatures as a possible alternative to refrigeration: evolution and recent advances - Mauro D. Santos; Liliana G. Fidalgo; Carlos A. Pinto; Ricardo V. Duarte; Álvaro T. Lemos; Ivonne Delgadillo; Jorge A. Saraiva (Critical Reviews in Food Science and Nutrition, 2021)

Numerical Prediction of the Boundary-Layer Flow Over the Bolund Hill: Assessment of Turbulence Models and Advection Schemes - A. M. G. Lopes; N. G. L. Duarte; O. H. Sánchez; R. Daus; H. Koch (Boundary-Layer Meteorology, 2021)

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Micheli Duarte de Paula Costa; Catherine E. Lovelock; Nathan J. Waltham; Mary Young; Maria F. Adame; Catherine V. Bryant; Don Butler; David Green; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Paul H. York; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

Acarbose presents in vitro and in vivo antileishmanial activity against Leishmania infantum and is a promising therapeutic candidate against visceral leishmaniasis - Rafaella R. Costa; João A. Oliveira-da-Silva; Thiago A. R. Reis; Grasiele S. V. Tavares; Débora V. C. Mendonça; Camila S. Freitas; Daniela P. Lage; Vívian T. Martins; Luciana M. R. Antinarelli; Amanda S. Machado; Raquel S. Bandeira; Fernanda Ludolf; et al. (Medical Microbiology and Immunology, 2021)

In vitro and in silico studies of 8(17),12E,14-labdatrien-18-oic acid in airways smooth muscle relaxation: new molecular insights about its mechanism of action - Edilson B. Alencar Filho; Luciano A. A. Ribeiro; Thiego G. C. Carvalho; Fabrício S. Silva; Luiz Antonio M. S. Duarte-Filho; Euzébio G. Barbosa; Pedro M. N. Menezes; Josean F. Tavares; Marcelo S. da Silva; Bagnólia A. Silva (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Exposure to pH 3.5 water has no effect on the gills of the Amazonian tambaqui (Colossoma macropomum) - R. J. Gonzalez; M. L. Patrick; R. M. Duarte; A. Casciato; J. Thackeray; N. Day; A. L. Val (Journal of Comparative Physiology B, 2021)

Global projections of the soil microbiome in the Anthropocene - Carlos A. Guerra; Manuel Delgado‐Baquerizo; Eliana Duarte; Orlando Marigliano; Christiane Görgen; Fernando T. Maestre; Nico Eisenhauer (Global Ecology and Biogeography, 2021)
Aim Soil microbes are essential for maintenance of life‐supporting ecosystem services, but projections of how these microbes will be affected by global change scenarios are lacking. Therefore, our aim was to provide projections of future soil microbial distribution using several scenarios of global change. Location Global. Time period 1950–2090. Major taxa studied Bacteria and fungi. Methods We used a global database of soil microbial communities across six continents to estimate past and future trends of the soil microbiome. To do so, we used structural equation models to include the direct and indirect effects of changes in climate and land use in our predictions, using current climate (temperature and precipitation) and land‐use projections between 1950 and 2090. Results Local bacterial richness will increase in all scenarios of change in climate and land use considered, although this increase will be followed by a generalized community homogenization process affecting > 85% of terrestrial ecosystems. Changes in the relative abundance of functional genes associated with the increases in bacterial richness are also expected. Based on an ecological cluster analysis, our results suggest that phylotypes such as Geodermatophilus spp. (typical desert bacteria), Mycobacterium sp. (which are known to include important human pathogens), Streptomyces mirabilis (major producers of antibiotic resistance genes) or potential fungal soil‐borne plant pathogens belonging to Ascomycota fungi ( Venturia spp., Devriesia spp.) will become more abundant in their communities. Main conclusions Our results provide evidence that climate change has a stronger influence on soil microbial communities than change in land use (often including deforestation and agricultural expansion), although most of the effects of climate are indirect, through other environmental variables (e.g., changes in soil pH). The same was found for microbial functions such as the prevalence of phosphate transport genes. We provide reliable predictions about the changes in the global distribution of microbial communities, showing an increase in alpha diversity and a homogenization of soil microbial communities in the Anthropocene.

The Choroid Plexus Is an Alternative Source of Prolactin to the Rat Brain - Ana R. Costa-Brito; Telma Quintela; Isabel Gonçalves; Ana C. Duarte; Ana R. Costa; Fernando A. Arosa; José E. Cavaco; Manuel C. Lemos; Cecília R. A. Santos (Molecular Neurobiology, 2021)

Whole body vibration influence on bus fare collectors evaluated by using a brain training mobile app - S. G. Firmino; M. L. M. Duarte; J. A. B. Neves; P. A. X. Viana; F. S. B. de Araújo (International Archives of Occupational and Environmental Health, 2021)

Water and socioeconomic dependencies: a multiregional model - Miguel A. Almazán-Gómez; Rosa Duarte; Raquel Langarita; Julio Sánchez-Chóliz (Clean Technologies and Environmental Policy, 2021)

Cadaverine and Spermine Elicit Ca2+ Uptake in Human CP Cells via a Trace Amine-Associated Receptor 1 Dependent Pathway - D. Almeida-Santos; A. C. Duarte; I. Gonçalves; Catarina L. Ferreira; I. Ferrer; Hiroshi Ishikawa; Christian Schwerk; Horst Schroten; Cecília R. A. Santos (Journal of Molecular Neuroscience, 2021)

Impact of a tarsonemid prey mite and its fungal diet on the reproductive performance of a predatory mite - Dominiek Vangansbeke; Marcus V. A. Duarte; Jonas Merckx; Alfredo Benavente; Wojciech L. Magowski; Soraya C. França; Karel Bolckmans; Felix L. Wäckers (Experimental and Applied Acarology, 2021)

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Phylogeographic Analysis Suggests a Recent Population Bottleneck in the Rare Red Sea Tridacna squamosina - Kah Kheng Lim; Susann Rossbach; Nathan R. Geraldi; Ester A. Serrão; Carlos M. Duarte (Frontiers in Marine Science, 2021)
Giant clams are an important ecological component of coral reefs in the Red Sea, as they enhance the reef’s productivity and provide habitat that can increase diversity. Three species of giant clams, namely Tridacna maxima , T. squamosa , and T. squamosina have been described within the Red Sea. However, due to its scarcity, information about the distribution and ecology of T. squamosina in the Saudi Arabian Red Sea is still lacking. This study used DNA barcoding to confirm the identity of the rare T. squamosina in the Farasan Banks. Six mtCOI fragments (500 bp) of T. squamosina were successfully amplified using the SQUA-primers for the first time. We used our data along with 18 reference sequences (16S) from the online database to assess the genetic diversity and population structure of T. squamosina . Low genetic diversity among the T. squamosina populations inferred from the 16S sequences implies a recent bottleneck for this species, which is supported by their historically higher diversity based on the coalescent-based estimator. Given the small population abundance and limited genetic variation of T. squamosina , it may warrant immediate local protections such as biobanking and fertility preservation programs as well as effective integrated coastal zone management plans.

Administration of branched-chain amino acids alters epigenetic regulatory enzymes in an animal model of Maple Syrup Urine Disease - Emilio L. Streck; Felipe P. Bussular; Leticia B. Wessler; Mariane B. Duarte; Victoria L. Rezende; Matheus S. Rodrigues; Carolina A. Torres; Isabela S. Lemos; Gabriela Candiotto; Fernanda F. Gava; Jade de Oliveira; Samira S. Valvassori (Metabolic Brain Disease, 2021)

Reduced cutaneous inflammation associated with antioxidant action after topical application of the aqueous extract of Annona muricata leaves - Luana M. Cercato; Jéssica M. D. Araújo; Alan S. Oliveira; Allan J. O. Melo; Bruno S. Lima; Edmilson W. P. dos Santos; Agenor G. dos S. Neto; Ricardo L. C. de Albuquerque-Júnior; Marcelo C. Duarte; Adriano A. S. Araujo; Ana Mara O. Silva; Renata Grespan; et al. (Inflammopharmacology, 2021)

Diversity of tomato-infecting begomoviruses and spatiotemporal dynamics of an endemic viral species of the Brazilian Atlantic rain forest biome - Macária F. Duarte; Maria E. N. Fonseca; Hélcio Costa; Niday A. N. Fernandes; Ailton Reis; Leonardo S. Boiteux; Rita C. Pereira-Carvalho (Virus Genes, 2021)

Release-Recapture Test of Dispersal and Survival of Sterile Males of Ceratitis capitata (Diptera: Tephritidae) - F Duarte; M V Calvo; S Delgado; A Bartolucci; A Asfennato; A Borges; I Scatoni; F M García (Neotropical Entomology, 2020)

Insights on Zika virus envelope gene conservation in American outbreaks - Mateus V. Thomazella; Quirino A. Lima Neto; Francisco F. Duarte Junior; Fernando A. Jorge; Déborah de Castro Moreira; Amauri D. Leal Junior; Mayra M. Presibella; Irina N. Riediger; Rafael A. da Silva; Isabel Maria V. G. de Carvalho; Dennis A. Bertolini (Brazilian Journal of Microbiology, 2020)

Insect chemical ecology: chemically mediated interactions and novel applications in agriculture - Crispus M. Mbaluto; Pascal M. Ayelo; Alexandra G. Duffy; Anna L. Erdei; Anaїs K. Tallon; Siyang Xia; Gabriela Caballero-Vidal; Urban Spitaler; Magdolna O. Szelényi; Gonçalo A. Duarte; William B. Walker; Paul G. Becher (Arthropod-Plant Interactions, 2020)
Insect chemical ecology (ICE) evolved as a discipline concerned with plant–insect interactions, and also with a strong focus on intraspecific pheromone-mediated communication. Progress in this field has rendered a more complete picture of how insects exploit chemical information in their surroundings in order to survive and navigate their world successfully. Simultaneously, this progress has prompted new research questions about the evolution of insect chemosensation and related ecological adaptations, molecular mechanisms that mediate commonly observed behaviors, and the consequences of chemically mediated interactions in different ecosystems. Themed meetings, workshops, and summer schools are ideal platforms for discussing scientific advancements as well as identifying gaps and challenges within the discipline. From the 11th to the 22nd of June 2018, the 11th annual PhD course in ICE was held at the Swedish University of Agricultural Sciences (SLU) Alnarp, Sweden. The course was made up of 35 student participants from 22 nationalities (Fig. 1a) as well as 32 lecturers. Lectures and laboratory demonstrations were supported by literature seminars, and four broad research areas were covered: (1) multitrophic interactions and plant defenses, (2) chemical communication focusing on odor sensing, processing, and behavior, (3) disease vectors, and (4) applied aspects of basic ICE research in agriculture. This particular article contains a summary and brief synthesis of these main emergent themes and discussions from the ICE 2018 course. In addition, we also provide suggestions on teaching the next generation of ICE scientists, especially during unprecedented global situations.

Mitoxantrone impairs proteasome activity and prompts early energetic and proteomic changes in HL-1 cardiomyocytes at clinically relevant concentrations - Vera Marisa Costa; João Paulo Capela; Joana R. Sousa; Rute P. Eleutério; Patrícia R. S. Rodrigues; José Luís Dores-Sousa; Rui A. Carvalho; Maria Lourdes Bastos; José Alberto Duarte; Fernando Remião; M. Gabriela Almeida; Kurt J. Varner; et al. (Archives of Toxicology, 2020)

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Assessing VIIRS capabilities to improve burned area mapping over the Brazilian Cerrado - Filippe L.M. Santos; Renata Libonati; Leonardo F. Peres; Allan A. Pereira; Luiza C. Narcizo; Julia A. Rodrigues; Duarte Oom; José M. C. Pereira; Wilfrid Schroeder; Alberto W. Setzer (International Journal of Remote Sensing, 2020)

Milk yield and composition and body weight of offsprings of mixed-breed goats on semi-arid rangelands with different rainfall - M. J. Flores-Najera; L. I. Vélez-Monroy; J. I. Sánchez-Duarte; V. Cuevas-Reyes; M. Mellado; C. A. Rosales-Nieto (Tropical Animal Health and Production, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Small Giant Clam, Tridacna maxima Exhibits Minimal Population Genetic Structure in the Red Sea and Genetic Differentiation From the Gulf of Aden - Kah Kheng Lim; Susann Rossbach; Nathan R. Geraldi; Sebastian Schmidt-Roach; Ester A. Serrão; Carlos M. Duarte (Frontiers in Marine Science, 2020)

Interfacial Stress and Container Failure During Freezing of Bulk Protein Solutions Can Be Prevented by Local Heating - Andreia Duarte; Pedro Rego; Aida Ferreira; Paulo Dias; Vítor Geraldes; Miguel A. Rodrigues (AAPS PharmSciTech, 2020)

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Geotourism and Territorial Development: a Systematic Literature Review and Research Agenda - António Duarte; Vitor Braga; Carla Marques; Artur A. Sá (Geoheritage, 2020)

Seagrass losses since mid‐20th century fuelled CO 2 emissions from soil carbon stocks - Cristian Salinas; Carlos M. Duarte; Paul S. Lavery; Pere Masque; Ariane Arias‐Ortiz; Javier X. Leon; David Callaghan; Gary A. Kendrick; Oscar Serrano (Global Change Biology, 2020)
Seagrass meadows store globally significant organic carbon (C org ) stocks which, if disturbed, can lead to CO 2 emissions, contributing to climate change. Eutrophication and thermal stress continue to be a major cause of seagrass decline worldwide, but the associated CO 2 emissions remain poorly understood. This study presents comprehensive estimates of seagrass soil C org erosion following eutrophication‐driven seagrass loss in Cockburn Sound (23 km 2 between 1960s and 1990s) and identifies the main drivers. We estimate that shallow seagrass meadows ( org stocks in 50 cm thick soils (4.5 ± 0.7 kg C org /m 2 ) than previously vegetated counterparts (0.5 ± 0.1 kg C org /m 2 ). In deeper areas (>5 m), however, soil C org stocks in seagrass and bare but previously vegetated areas were not significantly different (2.6 ± 0.3 and 3.0 ± 0.6 kg C org /m 2 , respectively). The soil C org sequestration capacity prevailed in shallow and deep vegetated areas (55 ± 11 and 21 ± 7 g C org m −2 year −1 , respectively), but was lost in bare areas. We identified that seagrass canopy loss alone does not necessarily drive changes in soil C org but, when combined with high hydrodynamic energy, significant erosion occurred. Our estimates point at ~0.20 m/s as the critical shear velocity threshold causing soil C org erosion. We estimate, from field studies and satellite imagery, that soil C org erosion (within the top 50 cm) following seagrass loss likely resulted in cumulative emissions of 0.06–0.14 Tg CO 2‐eq over the last 40 years in Cockburn Sound. We estimated that indirect impacts (i.e. eutrophication, thermal stress and light stress) causing the loss of ~161,150 ha of seagrasses in Australia, likely resulted in the release of 11–21 Tg CO 2 ‐eq since the 1950s, increasing cumulative CO 2 emissions from land‐use change in Australia by 1.1%–2.3% per annum. The patterns described serve as a baseline to estimate potential CO 2 emissions following disturbance of seagrass meadows.

Beyond Reef Restoration: Next-Generation Techniques for Coral Gardening, Landscaping, and Outreach - Sebastian Schmidt-Roach; Carlos M. Duarte; Charlotte A. E. Hauser; Manuel Aranda (Frontiers in Marine Science, 2020)

Nicorandil Affects Mitochondrial Respiratory Chain Function by Increasing Complex III Activity and ROS Production in Skeletal Muscle Mitochondria - E. Sánchez-Duarte; C. Cortés-Rojo; L. A. Sánchez-Briones; J. Campos-García; A. Saavedra-Molina; I. Delgado-Enciso; U. A. López-Lemus; R. Montoya-Pérez (The Journal of Membrane Biology, 2020)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Caffeine removal using Elaeis guineensis activated carbon: adsorption and RSM studies - Larissa L. A. Melo; Alessandra H. Ide; José Leandro S. Duarte; Carmem Lucia P. S. Zanta; Leonardo M. T. M. Oliveira; Wagner R. O. Pimentel; Lucas Meili (Environmental Science and Pollution Research, 2020)

The big picture of field hydrology studies in Brazil - Davi C. D. Melo; Jamil A. A. Anache; Cristiano das N. Almeida; Jaqueline V. Coutinho; Geraldo M. Ramos Filho; Lívia M. P. Rosalem; Natália S. Pelinson; Guilherme L. R. A. Ferreira; Dimaghi Schwamback; Kalyl G. Calixto; João P. G. Siqueira; Jean C. Duarte-Carvajalino; et al. (Hydrological Sciences Journal, 2020)

Toxicities of acetogenin-based bioacaricides against two-spotted spider mite and selectivity to its phytoseiid predators - J. Miotto; A. F. Duarte; D. Bernardi; L. P. Ribeiro; F. Andreazza; U. S. Cunha (Experimental and Applied Acarology, 2020)

Determination of trace elements in Sergio mirim: an evaluation of sample preparation methods and detection techniques - Jaime S. Mandlate; Bruno M. Soares; Carlos F. F. Andrade; Leonir A. Colling; Ednei G. Primel; Marcia F. Mesko; Fabio A. Duarte (Environmental Science and Pollution Research, 2020)

Failure to complete treatment for latent tuberculosis infection in Portugal, 2013–2017: geographic-, sociodemographic-, and medical-associated factors - Alexis Sentís; Paula Vasconcelos; Rita Sá Machado; Joan A. Caylà; Mònica Guxens; Vasco Peixoto; Raquel Duarte; Isabel Carvalho; Carlos Carvalho (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Reconciling Tourism Development and Conservation Outcomes Through Marine Spatial Planning for a Saudi Giga-Project in the Red Sea (The Red Sea Project, Vision 2030) - Vasiliki I. Chalastani; Panos Manetos; Abdulaziz M. Al-Suwailem; Jason A. Hale; Abhishekh P. Vijayan; John Pagano; Ian Williamson; Scott D. Henshaw; Raed Albaseet; Faisal Butt; Russell E. Brainard; Harry Coccossis; et al. (Frontiers in Marine Science, 2020)

Heat Waves Are a Major Threat to Turbid Coral Reefs in Brazil - Gustavo A. S. Duarte; Helena D. M. Villela; Matheus Deocleciano; Denise Silva; Adam Barno; Pedro M. Cardoso; Caren L. S. Vilela; Phillipe Rosado; Camila S. M. A. Messias; Maria Alejandra Chacon; Erika P. Santoro; Daniele B. Olmedo; et al. (Frontiers in Marine Science, 2020)

Imines and lactones derived from friedelanes and their cytotoxic activity - Mariana G. Aguilar; Grasiely F. Sousa; Fernanda C. G. Evangelista; Adriano P. Sabino; Sidney A. Vieira Filho; Lucienir P. Duarte (Natural Product Research, 2020)

Estimates of environmental loading from copper alloy materials - Patrick J. Earley; Brandon L. Swope; Marienne A. Colvin; Gunther Rosen; Pei-Fang Wang; Jessica Carilli; Ignacio Rivera-Duarte (Biofouling, 2020)

Haplotype-specific single-locus multiplex PCR assay for identification of Pacific and Atlantic white shrimps, exotic Litopenaeus vannamei and native Litopenaeus schmitti, along the coast of Brazil - A. Vilasboa; A. S. Alencar; A. V. B. Duarte; C. Tavares; J. Gusmão (Conservation Genetics Resources, 2020)

Diet of the European badgers (Meles meles) in urban and rural areas of Norway - Duarte J. Gomes; Izabela A. Wierzbowska; Kjetil Bevanger; Declan T. O’Mahony; Kaja Rola (European Journal of Wildlife Research, 2020)

Evaluation of the cytotoxicity on breast cancer cell of extracts and compounds isolated from Hyptis pectinata (L.) poit - Fernanda R. Santana; Liany Luna-Dulcey; Víctor U. Antunes; Claudio F. Tormena; Marcia R. Cominetti; Marcelo C. Duarte; James A. da Silva (Natural Product Research, 2020)

Correction to: Soil microbes that may accompany climate warming increase alpine plant production - Joshua S. Lynn; Danielle A. Duarte; Jennifer A. Rudgers (Oecologia, 2020)

Design, synthesis, and screening of sulfonylurea-derived NLRP3 inflammasome inhibitors - Amol A. Kulkarni; Ayyiliath M. Sajith; Trevor T. Duarte; Anahis Tena; Charles T. Spencer; J. Phillip Bowen (Medicinal Chemistry Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Novel approach for connecting real driving emissions to the European vehicle laboratorial certification test procedure - Roberto A. Varella; João P. Ribau; Patrícia C. Baptista; Luis Sousa; Gonçalo O. Duarte (Environmental Science and Pollution Research, 2019)

Peeling the Otolith of Fish: Optimal Parameterization for Micro-CT Scanning - Jonas E. Vasconcelos-Filho; Felix S. L. Thomsen; Borko Stosic; Antonio C. D. Antonino; Daniel A. Duarte; Richard J. Heck; Rosangela P. T. Lessa; Francisco M. Santana; Beatrice P. Ferreira; Paulo J. Duarte-Neto (Frontiers in Marine Science, 2019)

Corrigendum: Night-Time Temperature Reprieves Enhance the Thermal Tolerance of a Symbiotic Cnidarian - Shannon G. Klein; Kylie A. Pitt; Cathy H. Lucas; Shiou-Han Hung; Sebastian Schmidt-Roach; Manuel Aranda; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Soil microbes that may accompany climate warming increase alpine plant production - Joshua S. Lynn; Danielle A. Duarte; Jennifer A. Rudgers (Oecologia, 2019)

Overhauling Ocean Spatial Planning to Improve Marine Megafauna Conservation - Ana Micaela Martins Sequeira; Graeme Clive Hays; David W. Sims; Víctor M. Eguíluz; Jorge P. Rodríguez; Michelle R. Heupel; Rob Harcourt; Hannah Calich; Nuno Queiroz; Daniel Paul Costa; Juan Fernández-Gracia; Luciana C. Ferreira; et al. (Frontiers in Marine Science, 2019)

Niche partitioning and morphospace in early stages of two sympatric Diogenichthys species (Myctophidae) - Francisca Zavala‐Muñoz; Javier Vera‐Duarte; Claudia A. Bustos; Jorge Angulo‐Aros; Mauricio F. Landaeta (Journal of Fish Biology, 2019)
Diet and morphospace of larval stages of two sympatric lanternfish Diogenichthys atlanticus and D. laternatus from the south‐east Pacific Ocean were compared and the covariance between both variables was assessed for each species. Diogenichthys atlanticus stomach contents consisted mainly of copepod nauplii and digested remains and this species had a broader niche than D. laternatus , in which stomach contents were highly digested. No dietary overlap was found between both species. The covariance between skull shape and diet for D. atlanticus was given by a wider mouth gape related to the presence of copepod nauplii, whilst for D. laternatus , a shorter snout and posteriorly displaced eye were related to the presence of highly digested stomach contents. Interspecific differences between diets and skull shapes suggest that both species may have undergone morphological or niche divergence to avoid competition, such as feeding at different hours or depth stratification.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Tomato mottle mosaic virus in Brazil and its relationship with Tm-22 gene - Alice Nagai; Lígia M. L. Duarte; Alexandre L. R. Chaves; Lázaro E. P. Peres; Déborah Y. A. C. dos Santos (European Journal of Plant Pathology, 2019)

Evaluation of hydration of cement pastes containing high volume of mineral additions - M. A. S. Anjos; R. Reis; A. Camões; F. Duarte; C. Jesus (European Journal of Environmental and Civil Engineering, 2019)

Mineralogical, chemical and leaching characteristics of ashes from residential biomass combustion - Célia A. Alves; Oriol Font; Natalia Moreno; Estela D. Vicente; Márcio Duarte; Luís A.C. Tarelho; Xavier Querol (Environmental Science and Pollution Research, 2019)

Night-Time Temperature Reprieves Enhance the Thermal Tolerance of a Symbiotic Cnidarian - Shannon G. Klein; Kylie A. Pitt; Cathy H. Lucas; Shiou-Han Hung; Sebastian Schmidt-Roach; Manuel Aranda; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Distribution and Characteristics of Halobates germanus Population in the Red Sea - Gauri A. Mahadik; Susana Agusti; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Evaluation of the effects of extracts of Maytenus imbricata (Celastraceae) on the treatment of inflammatory and metabolic dysfunction induced by high-refined carbohydrate diet - C. C. Veloso; M. C. Oliveira; V. G. Rodrigues; C. C. Oliveira; L. P. Duarte; M. M. Teixeira; A. V. M. Ferreira; A. C. Perez (Inflammopharmacology, 2019)

Tidewater Glaciers and Bedrock Characteristics Control the Phytoplankton Growth Environment in a Fjord in the Arctic - Laura Halbach; Mikko Vihtakari; Pedro Duarte; Alistair Everett; Mats A. Granskog; Haakon Hop; Hanna M. Kauko; Svein Kristiansen; Per I. Myhre; Alexey K. Pavlov; Ankit Pramanik; Agnieszka Tatarek; et al. (Frontiers in Marine Science, 2019)

P2X7 Receptors Mediate CO-Induced Alterations in Gene Expression in Cultured Cortical Astrocytes—Transcriptomic Study - Sara R. Oliveira; Cláudia Figueiredo-Pereira; Carlos B. Duarte; Helena L. A. Vieira (Molecular Neurobiology, 2019)

Biosynthesis and bioactivity of Cynara cardunculus L. guaianolides and hydroxycinnamic acids: a genomic, biochemical and health-promoting perspective - Patrícia A. B. Ramos; Ana M. Ferro; M. Margarida Oliveira; Sónia Gonçalves; Carmen S. R. Freire; Armando J. D. Silvestre; Maria F. Duarte (Phytochemistry Reviews, 2019)

Endurance exercise protects skeletal muscle against both doxorubicin-induced and inactivity-induced muscle wasting - Scott K. Powers; Jose A. Duarte; Branden Le Nguyen; Hayden Hyatt (Pflügers Archiv - European Journal of Physiology, 2019)

Can Luminol Be a Fluorophore? - M. Fátima Barroso; Rui J. A. Silva; Sérgio F. Moreira; Sofia S. Rodrigues; Helena M. R. Gonçalves; Abel J. Duarte (Journal of Fluorescence, 2019)

Uptake of copper from acid mine drainage by the microalgae Nannochloropsis oculata - Maria del Rosario Martínez-Macias; Ma. A. Correa-Murrieta; Yedidia Villegas-Peralta; Germán Eduardo Dévora-Isiordia; Jesús Álvarez-Sánchez; Jorge Saldivar-Cabrales; Reyna G. Sánchez-Duarte (Environmental Science and Pollution Research, 2019)

Better estimates of soil carbon from geographical data: a revised global approach - Sandra Duarte-Guardia; Pablo L. Peri; Wulf Amelung; Douglas Sheil; Shawn W. Laffan; Nils Borchard; Michael I. Bird; Wouter Dieleman; David A. Pepper; Brian Zutta; Esteban Jobbagy; Lucas C. R. Silva; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Resilience of an aquatic macrophyte to an anthropogenically induced environmental stressor in a Ramsar wetland of southern Chile - Eduardo Jaramillo; Cristian Duarte; Fabio A. Labra; Nelson A. Lagos; Bruno Peruzzo; Ricardo Silva; Carlos Velasquez; Mario Manzano; Daniel Melnick (Ambio, 2019)

Impact of “The Blob” and “El Niño” in the SW Baja California Peninsula: Plankton and Environmental Variability of Bahia Magdalena - María del Carmen Jiménez-Quiroz; Rafael Cervantes-Duarte; René Funes-Rodríguez; Sofía A. Barón-Campis; Felipe de Jesús García-Romero; Sergio Hernández-Trujillo; David U. Hernández-Becerril; Rogelio González-Armas; Raúl Martell-Dubois; Sergio Cerdeira-Estrada; José I. Fernández-Méndez; Luis V. González-Ania; et al. (Frontiers in Marine Science, 2019)

Diagnosis of covert hepatic encephalopathy: a multi-center study testing the utility of single versus combined testing - Andres Duarte-Rojo; Sanath Allampati; Leroy R. Thacker; Christopher R. Flud; Kavish R. Patidar; Melanie B. White; Jagpal S. Klair; Douglas M. Heuman; James B. Wade; Edith A. Gavis; Jasmohan S. Bajaj (Metabolic Brain Disease, 2019)

Genetic diversity and differentiation in Patellifolia (Amaranthaceae) in the Macaronesian archipelagos and the Iberian Peninsula and implications for genetic conservation programmes - Lothar Frese; Marion Nachtigall; José María Iriondo; María Luisa Rubio Teso; Maria Cristina Duarte; Miguel Ângelo A. Pinheiro de Carvalho (Genetic Resources and Crop Evolution, 2019)

Effects of hydroelectric turbine noise on the behaviour of Leporinus taeniatus (Characiformes: Anostomidae) in captivity - Marina H. L. Duarte; Rafael M. C. Melo; Marina D. A. Scarpelli; Thiago M. A. Carvalho; Linilson R. Padovese; Nilo Bazzoli; Elizete Rizzo (Journal of Ethology, 2019)

Investigating taxon boundaries and extinction risk in endemic Chilean cacti (Copiapoa subsection Cinerei, Cactaceae) using chloroplast DNA sequences, microsatellite data and 3D mapping - Isabel Larridon; Emily Veltjen; Ilias Semmouri; Pieter Asselman; Pablo C. Guerrero; Milén Duarte; Helmut E. Walter; Mauricio A. Cisternas; Marie-Stéphanie Samain (Kew Bulletin, 2018)

Impact of incorporating ABCB1 and CYP4F2 polymorphisms in a pharmacogenetics-guided warfarin dosing algorithm for the Brazilian population - Letícia C. Tavares; Nubia E. Duarte; Leiliane R. Marcatto; Renata A. G. Soares; Jose E. Krieger; Alexandre C. Pereira; Paulo Caleb Junior Lima Santos (European Journal of Clinical Pharmacology, 2018)

Improvement of Biomethane Production from Sewage Sludge in Co-digestion with Glycerol and Waste Frying Oil, Using a Design of Experiments - J. V. Oliveira; T. Duarte; J. C. Costa; A. J. Cavaleiro; M. A. Pereira; M. M. Alves (BioEnergy Research, 2018)

Claims That Anthropogenic Stressors Facilitate Jellyfish Blooms Have Been Amplified Beyond the Available Evidence: A Systematic Review - Kylie A. Pitt; Cathy H. Lucas; Robert H. Condon; Carlos M. Duarte; Ben Stewart-Koster (Frontiers in Marine Science, 2018)

Surviving in hot and cold: psychrophiles and thermophiles from Deception Island volcano, Antarctica - Amanda G. Bendia; Gabriel G. Araujo; André A. Pulschen; Bruna Contro; Rubens T. D. Duarte; Fábio Rodrigues; Douglas Galante; Vivian H. Pellizari (Extremophiles, 2018)

Predator Avoidance in the European Seabass After Recovery From Short-Term Hypoxia and Different CO2 Conditions - Alexandra Steckbauer; Carlos Díaz-Gil; Josep Alós; Ignacio A. Catalán; Carlos M. Duarte (Frontiers in Marine Science, 2018)

Scirtothrips dorsalis (Thysanoptera: Thripidae): a Newly Introduced Polyphagous Pest in Northeastern Brazil - N S Dias-Pini; M G A Lima; E F B Lima; G P S Maciel; P M Duarte (Neotropical Entomology, 2018)

Dramatic loss of seagrass habitat under projected climate change in the Mediterranean Sea - Rosa M. Chefaoui; Carlos M. Duarte; Ester A. Serrão (Global Change Biology, 2018)
Although climate warming is affecting most marine ecosystems, the Mediterranean is showing earlier impacts. Foundation seagrasses are already experiencing a well‐documented regression in the Mediterranean which could be aggravated by climate change. Here, we forecast distributions of two seagrasses and contrast predicted loss with discrete regions identified on the basis of extant genetic diversity. Under the worst‐case scenario, Posidonia oceanica might lose 75% of suitable habitat by 2050 and is at risk of functional extinction by 2100, whereas Cymodocea nodosa would lose only 46.5% in that scenario as losses are compensated with gained and stable areas in the Atlantic. Besides, we predict that erosion of present genetic diversity and vicariant processes can happen, as all Mediterranean genetic regions could decrease considerably in extension in future warming scenarios. The functional extinction of Posidonia oceanica would have important ecological impacts and may also lead to the release of the massive carbon stocks these ecosystems stored over millennia.

Creation of a coastal evolution prognostic model using shoreline historical data and techniques of digital image processing in a GIS environment for generating future scenarios - Willamys R. N. de Sousa; Michael V. S. Souto; Stefanny S. Matos; Cynthia R. Duarte; Ana R. G. N. L. Salgueiro; Cláudio A. da Silva Neto (International Journal of Remote Sensing, 2018)

Publisher Correction to: Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

Aged rats are more vulnerable than adolescents to “ecstasy”-induced toxicity - R. Feio-Azevedo; V. M. Costa; D. J. Barbosa; A. Teixeira-Gomes; I. Pita; S. Gomes; F. C. Pereira; M. Duarte-Araújo; J. A. Duarte; F. Marques; E. Fernandes; M. L. Bastos; et al. (Archives of Toxicology, 2018)

Effects of a nanoemulsion with Copaifera officinalis oleoresin against monogenean parasites of Colossoma macropomum: A Neotropical Serrasalmidae - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; C Solans; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Monogeneans are ectoparasites that may cause losses in production and productivity in the aquaculture of Colossoma macropomum . Chemotherapeutics used in aquaculture usually have major adverse effects on fish; hence, the use of essential oils has been considered advantageous, but these are not soluble in water. Thus, the use of nanostructures to enhance water solubility of compounds and improve bioactivity may be very promising. This study investigated the antiparasitic activity of nanoemulsion prepared with Copaifera officinalis oleoresin (50, 100, 150, 200 and 300 mg/L), against monogenean parasites from the gills of C. macropomum . The particle size distribution and zeta potential suggested that a potentially kinetic stable system was generated. The nanoemulsion from C. officinalis oleoresin achieved high efficacy (100%) at low concentrations (200 and 300 mg/L) after 15 min of exposure. This was the first time that a nanoemulsion was generated from C. officinalis oleoresin using a solvent‐free, non‐heating and low‐energy method. Moreover, this was the first time that an antiparasitic against monogeneans on fish gills, based on nanoemulsion of C. officinalis oleoresin, was tested.

Algal Colonization of Young Arctic Sea Ice in Spring - Hanna M. Kauko; Lasse M. Olsen; Pedro Duarte; Ilka Peeken; Mats A. Granskog; Geir Johnsen; Mar Fernández-Méndez; Alexey K. Pavlov; Christopher J. Mundy; Philipp Assmy (Frontiers in Marine Science, 2018)

Climate Change Impacts on Seagrass Meadows and Macroalgal Forests: An Integrative Perspective on Acclimation and Adaptation Potential - Bernardo Duarte; Irene Martins; Rui Rosa; Ana R. Matos; Michael Y. Roleda; Thorsten B. H. Reusch; Aschwin H. Engelen; Ester A. Serrão; Gareth A. Pearson; João C. Marques; Isabel Caçador; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2018)

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

β-(1→6)-d-glucan secreted during the optimised production of exopolysaccharides by Paecilomyces variotii has immunostimulatory activity - Erica F. Osaku; Rafael A. Menolli; Claudia R. L. de M. Costa; Fernando Henrique G. Tessaro; Renan H. de Melo; Alex E. do Amaral; Péricles A. D. Duarte; Arquimedes Paixão de Santana Filho; Andrea Caroline Ruthes; José Luis da C. Silva; Rosiane G. Mello (Antonie van Leeuwenhoek, 2018)

Cookie‐cutter shark Isistius spp. predation upon different tuna species from the south‐western Atlantic Ocean - Y. V. Niella; L. A. G. Duarte; V. R. Bandeira; O. Crespo; D. Beare; F. H. V. Hazin (Journal of Fish Biology, 2018)
The predation of cookie‐cutter sharks Isistius spp. upon the early life stages of yellowfin tuna Thunnus albacares , skipjack tuna Katsuwonus pelamis and little tunny Euthynnus alletteratus are described. New evidence suggesting a connection between commercial fishing and predation by Isistius sp. is presented, with these sharks biting tunas hooked in surface waters during daylight. The healing patterns of the wounds made by the sharks are described in detail and, although such damage is known to negatively influence market price elsewhere, it is not the case on the south‐east Brazilian coast.

Algal Hot Spots in a Changing Arctic Ocean: Sea-Ice Ridges and the Snow-Ice Interface - Mar Fernández-Méndez; Lasse M. Olsen; Hanna M. Kauko; Amelie Meyer; Anja Rösel; Ioanna Merkouriadi; Christopher J. Mundy; Jens K. Ehn; A. Malin Johansson; Penelope M. Wagner; Åse Ervik; Brian K. Sorrell; et al. (Frontiers in Marine Science, 2018)

Nanoemulsion from essential oil of Pterodon emarginatus (Fabaceae) shows in vitro efficacy against monogeneans of Colossoma macropomum (Pisces: Serrasalmidae) - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; E C Conceição; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Outbreaks of diseases pose a major threat to sustainable aquaculture development worldwide. Application of herbal products to combat parasitic diseases provides an alternative approach for sustainable aquaculture. This study investigated the in vitro antiparasitic effects of an oil‐in‐water nanoemulsion prepared using the essential oil from Pterodon emarginatus , against monogeneans infesting Colossoma macropomum . Gill arches from C. macropomum (47.6 ± 14.5 g and 13.5 ± 1.4 cm) that were naturally parasitized by Anacanthorus spathulatus , Notozothecium janauachensis and Mymarothecium boegeri were immersed in different dispersions of the P. emarginatus nanoemulsions (0, 50, 100, 200, 400 and 600 mg/L). The major compounds presented in the essential oil of P. emarginatus were β‐elemene, β‐caryophyllene and α‐humulene. Characterization of these nanoemulsions showed that they have a small mean droplet size and low polydispersity index, which is concordant with stable systems. In this in vitro trial, the P. emarginatus nanoemulsion concentrations of 100, 200, 400 and 600 mg/L presented 100% helminthic efficacy against monogeneans of the gills of C. macropomum . The highest two concentrations used (400 and 600 mg/L) were seen to immobilize the parasites after only 15 min. Therefore, it would be worthwhile testing these concentrations in therapeutic baths against monogeneans of C. macropomum .

New Tools to Identify the Location of Seagrass Meadows: Marine Grazers as Habitat Indicators - Graeme C. Hays; Teresa Alcoverro; Marjolijn J. A. Christianen; Carlos M. Duarte; Mark Hamann; Peter I. Macreadie; Helene D. Marsh; Michael A. Rasheed; Michele Thums; Richard K. F. Unsworth; Paul H. York; Nicole Esteban (Frontiers in Marine Science, 2018)

Tingenone, a pentacyclic triterpene, induces peripheral antinociception due to cannabinoid receptors activation in mice - C. C. Veloso; R. C. M. Ferreira; V. G. Rodrigues; L. P. Duarte; A. Klein; I. D. Duarte; T. R. L. Romero; A. C. Perez (Inflammopharmacology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Communities of arbuscular mycorrhizal fungi under Picconia azorica in native forests of Azores - Catarina Drumonde Melo; Sara Luna; Claudia Krüger; Christopher Walker; Duarte Mendonça; Henrique M. A. C. Fonseca; Maria Jaizme-Vega; Artur Câmara Machado (Symbiosis, 2018)

Cell Penetration and Secondary Structure of a Synthetic Peptide with Anti-HIV Activity - Taimi E. Paneque; Anna C. Ramírez-Suárez; Dionne Casillas; Carlos A. Duarte; Glay Chinea; Carlos Espinosa-Viñals; Hilda Garay; Llilian Gómez-Pérez; Celia Fernández-Ortega (International Journal of Peptide Research and Therapeutics, 2017)

Habitat-dependent niche partitioning between colour morphs of the algal-dwelling shrimp Hippolyte obliquimanus - Rafael C. Duarte; Augusto A. V. Flores; Catarina Vinagre; Miguel C. Leal (Marine Biology, 2017)

Diet and body shape changes of pāroko Kelloggella disalvoi (Gobiidae) from intertidal pools of Easter Island - J. Vera‐Duarte; C. A. Bustos; M. F. Landaeta (Journal of Fish Biology, 2017)
This study assesses seasonal variation in the morphology and diet of juveniles and adults of the Easter Island endemic goby Kelloggella disalvoi from intertidal pools during September–October 2015 (spring) and June–July 2016 (winter), utilizing geometric morphometric and gut‐content analyses. A set of 16 landmarks was digitized in 128 individuals. Shape changes related to size changes ( i.e . allometry) were low (18·6%) and were seasonally similar. Body shape changes were mainly dorsoventral (44·2% of variance) and comprised posteroventral displacement of the premaxilla and bending of the body. The latter included vertical displacement of the anterior portion of the first and second dorsal fins and the entire base of the caudal fin. Diets mainly comprised developmental stages of harpacticoid copepods (from eggs to adults), ostracods, isopods, gastropods and bivalves. Also, trophic niche breadth remained constant throughout development and did not vary between seasons. Nonetheless, significant dietary differences were detected in specimens collected during spring (main prey items: harpacticoid copepods and copepod eggs) and winter (harpacticoid copepods and copepod nauplii). Finally, there was weak but significant covariation between diet and morphology: molluscivores were characterized by having an inferior mouth gape, whereas planktivores had an anteriorly directed premaxilla.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Zooplankton excretion metabolites stimulate Southern Ocean phytoplankton growth - A. Coello-Camba; M. Llabrés; C. M. Duarte; S. Agustí (Polar Biology, 2017)

Middle-Aged Diabetic Females and Males Present Distinct Susceptibility to Alzheimer Disease-like Pathology - E. Candeias; A. I. Duarte; I. Sebastião; M. A. Fernandes; A. I. Plácido; C. Carvalho; S. Correia; R. X. Santos; R. Seiça; M. S. Santos; C. R. Oliveira; P. I. Moreira (Molecular Neurobiology, 2017)

Cognitive Event-Related Potentials (P300) and Cognitive Impairment in Duchenne Muscular Dystrophy - N. Esquitin-Garduño; R. E. Escobar-Cedillo; B. G. Flores-Avalos; G. Escobar-Cedillo; A. Miranda-Duarte; L. B. López-Hernández; V. I. Orellana-Villazón; R. M. Coral-Vázquez; S. García; B. Gómez-Díaz (Neurophysiology, 2017)

Anthocyanins control neuroinflammation and consequent memory dysfunction in mice exposed to lipopolysaccharide - Fabiano B. Carvalho; Jessié M. Gutierres; Andressa Bueno; Paula Agostinho; Adriana M. Zago; Juliano Vieira; Pâmela Frühauf; José L. Cechella; Cristina Wayne Nogueira; Sara M. Oliveira; Caroline Rizzi; Roselia M. Spanevello; et al. (Molecular Neurobiology, 2017)

Guanosine Exerts Neuroprotective Effect in an Experimental Model of Acute Ammonia Intoxication - G. F. Cittolin-Santos; A. M. de Assis; P. A. Guazzelli; L. G. Paniz; J. S. da Silva; M. E. Calcagnotto; G. Hansel; K. C. Zenki; E. Kalinine; M. M. Duarte; D. O. Souza (Molecular Neurobiology, 2017)

On the opposite relation between extreme precipitation over west Amazon and southeastern Brazil: observations and model simulations - Iracema Fonseca de Albuquerque Cavalcanti; Jose A. Marengo; Lincoln Muniz Alves; Duarte Filipe Costa (International Journal of Climatology, 2017)
During the austral summer of 2014 and 2015, a severe drought occurred in southeastern Brazil at the same time when flooding conditions were registered in the state of Acre in the western Amazonia of Brazil. This study aimed the identification of the atmospheric and oceanic large‐scale characteristics and regional features associated with these conditions, and verification of the Center of Weather Forecasting and Climate Studies/National Institute of Space Research (CPTEC/INPE) atmospheric global circulation model ability in reproducing the observed features. The state of Acre was chosen as a pilot area of the PULSE ‐Brazil project – a web platform tool that contains climate, ecological and health data for Brazil. The observational data and model results were analysed for the climatological period of 1981–2010. Correlation analyses between precipitation over west Amazon and atmospheric and oceanic variables indicated the main patterns in both data sets. Extreme wet and dry Januaries over west Amazon were selected to explore the regional and large‐scale associated features. The general results of climate analyses indicated an opposite relation of precipitation between western Amazon and southeastern Brazil, in January, besides the typical precipitation dipole between the south Atlantic convergence zone and southeastern South America. This configuration is related to anomalous humidity flux at low levels and associated anomalous sea level pressure over southeastern South America induced by subsidence. The role of convection anomalies over the Pacific Ocean on South America anomalies is discussed. The wet and dry cases in Acre region display opposite atmospheric anomalies over South America that are linked to wavetrains over the Pacific Ocean, likely related to the opposite conditions of Indonesia‐Pacific tropical convection. Similar patterns of the dry cases were observed during January of 2014 and 2015. The model reproduced some observed atmospheric patterns related to precipitation extremes and the results are discussed in terms of regional and large‐scale climate variability.

Adenosine receptors: regulatory players in the preservation of mitochondrial function induced by ischemic preconditioning of rat liver - Filipe V. Duarte; João A. Amorim; Ana T. Varela; João S. Teodoro; Ana P. Gomes; Rodrigo A. Cunha; Carlos M. Palmeira; Anabela P. Rolo (Purinergic Signalling, 2017)

Fusarium verticillioides and fumonisin contamination in Bt and non-Bt maize cultivated in Brazil - Vinícius M. Barroso; Liliana O. Rocha; Tatiana A. Reis; Gabriela M. Reis; Aildson P. Duarte; Marcos D. Michelotto; Benedito Correa (Mycotoxin Research, 2017)

Synthesis and antileishmanial activity of 1,3-bis(aryloxy)propan-2-amines - Stefânia N. Lavorato; Mariana C. Duarte; Daniela P. Lage; Carlos A. P. Tavares; Eduardo A. F. Coelho; Ricardo J. Alves (Medicinal Chemistry Research, 2017)

Investigating essential and toxic elements in Antarctic macroalgae using a green analytical method - Rochele S. Picoloto; Rodrigo M. Pereira; Vanize C. Costa; Carla A. Hartwig; Claudio M. P. Pereira; Pio Colepicolo; Fabio A. Duarte; Marcia F. Mesko (Journal of Applied Phycology, 2017)

Entangled fates of holobiont genomes during invasion: nested bacterial and host diversities in Caulerpa taxifolia - S. Arnaud‐Haond; T. Aires; R. Candeias; S. J. L. Teixeira; C. M. Duarte; M. Valero; E. A. Serrão (Molecular Ecology, 2017)
Successful prevention and mitigation of biological invasions requires retracing the initial steps of introduction, as well as understanding key elements enhancing the adaptability of invasive species. We studied the genetic diversity of the green alga Caulerpa taxifolia and its associated bacterial communities in several areas around the world. The striking congruence of α and β diversity of the algal genome and endophytic communities reveals a tight association, supporting the holobiont concept as best describing the unit of spreading and invasion. Both genomic compartments support the hypotheses of a unique accidental introduction in the Mediterranean and of multiple invasion events in southern Australia. In addition to helping with tracing the origin of invasion, bacterial communities exhibit metabolic functions that can potentially enhance adaptability and competitiveness of the consortium they form with their host. We thus hypothesize that low genetic diversities of both host and symbiont communities may contribute to the recent regression in the Mediterranean, in contrast with the persistence of highly diverse assemblages in southern Australia. This study supports the importance of scaling up from the host to the holobiont for a comprehensive understanding of invasions.

A population genetics toolbox for the threatened canopy-forming brown seaweeds Cystoseira tamariscifolia and C. amentacea (Fucales, Sargassaceae) - Aschwin H. Engelen; Joana Costa; Ricardo Bermejo; Núria Marba; Carlos M. Duarte; Ester A. Serrão (Journal of Applied Phycology, 2017)

Biological and molecular characterization of a putative new potexvirus infecting Senna occidentalis - Jorge A. M. Rezende; Viviana M. Camelo-García; Sónia C. S. Andrade; José E. Buriolla; Elliot W. Kitajima; Ligia M. L. Duarte (Archives of Virology, 2017)

Cytotoxicity and oxidative stress responses of silica-coated iron oxide nanoparticles in CHSE-214 cells - K. Srikanth; Tito Trindade; A. C. Duarte; E. Pereira (Environmental Science and Pollution Research, 2017)

Home sweet home: evidence for nest‐fidelity in the rocky intertidal fish, the shanny L ipophrys pholis - J. Martins; F. Almada; A. Gonçalves; P. Duarte‐Coelho; P. E. Jorge (Journal of Fish Biology, 2017)
The ability to be faithful to a particular area or site was analysed in the shanny Lipophrys pholis . Using passive integrated transponders, adults from a population of L. pholis at Cabo Raso, Portugal, were followed over a period of 3 years. The findings showed that site fidelity is a consistent behaviour during the breeding season with specific breeding males being found only in particular sectors within the area, and in specific nests throughout the years. The fact that, in general, L. pholis individuals were absent from the study area during the non‐breeding season and breeding males were recorded returning to the same nests and sectors for consecutive breeding seasons suggests that they have developed excellent homing abilities. Translocation data corroborate this idea showing that breeding males successfully returned to their nests after a displacement of >100 m. Altogether, these findings highlight the relevance of life‐history traits ( e.g. nesting) in the conditioning of site fidelity and homing for this species of rocky intertidal fish, and more importantly, provide evidence for the need of a well‐developed navigational system.

Music supported therapy promotes motor plasticity in individuals with chronic stroke - P. Ripollés; N. Rojo; J. Grau-Sánchez; J. L. Amengual; E. Càmara; J. Marco-Pallarés; M. Juncadella; L. Vaquero; F. Rubio; E. Duarte; C. Garrido; E. Altenmüller; et al. (Brain Imaging and Behavior, 2016)

New jacaranone glucoside from Jacaranda oxyphylla leaves - V. V. Pereira; L. P. Duarte; R. R. Silva; J. A. Takahashi (Natural Product Research, 2016)

Prevalence of the genus Cladosporium on the integument of leaf-cutting ants characterized by 454 pyrosequencing - A. P. M. Duarte; M. Ferro; A. Rodrigues; M. Bacci; N. S. Nagamoto; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2016)

Flawed citation practices facilitate the unsubstantiated perception of a global trend toward increased jellyfish blooms - Marina Sanz‐Martín; Kylie A. Pitt; Robert H. Condon; Cathy H. Lucas; Charles Novaes de Santana; Carlos M. Duarte (Global Ecology and Biogeography, 2016)
Speculation over a global rise in jellyfish populations has become widespread in the scientific literature, but until recently the purported ‘global increase’ had not been tested. Here we present a citation analysis of peer‐reviewed literature to track the evolution of the current perception of increases in jellyfish and identify key papers involved in its establishment. Trend statements and citation threads were reviewed and arranged in a citation network. Trend statements were assessed according their degree of affirmation and spatial scale, and the appropriateness of the citations used to support statements was assessed. Analyses showed that 48.9% of publications misinterpreted the conclusions of cited sources, with a bias towards claiming jellyfish populations are increasing, with a single review having the most influence on the network. Collectively, these disparities resulted in a network based on unsubstantiated statements and citation threads. As a community, we must ensure our statements about scientific findings in general are accurately substantiated and carefully communicated such that incorrect perceptions, as in the case of jellyfish blooms, do not develop in the absence of rigorous testing.

Topography‐driven isolation, speciation and a global increase of endemism with elevation - Manuel J. Steinbauer; Richard Field; John‐Arvid Grytnes; Panayiotis Trigas; Claudine Ah‐Peng; Fabio Attorre; H. John B. Birks; Paulo A. V. Borges; Pedro Cardoso; Chang‐Hung Chou; Michele De Sanctis; Miguel M. de Sequeira; et al. (Global Ecology and Biogeography, 2016)
Aim Higher‐elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness. Location Thirty‐two insular and 18 continental elevational gradients from around the world. Methods We compiled entire floras with elevation‐specific occurrence information, and calculated the proportion of native species that are endemic (‘percent endemism’) in 100‐m bands, for each of the 50 elevational gradients. Using generalized linear models, we tested the relationships between percent endemism and elevation, isolation, temperature, area and species richness. Results Percent endemism consistently increased monotonically with elevation, globally. This was independent of richness–elevation relationships, which had varying shapes but decreased with elevation at high elevations. The endemism–elevation relationships were consistent with isolation‐related predictions, but inconsistent with hypotheses related to area, richness and temperature. Main conclusions Higher per‐species speciation rates caused by increasing isolation with elevation are the most plausible and parsimonious explanation for the globally consistent pattern of higher endemism at higher elevations that we identify. We suggest that topography‐driven isolation increases speciation rates in mountainous areas, across all elevations and increasingly towards the equator. If so, it represents a mechanism that may contribute to generating latitudinal diversity gradients in a way that is consistent with both present‐day and palaeontological evidence.

Structure–activity relationship of a series of 1,2-dihydroquinoline analogues and binding mode with Vibrio cholerae dihydrofolate reductase - Vítor W. Rabelo; Thienne F. Sampaio; Lívia D. Duarte; Desirée H. B. Lopes; Paula A. Abreu (Medicinal Chemistry Research, 2016)

Modulation of aquaporins 3 and 9 after exposure of ovine ovarian tissue to cryoprotectants followed by in vitro culture - A. D. Sales; A. B. G. Duarte; R. R. Santos; K. A. Alves; L. F. Lima; G. Q. Rodrigues; I. R. Brito; C. H. Lobo; J. B. Bruno; Y. Locatelli; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Research, 2016)

Spartina versicolor Fabre: Another case of Spartina trans-Atlantic introduction? - A. Baumel; M. Rousseau-Gueutin; C. Sapienza-Bianchi; A. Gareil; N. Duong; H. Rousseau; O. Coriton; R. Amirouche; S. Sciandrello; B. Duarte; I. Caçador; J. M. Castillo; et al. (Biological Invasions, 2016)

Advantages and limitations of chemical extraction tests to predict mercury soil-plant transfer in soil risk evaluations - R. J. R. Monteiro; S. M. Rodrigues; N. Cruz; B. Henriques; A. C. Duarte; P. F. A. M. Römkens; E. Pereira (Environmental Science and Pollution Research, 2016)

Biofortification of wheat, rice and common bean by applying foliar zinc fertilizer along with pesticides in seven countries - H. Ram; A. Rashid; W. Zhang; A. P. Duarte; N. Phattarakul; S. Simunji; M. Kalayci; R. Freitas; B. Rerkasem; R. S. Bal; K. Mahmood; E. Savasli; et al. (Plant and Soil, 2016)

Assessing soil erosion risk using RUSLE through a GIS open source desktop and web application - L. Duarte; A. C. Teodoro; J. A. Gonçalves; D. Soares; M. Cunha (Environmental Monitoring and Assessment, 2016)

Phagocytic cell responses to silica-coated dithiocarbamate-functionalized iron oxide nanoparticles and mercury co-exposures in Anguilla anguilla L. - Leonor Costa; Iram Mohmood; Tito Trindade; Naser A. Anjum; Armando C. Duarte; Eduarda Pereira (Environmental Science and Pollution Research, 2016)

Comparative study on metal biosorption by two macroalgae in saline waters: single and ternary systems - Paula Figueira; Bruno Henriques; Ana Teixeira; Cláudia B. Lopes; Ana T. Reis; Rui J. R. Monteiro; A. C. Duarte; M. A. Pardal; E. Pereira (Environmental Science and Pollution Research, 2016)

Testing the climate variability hypothesis in thermal tolerance limits of tropical and temperate tadpoles - L. M. Gutiérrez‐Pesquera; M. Tejedo; M. Á. Olalla‐Tárraga; H. Duarte; A. Nicieza; M. Solé (Journal of Biogeography, 2016)
Aim The climate variability hypothesis ( CVH ) states that a positive relationship may exist between the breadth of thermal tolerance range and the level of climatic variability experienced by taxa with increasing latitude, especially in terrestrial ectotherms. Under CVH , we expected to find a correspondence between both thermal tolerance limits ( CT max and CT min), ambient extreme temperature and the range sizes of species. We examined the validity of these predictions in a lowland tropical and a temperate tadpole assemblage. Location Lowland Neotropics (Bahia, Brazil) and Palaearctic (Iberian Peninsula and North Africa). Method We employed phylogenetic eigenvector regression ( PVR ) and Pagel's lambda to analyse phylogenetic signals in CT max and CT min. We used phylogenetic regression analyses ( PGLS ) to test the relationships between thermal limits, range size and temperature predictors (measured at the macroscale and microhabitat levels) and phy‐ ANOVA to compare both the physiological traits and thermal regimen in both tropical and temperate assemblages. Results We documented moderate‐to‐strong phylogenetic signal in both heat and cold tolerance. Temperate‐zone tadpoles had broader thermal tolerances than tropical ones. Thermal tolerance range was correlated with range sizes and was explained by seasonal thermal range predictors at the global scale. Both macro‐ and microclimate temperature variables provided the best predictive multivariate models of thermal limits at the global scale. Microclimatic predictors, however, were the main determinants of CT max and CT min variation at the local level of tropical and temperate communities respectively. Main conclusions Thermal tolerance range increases with latitude in tadpoles due to the higher increase in cold tolerance in temperate tadpoles. At the global scale, both macro‐ and microenvironment thermal information were reliable predictors of critical thermal limits and thermal tolerance range, as CVH predicts. However, thermal limits were best predicted by temperatures of the micro‐habitat at the regional level, thus suggesting that physiological thermal boundaries may be governed by thermal selection.

Biomineralization changes with food supply confer juvenile scallops ( Argopecten purpuratus ) resistance to ocean acidification - Laura Ramajo; Núria Marbà; Luis Prado; Sophie Peron; Marco A. Lardies; Alejandro B. Rodriguez‐Navarro; Cristian A. Vargas; Nelson A. Lagos; Carlos M. Duarte (Global Change Biology, 2016)
Future ocean acidification ( OA ) will affect physiological traits of marine species, with calcifying species being particularly vulnerable. As OA entails high energy demands, particularly during the rapid juvenile growth phase, food supply may play a key role in the response of marine organisms to OA . We experimentally evaluated the role of food supply in modulating physiological responses and biomineralization processes in juveniles of the Chilean scallop, Argopecten purpuratus, that were exposed to control ( pH ~ 8.0) and low pH ( pH ~ 7.6) conditions using three food supply treatments (high, intermediate, and low). We found that pH and food levels had additive effects on the physiological response of the juvenile scallops. Metabolic rates, shell growth, net calcification, and ingestion rates increased significantly at low pH conditions, independent of food. These physiological responses increased significantly in organisms exposed to intermediate and high levels of food supply. Hence, food supply seems to play a major role modulating organismal response by providing the energetic means to bolster the physiological response of OA stress. On the contrary, the relative expression of chitin synthase, a functional molecule for biomineralization, increased significantly in scallops exposed to low food supply and low pH , which resulted in a thicker periostracum enriched with chitin polysaccharides. Under reduced food and low pH conditions, the adaptive organismal response was to trade‐off growth for the expression of biomineralization molecules and altering of the organic composition of shell periostracum, suggesting that the future performance of these calcifiers will depend on the trajectories of both OA and food supply. Thus, incorporating a suite of traits and multiple stressors in future studies of the adaptive organismal response may provide key insights on OA impacts on marine calcifiers.

Astaxanthin and Its Esters in Pigmented Oil from Fermented Shrimp By-Products - José A. Núñez-Gastélum; Dalia I. Sánchez-Machado; Jaime López-Cervantes; Jesús R. Rodríguez-Núñez; Ma. A. Correa-Murrieta; Reyna G. Sánchez-Duarte; Olga N. Campas-Baypoli (Journal of Aquatic Food Product Technology, 2016)

The concerted impact of domestication and transposon insertions on methylation patterns between dogs and grey wolves - Ilana Janowitz Koch; Michelle M. Clark; Michael J. Thompson; Kerry A. Deere‐Machemer; Jun Wang; Lionel Duarte; Gitanjali E. Gnanadesikan; Eskender L. McCoy; Liudmilla Rubbi; Daniel R. Stahler; Matteo Pellegrini; Elaine A. Ostrander; et al. (Molecular Ecology, 2016)
The process of domestication can exert intense trait‐targeted selection on genes and regulatory regions. Specifically, rapid shifts in the structure and sequence of genomic regulatory elements could provide an explanation for the extensive, and sometimes extreme, variation in phenotypic traits observed in domesticated species. Here, we explored methylation differences from >24 000 cytosines distributed across the genomes of the domesticated dog ( Canis familiaris ) and the grey wolf ( Canis lupus ). PCA and model‐based cluster analyses identified two primary groups, domestic vs. wild canids. A scan for significantly differentially methylated sites ( DMS s) revealed species‐specific patterns at 68 sites after correcting for cell heterogeneity, with weak yet significant hypermethylation typical of purebred dogs when compared to wolves (59% and 58%, P 66%) of differentially methylated regions contained or were associated with repetitive elements, indicative of a genotype‐mediated trend. However, DMS s were also often linked to functionally relevant genes (e.g. neurotransmitters). Finally, we utilized known genealogical relationships among Yellowstone wolves to survey transmission stability of methylation marks, from which we found a substantial fraction that demonstrated high heritability (both H 2 and h 2 > 0.99). These analyses provide a unique epigenetic insight into the molecular consequences of recent selection and radiation of our most ancient domesticated companion, the dog. These findings suggest selection has acted on methylation patterns, providing a new genomic perspective on phenotypic diversification in domesticated species.

In situ p rotein‐ SIP highlights Burkholderiaceae as key players degrading toluene by para ring hydroxylation in a constructed wetland model - Vanessa Lünsmann; Uwe Kappelmeyer; René Benndorf; Paula M. Martinez‐Lavanchy; Anja Taubert; Lorenz Adrian; Marcia Duarte; Dietmar H. Pieper; Martin von Bergen; Jochen A. Müller; Hermann J. Heipieper; Nico Jehmlich (Environmental Microbiology, 2016)
Summary In constructed wetlands, organic pollutants are mainly degraded via microbial processes. Helophytes, plants that are commonly used in these systems, provide oxygen and root exudates to the rhizosphere, stimulating microbial degradation. While the treatment performance of constructed wetlands can be remarkable, a mechanistic understanding of microbial degradation processes in the rhizosphere is still limited. We investigated microbial toluene removal in a constructed wetland model system combining 16S rRNA gene sequencing, metaproteomics and 13 C ‐toluene in situ protein‐based stable isotope probing (protein‐ SIP ). The rhizospheric bacterial community was dominated by B urkholderiales and R hizobiales , each contributing about 20% to total taxon abundance. Protein‐ SIP data revealed that the members of B urkholderiaceae , the proteins of which showed about 73% of 13 C ‐incorporation, were the main degraders of toluene in the planted system, while the members of C omamonadaceae were involved to a lesser extent in degradation (about 64% 13 C ‐incorporation). Among the B urkholderiaceae , one of the key players of toluene degradation could be assigned to R alstonia pickettii . We observed that the main pathway of toluene degradation occurred via two subsequent monooxygenations of the aromatic ring. Our study provides a suitable approach to assess the key processes and microbes that are involved in the degradation of organic pollutants in complex rhizospheric ecosystems.

Highly differentiated human airway epithelial cells: a model to study host cell–parasite interactions in pertussis - Claudia Guevara; Chengxian Zhang; Jennifer A. Gaddy; Junaid Iqbal; Julio Guerra; David P. Greenberg; Michael D. Decker; Nicholas Carbonetti; Timothy D. Starner; Paul B. McCray; Frits R. Mooi; Oscar G. Gómez-Duarte (Infectious Diseases, 2016)

Photocatalytic Treatment of Olive Oil Mill Wastewater Using TiO2 and Fe2O3 Nanomaterials - V. Nogueira; I. Lopes; T. A. P. Rocha-Santos; F. Gonçalves; A. C. Duarte; R. Pereira (Water, Air, & Soil Pollution, 2016)

Large-Scale Prediction of Seagrass Distribution Integrating Landscape Metrics and Environmental Factors: The Case of Cymodocea nodosa (Mediterranean–Atlantic) - Rosa M. Chefaoui; Jorge Assis; Carlos M. Duarte; Ester A. Serrão (Estuaries and Coasts, 2016)

Does ecophysiological behaviour explain habitat occupation of sympatric Clusia species in a Brazilian Atlantic rainforest? - Ulrich Lüttge; Fabio R. Scarano; Eduardo A. de Mattos; Augusto C. Franco; Fernando Broetto; André T. C. Dias; Heitor M. Duarte; Norbert Uehlein; Tânia Wendt (Trees, 2015)

Potato virus Y infection affects flavonoid profiles of Physalis angulata L. - Alice Nagai; Lígia M. L. Duarte; Alexandre L. R. Chaves; Déborah Y. A. C. dos Santos (Brazilian Journal of Botany, 2015)

Alternative food promotes broad mite control on chilli pepper plants - Marcus V. A. Duarte; Madelaine Venzon; Marilia C. de S. Bittencourt; Fredy A. Rodríguez-Cruz; Angelo Pallini; Arne Janssen (BioControl, 2015)

A breakthrough on Amanita phalloides poisoning: an effective antidotal effect by polymyxin B - Juliana Garcia; Vera Marisa Costa; Alexandra T. P. Carvalho; Ricardo Silvestre; José Alberto Duarte; Daniel F. A. R. Dourado; Marcelo D. Arbo; Teresa Baltazar; Ricardo Jorge Dinis-Oliveira; Paula Baptista; Maria de Lourdes Bastos; Félix Carvalho (Archives of Toxicology, 2015)

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

Antileishmanial activity of compounds produced by endophytic fungi derived from medicinal plant Vernonia polyanthes and their potential as source of bioactive substances - Adriana M. do Nascimento; Mateus Gonçalves Soares; Fernanda K. V. da Silva Torchelsen; Jorge A. Viana de Araujo; Paula S. Lage; Mariana C. Duarte; Pedro H. R. Andrade; Tatiana G. Ribeiro; Eduardo A. F. Coelho; Andréa M. do Nascimento (World Journal of Microbiology and Biotechnology, 2015)

Assessing the ecotoxicity of metal nano-oxides with potential for wastewater treatment - V. Nogueira; I. Lopes; T. A. P. Rocha-Santos; M. G. Rasteiro; N. Abrantes; F. Gonçalves; A. M. V. M. Soares; A. C. Duarte; R. Pereira (Environmental Science and Pollution Research, 2015)

Gain-assisted plasmonic metamaterials: mimicking nature to go across scales - Antonio De Luca; Roberto Bartolino; Miguel A. Correa-Duarte; M. Lucia Curri; Nicole F. Steinmetz; Giuseppe Strangi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2015)

Geostatistics and Geographic Information Systems to Study the Spatial Distribution of Grapholita molesta (Busck) (Lepidoptera: Tortricidae) in Peach Fields - F Duarte; M V Calvo; A Borges; I B Scatoni (Neotropical Entomology, 2015)

Volatile organic compounds emitted by the stacks of restaurants - Célia A. Alves; Margarita Evtyugina; Mário Cerqueira; Teresa Nunes; Márcio Duarte; Estela Vicente (Air Quality, Atmosphere & Health, 2015)

Synergistic effects of hypoxia and increasing CO2 on benthic invertebrates of the central Chilean coast - Alexandra Steckbauer; Laura Ramajo; Iris E. Hendriks; Miriam Fernandez; Nelson A. Lagos; Luis Prado; Carlos M. Duarte (Frontiers in Marine Science, 2015)

Size-Dependent Arsenic Accumulation in Scrobicularia plana in a Temperate Coastal Lagoon (Ria de Aveiro, Portugal) - T. Ereira; J. P. Coelho; A. C. Duarte; M. A. Pardal; M. E. Pereira (Water, Air, & Soil Pollution, 2015)

Effects of resistance training on neuromuscular characteristics and pacing during 10-km running time trial - Mayara V. Damasceno; Adriano E. Lima-Silva; Leonardo A. Pasqua; Valmor Tricoli; Marcos Duarte; David J. Bishop; Rômulo Bertuzzi (European Journal of Applied Physiology, 2015)

CO2-Driven Ocean Acidification Disrupts the Filter Feeding Behavior in Chilean Gastropod and Bivalve Species from Different Geographic Localities - Cristian A. Vargas; Victor M. Aguilera; Valeska San Martín; Patricio H. Manríquez; Jorge M. Navarro; Cristian Duarte; Rodrigo Torres; Marco A. Lardies; Nelson A. Lagos (Estuaries and Coasts, 2015)

Lipid peroxidation and its control in Anguilla anguilla hepatocytes under silica-coated iron oxide nanoparticles (with or without mercury) exposure - Koigoora Srikanth; Naser A. Anjum; Tito Trindade; Armando C. Duarte; Edurda Pereira; Iqbal Ahmad (Environmental Science and Pollution Research, 2015)

Nickel and Copper Toxicity to Embryos of the Long-Spined Sea Urchin, Diadema savignyi - G. Rosen; I. Rivera-Duarte; M. A. Colvin; R. E. Dolecal; L. J. Raymundo; P. J. Earley (Bulletin of Environmental Contamination and Toxicology, 2015)

Deer populations inhabiting urban areas in the south of Spain: habitat and conflicts - Jesús Duarte; Miguel A. Farfán; Julia E. Fa; J. Mario Vargas (European Journal of Wildlife Research, 2015)

Contribution of Coagulation–Flocculation Process for a More Sustainable Pig Slurry Management - R. A. Fragoso; E. A. Duarte; J. Paiva (Water, Air, & Soil Pollution, 2015)

Catalog of total excitation–emission and total synchronous fluorescence maps with synchronous fluorescence spectra of homologated fluorescent pesticides in large use in Morocco: development of a spectrometric low cost and direct analysis as an alert method in case of massive contamination of soils and waters by fluorescent pesticides - S. Foudeil; H. Hassoun; T. Lamhasni; S. Ait Lyazidi; F. Benyaich; M. Haddad; M. Choukrad; A. Boughdad; M. Bounakhla; H. Bounouira; R. M. B. O. Duarte; A. Cachada; et al. (Environmental Science and Pollution Research, 2015)

Genetic diversity and biogeographical patterns of Caulerpa prolifera across the Mediterranean and Mediterranean/Atlantic transition zone - Elena Varela-Álvarez; Ana C. Balau; Núria Marbà; Julio Afonso-Carrillo; Carlos M. Duarte; Ester A. Serrão (Marine Biology, 2015)

Intraspecific Variability in the Response of the Edible Mussel Mytilus chilensis (Hupe) to Ocean Acidification - Cristian Duarte; Jorge M. Navarro; Karin Acuña; Rodrigo Torres; Patricio H. Manríquez; Marcos A. Lardies; Cristian A. Vargas; Nelson A. Lagos; Víctor Aguilera (Estuaries and Coasts, 2015)

Occurrence and analysis of endocrine-disrupting compounds in a water supply system - A. R. M Carvalho; V. V. Cardoso; A. Rodrigues; E. Ferreira; M. J. Benoliel; E. A. Duarte (Environmental Monitoring and Assessment, 2015)

Lipids and proteins—major targets of oxidative modifications in abiotic stressed plants - Naser A. Anjum; Adriano Sofo; Antonio Scopa; Aryadeep Roychoudhury; Sarvajeet S. Gill; Muhammad Iqbal; Alexander S. Lukatkin; Eduarda Pereira; Armando C. Duarte; Iqbal Ahmad (Environmental Science and Pollution Research, 2015)

Too much is bad—an appraisal of phytotoxicity of elevated plant-beneficial heavy metal ions - Naser A. Anjum; Harminder P. Singh; M. Iqbal R. Khan; Asim Masood; Tasir S. Per; Asha Negi; Daizy R. Batish; Nafees A. Khan; Armando C. Duarte; Eduarda Pereira; Iqbal Ahmad (Environmental Science and Pollution Research, 2015)

Activation of IGF-1 and Insulin Signaling Pathways Ameliorate Mitochondrial Function and Energy Metabolism in Huntington’s Disease Human Lymphoblasts - Luana Naia; I. Luísa Ferreira; Teresa Cunha-Oliveira; Ana I. Duarte; Márcio Ribeiro; Tatiana R. Rosenstock; Mário N. Laço; Maria J. Ribeiro; Catarina R. Oliveira; Frédéric Saudou; Sandrine Humbert; A. Cristina Rego (Molecular Neurobiology, 2015)

A new species of the oligotrophic genus Ochroconis (Sympoventuriaceae) - K. Samerpitak; A. P. M. Duarte; D. Attili-Angelis; F. C. Pagnocca; G. Heinrichs; A. J. M. M. Rijs; A. Alfjorden; A. H. G. Gerrits van den Ende; S. B. J. Menken; G. S. de Hoog (Mycological Progress, 2015)

Plant-beneficial elements status assessment in soil-plant system in the vicinity of a chemical industry complex: shedding light on forage grass safety issues - Naser A. Anjum; Armando C. Duarte; Eduarda Pereira; Iqbal Ahmad (Environmental Science and Pollution Research, 2015)

Juncus maritimus root biochemical assessment for its mercury stabilization potential in Ria de Aveiro coastal lagoon (Portugal) - Naser A. Anjum; Armando C. Duarte; Eduarda Pereira; Iqbal Ahmad (Environmental Science and Pollution Research, 2015)

Phylogeny and recombination analysis of Brazilian yellow passion fruit isolates of Cowpea aphid-borne mosaic virus: origin and relationship with hosts - Leilane K. Rodrigues; Leonardo A. Silva; Renata M. Garcêz; Alexandre L. R. Chaves; Ligia M. L. Duarte; José S. Giampani; Addolorata Colariccio; Ricardo Harakava; Marcelo Eiras (Australasian Plant Pathology, 2015)

Spatial gradients in trace metal concentrations in the surface microlayer of the Mediterranean Sea - Antonio Tovar-Sánchez; Jesús M. Arrieta; Carlos M. Duarte; Sergio A. Sañudo-Wilhelmy (Frontiers in Marine Science, 2014)

Biomares, a LIFE project to restore and manage the biodiversity of Prof. Luiz Saldanha Marine Park - Alexandra H. Cunha; Karim Erzini; Ester A. Serrão; Emanuel Gonçalves; Rita Borges; Miguel Henriques; Victor Henriques; Miriam Guerra; Carlos Duarte; Núria Marbá; Mark Fonseca (Journal of Coastal Conservation, 2014)

Metal/metalloid stress tolerance in plants: role of ascorbate, its redox couple, and associated enzymes - Naser A. Anjum; Sarvajeet S. Gill; Ritu Gill; Mirza Hasanuzzaman; Armando C. Duarte; Eduarda Pereira; Iqbal Ahmad; Renu Tuteja; Narendra Tuteja (Protoplasma, 2014)

The Impact of Uranium Mine Contamination of Soils on Plant Litter Decomposition - Ana C. Freitas; Dina Rodrigues; Teresa A. P. Rocha-Santos; Fernando Gonçalves; Armando C. Duarte; Ruth Pereira (Archives of Environmental Contamination and Toxicology, 2014)

Geochemistry, mineralogy, solid-phase fractionation and oral bioaccessibility of lead in urban soils of Lisbon - A. P. Reis; C. Patinha; J. Wragg; A. C. Dias; M. Cave; A. J. Sousa; C. Costa; A. Cachada; E. Ferreira da Silva; F. Rocha; A. Duarte (Environmental Geochemistry and Health, 2014)

Salt Marsh Halophyte Services to Metal–Metalloid Remediation: Assessment of the Processes and Underlying Mechanisms - Naser A. Anjum; Iqbal Ahmad; Mónica Válega; Iram Mohmood; Sarvajeet S. Gill; Narendra Tuteja; Armando C. Duarte; Eduarda Pereira (Critical Reviews in Environmental Science and Technology, 2014)

Diazoxide Attenuates Autoimmune Encephalomyelitis and Modulates Lymphocyte Proliferation and Dendritic Cell Functionality - N. Virgili; P. Mancera; C. Chanvillard; A. Wegner; B. Wappenhans; M. J. Rodríguez; C. Infante-Duarte; J. F. Espinosa-Parrilla; M. Pugliese (Journal of Neuroimmune Pharmacology, 2014)

Mercury accumulation and tissue-specific antioxidant efficiency in the wild European sea bass (Dicentrarchus labrax) with emphasis on seasonality - C. L. Mieiro; M. Dolbeth; T. A. Marques; A. C. Duarte; M. E. Pereira; M. Pacheco (Environmental Science and Pollution Research, 2014)

Leaf-cutting ants: an unexpected microenvironment holding human opportunistic black fungi - A. P. M. Duarte; D. Attili-Angelis; N. C. Baron; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2014)

Gelatinous zooplankton biomass in the global oceans: geographic variation and environmental drivers - Cathy H. Lucas; Daniel O. B. Jones; Catherine J. Hollyhead; Robert H. Condon; Carlos M. Duarte; William M. Graham; Kelly L. Robinson; Kylie A. Pitt; Mark Schildhauer; Jim Regetz (Global Ecology and Biogeography, 2014)
Aim Scientific debate regarding the future trends, and subsequent ecological, biogeochemical and societal impacts, of gelatinous zooplankton ( GZ ) in a changing ocean is hampered by lack of a global baseline and an understanding of the causes of biogeographic patterns. We address this by using a new global database of GZ records to test hypotheses relating to environmental drivers of biogeographic variation in the multidecadal baseline of epipelagic GZ biomass in the world's oceans. Location Global oceans. Methods Over 476,000 global GZ data and metadata items were assembled from a variety of published and unpublished sources. From this, a total of 91,765 quantitative abundance data items from 1934 to 2011 were converted to carbon biomass using published biometric equations and species‐specific average sizes. Total GZ , Cnidaria, Ctenophora and Chordata (Thaliacea) biomass was mapped into 5° grid cells and environmental drivers of geographic variation were tested using spatial linear models. Results We present JeDI (the J ellyfish D atabase I nitiative), a publically accessible database available at http://jedi.nceas.ucsb.edu . We show that: (1) GZ are present throughout the world's oceans; (2) the global geometric mean and standard deviation of total gelatinous biomass is 0.53 ± 16.16 mg C m −3 , corresponding to a global biomass of 38.3 Tg C in the mixed layer of the ocean; (3) biomass of all gelatinous phyla is greatest in the subtropical and boreal Northern Hemisphere; and (4) within the North Atlantic, dissolved oxygen, apparent oxygen utilization and sea surface temperature are the principal drivers of biomass distribution. Main conclusions JeDI is a unique global dataset of GZ taxa which will provide a benchmark against which future observations can be compared and shifting baselines assessed. The presence of GZ throughout the world's oceans and across the complete global spectrum of environmental variables indicates that evolution has delivered a range of species able to adapt to all available ecological niches.

Mercury Bioaccumulation in the Egyptian Mongoose (Herpestes ichneumon): Geographical, Tissue, Gender and Age Differences - S. Rodrigues; J. P. Coelho; V. Bandeira; T. Barros; A. C. Duarte; C. Fonseca; M. E. Pereira (Water, Air, & Soil Pollution, 2014)

IGF-1 Intranasal Administration Rescues Huntington's Disease Phenotypes in YAC128 Mice - Carla Lopes; Márcio Ribeiro; Ana I. Duarte; Sandrine Humbert; Frederic Saudou; Luís Pereira de Almeida; Michael Hayden; A. Cristina Rego (Molecular Neurobiology, 2014)

Brain glutathione redox system significance for the control of silica-coated magnetite nanoparticles with or without mercury co-exposures mediated oxidative stress in European eel (Anguilla anguilla L.) - Naser A. Anjum; Koigoora Srikanth; Iram Mohmood; Iqbal Sayeed; Tito Trindade; Armando C. Duarte; Eduarda Pereira; Iqbal Ahmad (Environmental Science and Pollution Research, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Oxidative stress status, antioxidant metabolism and polypeptide patterns in Juncus maritimus shoots exhibiting differential mercury burdens in Ria de Aveiro coastal lagoon (Portugal) - Naser A. Anjum; Armando C. Duarte; Eduarda Pereira; Iqbal Ahmad (Environmental Science and Pollution Research, 2014)

Blowflies (Diptera, Calliphoridae) Associated with Pig Carcasses in a Caatinga Area, Northeastern Brazil - A C F Alves; W E Santos; R C A P Farias; A J Creão-Duarte (Neotropical Entomology, 2014)

Removal of phenolic compounds in olive mill wastewater by silica–alginate–fungi biocomposites - K. R. Duarte; C. Justino; T. Panteleitchouk; A. Zrineh; A. C. Freitas; A. C. Duarte; T. A. P. Rocha-Santos (International Journal of Environmental Science and Technology, 2014)

Climatic niche at physiological and macroecological scales: the thermal tolerance–geographical range interface and niche dimensionality - Sidney F. Gouveia; Joaquín Hortal; Miguel Tejedo; Helder Duarte; Fernanda A. S. Cassemiro; Carlos A. Navas; José Alexandre F. Diniz‐Filho (Global Ecology and Biogeography, 2014)
Aim Under the H utchinsonian concept of the realized niche, biotic interactions and dispersal limitation may prevent species from fully occupying areas that they could tolerate physiologically. This can hamper the translation of physiological limits into climatically defined range limits and distorts inferences of evolutionary changes of the adaptive limits (i.e. niche conservatism). In contrast, heritable physiological limits should conform more closely to the position of the niche in the climatic hyperspace. Here, we hypothesize that a measure of niche position in the climatic hyperspace is more reliable than niche boundaries to capture the variability and evolutionary pattern of physiological tolerance. Location N eotropics and P alaeartic. Methods We used phylogenetic and non‐phylogenetic regressions to test the relationships between physiological requirements and macroecological niche features (i.e. based on known species distributions) among anurans. We use larval critical thermal maximum ( CT max ) as a measure of physiological response and maximum temperature ( T max ), temperature variability ( T var ) and the position and breadth of niche in climatic hyperspace as measures of the realized niche in geographical space. We also compare evolutionary rates among these parameters using the phylogenetic signal representation curve. Results CT max is better correlated with niche position ( r 2 = 0.414) than with T var , and CT max is unrelated to either T max or niche breadth. CT max and macroecological niche position also show similar and rapid evolutionary rates, i.e. faster than B rownian motion, whereas T max and T var evolve more slowly and niche breadth evolves at random. Main conclusions The transferability between thermal tolerance and realized climatic niche limits is weak. Only macroecological niche position in the multivariate climatic hyperspace correlates with physiological tolerance. It thus appears to be more suitable for describing the variability and evolutionary pattern of the species' adaptive limits. We link these results to ‘niche dimensionality’, in that multiple interacting factors outweigh single factors in demarcating the species' realized climatic niche, thereby determining the conserved upper thermal limits of the species.

Conspecific cues affect stage-specific molting frequency, survival, and claw morphology of early juvenile stages of the shore crab Carcinus maenas - Rafael C. Duarte; Ana Ré; Augusto A. V. Flores; Henrique Queiroga (Hydrobiologia, 2014)

Climate effects on amphibian distributions depend on phylogenetic resolution and the biogeographical history of taxa - L. D. S. Duarte; C. Both; V. J. Debastiani; M. B. Carlucci; L. O. Gonçalves; L. Cappelatti; G. D. S. Seger; V. A. G. Bastazini; F. T. Brum; E. V. Salengue; J. S. Bernardo‐Silva (Global Ecology and Biogeography, 2014)
Aim Disentangling the effects of climate and historical factors on biodiversity distribution remains a challenge for biogeographers. Here, we provide an analytical framework to discriminate the contributions of contemporary climate and the biogeographical history of taxa to the geographical distributions of phylogenetic lineages. Furthermore, we evaluate the constraint that the biogeographical history of clades exerts on the association between climate and clade distribution, i.e. the historical legacy of climatic effects. As a case study, we analysed the distributions of amphibian lineages across the A mericas. Location The A mericas. Methods We tallied the number of amphibian species per genus in each of 262 ecoregions. Each ecoregion was described by the composition of phylogenetic lineages using phylogenetic fuzzy weighting. The composition of amphibian genera and phylogenetic clades represented the distributions of shallow and deep phylogenetic nodes, respectively. We characterized each ecoregion by the biogeographical history of amphibian taxa and its current climate, whose influences on shallow and deep phylogenetic nodes were analysed using variation partitioning analysis. Results The association between climate and the distributions of deep phylogenetic nodes showed a strong historical legacy, although the distribution of amphibian genera was mostly associated with climate. Hyloidea were associated with a G ondwanan origin and higher annual mean temperatures, whereas other clades (e.g. C audata) were related to a L aurasian origin and higher temperature seasonality. Microhylidae were related to occurrence in the E arly J urassic in G ondwana and recent occurrence in the N eotropics. Main conclusions Biogeographical patterns can be thought of as the net outcome of evolutionary, historical and ecological processes. Although temperature is likely to affect the ecology of amphibians, the effects of climate on the distributions of deep phylogenetic nodes were strongly constrained by the biogeographical history of clades. Nevertheless, local, climatically driven processes are likely to influence the distributions of shallow phylogenetic nodes. The historical biogeography of clades might help to explain the interplay between evolutionary and environmental processes in determining assembly patterns found elsewhere.

Life cycle contributions of copper from vessel painting and maintenance activities - Patrick J. Earley; Brandon L. Swope; Katherine Barbeau; Randelle Bundy; Janessa A. McDonald; Ignacio Rivera-Duarte (Biofouling, 2014)

Environmentally friendly system for the degradation of multipesticide residues in aqueous media by the Fenton’s reaction - Bruno de S. Guimarães; Natiele Kleemann; Sergiane S. Caldas; Fabiane P. Costa; Maria A. K. Silveira; Fabio A. Duarte; Ednei G. Primel (Environmental Science and Pollution Research, 2014)

BbrizAGL6 Is Differentially Expressed During Embryo Sac Formation of Apomictic and Sexual Brachiaria brizantha Plants - Larissa Arrais Guimarães; Diva Maria de A. Dusi; Simona Masiero; Francesca Resentini; Ana Cristina M. M. Gomes; Érica Duarte Silveira; Lilian Hasegawa Florentino; Júlio Carlyle M. Rodrigues; Lucia Colombo; Vera Tavares de C. Carneiro (Plant Molecular Biology Reporter, 2013)

Algistatic effect of a quinonamethide triterpene on Microcystis novacekii - Fernando C. Silva; Fernanda A. F. Guedes; Maione W. Franco; Francisco A. R. Barbosa; Camila A. Marra; Lucienir P. Duarte; Grácia D. F. Silva; Sidney A. Vieira-Filho (Journal of Applied Phycology, 2013)

ECONOMIC RISK ANALYSIS OF TOMATO IRRIGATION USING DESALINATED WATER BY REVERSE OSMOSIS - T. M. Soares; C.D.G.C. Almeida; J. A. Frizzone; E. F. F. Silva; S. N. Duarte (Irrigation and Drainage, 2013)
Groundwater desalination by reverse osmosis is an alternative being used more and more in Brazil, especially in the north‐east region, and aims to provide fresh water in isolated communities. Desalination to produce water for irrigation is a subject on which there has been minimal study. This research evaluated the economic feasibility of desalination for tomato ( Lycopersicon esculentum Mill) irrigation. By the Monte Carlo method, applied to the net present worth (NPW), a probabilistic analysis of risk was accomplished for tomato irrigation using 21 scenarios, comprising different irrigation waters (EC (electrical conductivity) 1, 2, 3, 4, 5 or 6 dS m ‐1 ), desalinated water and three yield levels (100, 70 and 40 Mg ha ‐1 ) obtained under non‐saline water conditions. For each scenario, 5000 values of NPW were simulated, and net present worth expectation, E (NPW), was estimated. Desalination for tomato irrigation is just justified for waters with salinity levels higher than its salinity threshold. Tomato irrigation with desalinated water presents economic feasibility dependent on the yield level which would be reached under non‐saline conditions. Even using water with 6 dS m ‐1 , there was economic feasibility above 75% in desalination for tomato irrigation at all the levels of the designed yield. Copyright © 2013 John Wiley & Sons, Ltd.

Isolation and characterization of rice (Oryza sativa L.) E3-ubiquitin ligase OsHOS1 gene in the modulation of cold stress response - Tiago Lourenço; Helena Sapeta; Duarte D. Figueiredo; Mafalda Rodrigues; André Cordeiro; Isabel A. Abreu; Nelson J. M. Saibo; M. Margarida Oliveira (Plant Molecular Biology, 2013)

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Taxonomic assessment and enzymes production by yeasts isolated from marine and terrestrial Antarctic samples - A. W. F. Duarte; I. Dayo-Owoyemi; F. S. Nobre; F. C. Pagnocca; L. C. S. Chaud; A. Pessoa; M. G. A. Felipe; L. D. Sette (Extremophiles, 2013)

Habitat monitoring and genotoxicity in Ucides cordatus (Crustacea: Ucididae), as tools to manage a mangrove reserve in southeastern Brazil - M. A. A. Pinheiro; L. F. A. Duarte; T. R. Toledo; M. L. Adam; R. A. Torres (Environmental Monitoring and Assessment, 2013)

Mercury bioaccumulation and the population dynamics of Mesopodopsis slabberi (Crustacea: Mysidacea) along a mercury contamination gradient - M. D’Ambrosio; S. C. Marques; U. M. Azeiteiro; M. A. Pardal; E. Pereira; A. C. Duarte; P. G. Cardoso (Ecotoxicology, 2013)

Antibacterial activity of alkaloids produced by endophytic fungus Aspergillus sp. EJC08 isolated from medical plant Bauhinia guianensis - Eduardo Antonio A. Pinheiro; Josiwander Miranda Carvalho; Diellem Cristina P. dos Santos; André de Oliveira Feitosa; Patrícia Santana B. Marinho; Giselle Maria Skelding Pinheiro Guilhon; Afonso Duarte L. de Souza; Felipe Moura A. da Silva; Andrey Moacir do R. Marinho (Natural Product Research, 2013)

The Application of MnO2 in the Removal of Manganese from Acid Mine Water - Alice O. Aguiar; Rute A. Duarte; Ana Claudia Q. Ladeira (Water, Air, & Soil Pollution, 2013)

Nitrate reductase is required for the transcriptional modulation and bactericidal activity of nitric oxide during the defense response of Arabidopsis thaliana against Pseudomonas syringae - Simone C. Vitor; Gustavo T. Duarte; Elzira E. Saviani; Michel G. A. Vincentz; Halley C. Oliveira; Ione Salgado (Planta, 2013)

Long-distance lava correlation in the Paraná volcanic province along the Serra Geral cuesta, southeastern Brazil - L. A. Hartmann; K. R. Arena; S. K. Duarte; J. Pertille (International Journal of Earth Sciences, 2013)

Low-pH Freshwater Discharges Drive Spatial and Temporal Variations in Life History Traits of Neritic Copepod Acartia tonsa - Victor M. Aguilera; Cristian A. Vargas; Patricio H. Manríquez; Jorge M. Navarro; Cristian Duarte (Estuaries and Coasts, 2013)

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Decomposition and nutrient release in leaves of Atlantic Rainforest tree species used in agroforestry systems - Edivânia M. G. Duarte; Irene M. Cardoso; Thomas Stijnen; Maria Alice F. C. Mendonça; Marino S. Coelho; Reinaldo B. Cantarutti; Thomas W. Kuyper; Ecila M. A. Villani; Eduardo S. Mendonça (Agroforestry Systems, 2013)

Valuation of Unmodified Rice Husk Waste as an Eco-Friendly Sorbent to Remove Mercury: a Study Using Environmental Realistic Concentrations - Luciana S. Rocha; Cláudia B. Lopes; J. A. Borges; A. C. Duarte; E. Pereira (Water, Air, & Soil Pollution, 2013)

OsRMC, a negative regulator of salt stress response in rice, is regulated by two AP2/ERF transcription factors - Tânia S. Serra; Duarte D. Figueiredo; André M. Cordeiro; Diego M. Almeida; Tiago Lourenço; Isabel A. Abreu; Alvaro Sebastián; Lisete Fernandes; Bruno Contreras-Moreira; M. Margarida Oliveira; Nelson J. M. Saibo (Plant Molecular Biology, 2013)

Erratum to: NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina R. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina C. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

Phenological development stages variation versus mercury tolerance, accumulation, and allocation in salt marsh macrophytes Triglochin maritima and Scirpus maritimus prevalent in Ria de Aveiro coastal lagoon (Portugal) - Naser A. Anjum; Iqbal Ahmad; Mónica Válega; Etelvina Figueira; Armando C. Duarte; Eduarda Pereira (Environmental Science and Pollution Research, 2013)

A new species of Caryospora Léger, 1904 (Apicomplexa: Eimeriidae) from the snake Philodryas olfersii Lichtenstein (Colubridae) from a coastal habitat in Brazil - Lúcio A. Viana; Gisele R. Winck; Cleide D. Coelho; Walter Flausino; Carlos F. Duarte Rocha (Systematic Parasitology, 2013)

Species‐specific ontogenetic diet shifts among Neotropical Crenicichla : using stable isotopes and tissue stoichiometry - E. D. Burress; A. Duarte; W. S. Serra; M. M. Gangloff; L. Siefferman (Journal of Fish Biology, 2013)
Ontogenetic diet shifts were compared among five sympatric pike cichlids Crenicichla in a subtropical South American stream using stable C and N isotopes and tissue stoichiometry (C:N). Within species, stable N isotopes were positively related to body size while C:N showed negative relationships. Stable C isotopes, however, were not related to body size in any species. By modelling the switch to piscivory using gut content‐isotope‐body size relationships, diet shifts were shown to be species‐specific with regard to both rate and degree of piscivory. Compared to other piscivorous lineages, Crenicichla appear to be unusually small‐bodied (based on maximum body size). Because of their diversity, abundance and dynamic size‐structured functional roles, Crenicichla may exert broad and complex predation pressures on the aquatic community.

Anxiogenic-like profile of Wistar adult rats based on the pilocarpine model: an animal model for trait anxiety? - Filipe S. Duarte; Marcelo Duzzioni; Alexandre A. Hoeller; Nayana M. Silva; Andy L. Ern; Tetsade C. Piermartiri; Carla I. Tasca; Elaine C. Gavioli; Tadeu Lemos; Antonio P. Carobrez; Thereza C. M. De Lima (Psychopharmacology, 2013)

Propolis volatiles characterisation from acaricide-treated and -untreated beehives maintained at Algarve (Portugal) - Maria G. Miguel; Susana Nunes; Cláudia Cruz; João Duarte; Maria D. Antunes; Ana M. Cavaco; Marta D. Mendes; A. Sofia Lima; Luis G. Pedro; José G. Barroso; A. Cristina Figueiredo (Natural Product Research, 2013)

Glutathione and its dependent enzymes’ modulatory responses to toxic metals and metalloids in fish—a review - K. Srikanth; E. Pereira; A. C. Duarte; I. Ahmad (Environmental Science and Pollution Research, 2013)

Is Ocean Acidification an Open-Ocean Syndrome? Understanding Anthropogenic Impacts on Seawater pH - Carlos M. Duarte; Iris E. Hendriks; Tommy S. Moore; Ylva S. Olsen; Alexandra Steckbauer; Laura Ramajo; Jacob Carstensen; Julie A. Trotter; Malcolm McCulloch (Estuaries and Coasts, 2013)

Major inputs and mobility of potentially toxic elements contamination in urban areas - A. Cachada; A. C. Dias; P. Pato; C. Mieiro; T. Rocha-Santos; M. E. Pereira; E. Ferreira da Silva; A. C. Duarte (Environmental Monitoring and Assessment, 2013)

Eriophorum angustifolium and Lolium perenne metabolic adaptations to metals- and metalloids-induced anomalies in the vicinity of a chemical industrial complex - Naser A. Anjum; Iqbal Ahmad; Sónia M. Rodrigues; Bruno Henriques; Nuno Cruz; Cláudia Coelho; Mário Pacheco; Armando C. Duarte; Eduarda Pereira (Environmental Science and Pollution Research, 2013)

Derivation of soil to plant transfer functions for metals and metalloids: impact of contaminant’s availability - S. M. Rodrigues; E. Pereira; A. C. Duarte; P. F. A. M. Römkens (Plant and Soil, 2012)

Pesticide application to agricultural fields: effects on the reproduction and avoidance behaviour of Folsomia candida and Eisenia andrei - M. J. G. Santos; M. F. L. Ferreira; A. Cachada; A. C. Duarte; J. P. Sousa (Ecotoxicology, 2012)

Mercury-Induced Chromosomal Damage in Wild Fish (Dicentrarchus labrax L.) Reflecting Aquatic Contamination in Contrasting Seasons - Iram Mohmood; Cláudia Leopoldina Mieiro; João P. Coelho; Naser A. Anjum; Iqbal Ahmad; Eduarda Pereira; Armando Costa Duarte; Mário Pacheco (Archives of Environmental Contamination and Toxicology, 2012)

Saccharomyces bacillaris is not a synonym of Candida stellata: reinstatement as Starmerella bacillaris comb. nov. - F. L. Duarte; N. H. Pimentel; A. Teixeira; Á. Fonseca (Antonie van Leeuwenhoek, 2012)

Treatment of Olive Oil Mill Wastewater by Silica–Alginate–Fungi Biocomposites - Kátia R. Duarte; Ana C. Freitas; Ruth Pereira; Jorge C. Pinheiro; Fernando Gonçalves; H. Azaari; Mohammed El Azzouzi; Abdallah Zrineh; Souad Zaydoun; Armando C. Duarte; Teresa A. P. Rocha-Santos (Water, Air, & Soil Pollution, 2012)

Range expansion of nonindigenous caribou in the Aleutian archipelago of Alaska - Mark A. Ricca; Floyd W. Weckerly; Adam Duarte; Jeffrey C. Williams (Biological Invasions, 2012)

Net primary productivity, upwelling and coastal currents in the Gulf of Ulloa, Baja California, México - E. González-Rodríguez; A. Trasviña-Castro; G. Gaxiola-Castro; L. Zamudio; R. Cervantes-Duarte (Ocean Science, 2012)
The Gulf of Ulloa, a highly productive area off the western coast of the Baja California Peninsula, is examined for five successive years (2003–2007) by using satellite data and seasonal net primary productivity (NPP) estimates obtained from a vertical generalised production model. The results identify that northwestern winds blow parallel to the coast throughout the year. However, highest NPP occurs from March to June. During this period, an equatorward coastal current transports water from neighbouring upwelling areas to the northern Gulf of Ulloa and in combination with local upwelling, which injects nutrients into the euphotic zone, produce the observed increase in NPP. The opposite situation occurs in late summer when a warm poleward current of tropical characteristics arrives and inhibits the productivity in the whole region and generates the yearly lowest NPP levels. Our findings reveal the importance of lateral advection in the modulation of the primary productivity in this subtropical upwelling region.

Screening of antimicrobial activity of Cistus ladanifer and Arbutus unedo extracts - S. Ferreira; J. Santos; A. Duarte; A.P. Duarte; J.A. Queiroz; F.C. Domingues (Natural Product Research, 2012)

Salt marsh macrophyte Phragmites australis strategies assessment for its dominance in mercury-contaminated coastal lagoon (Ria de Aveiro, Portugal) - Naser A. Anjum; Iqbal Ahmad; Mónica Válega; Mário Pacheco; Etelvina Figueira; Armando C. Duarte; Eduarda Pereira (Environmental Science and Pollution Research, 2012)

IL-1ra anti-inflammatory cytokine polymorphism is associated with risk of gastric cancer and chronic gastritis in a Brazilian population, but the TNF-β pro-inflammatory cytokine is not - J. Garcia Oliveira; M. Cristina Duarte; A. Elizabete Silva (Molecular Biology Reports, 2012)

Evaluation of Species-Specific Dissimilarities in Two Marine Fish Species: Mercury Accumulation as a Function of Metal Levels in Consumed Prey - C. L. Mieiro; J. P. Coelho; M. Pacheco; A. C. Duarte; M. E. Pereira (Archives of Environmental Contamination and Toxicology, 2012)

Persistence of uropathogenic Escherichia coli strains in the host for long periods of time: relationship between phylogenetic groups and virulence factors - A. Narciso; F. Nunes; T. Amores; L. Lito; J. Melo-Cristino; A. Duarte (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

First histological and virological report of fibropapilloma associated with herpesvirus in Chelonia mydas at Príncipe Island, West Africa - A. Duarte; P. Faísca; N. S. Loureiro; R. Rosado; S. Gil; N. Pereira; L. Tavares (Archives of Virology, 2012)

BMPRIB and BMPRII mRNA expression levels in goat ovarian follicles and the in vitro effects of BMP-15 on preantral follicle development - Isadora Machado T. Lima; Ivina R. Brito; Rafael Rossetto; Ana Beatriz G. Duarte; Giovanna Q. Rodrigues; Márcia Viviane A. Saraiva; José Jackson N. Costa; Mariana Aragão M. Donato; Christina A. Peixoto; José Roberto V. Silva; José Ricardo de Figueiredo; Ana Paula R. Rodrigues (Cell and Tissue Research, 2012)

Synergistic control of CO2 emissions by fish and nutrients in a humic tropical lake - Humberto Marotta; Carlos M. Duarte; Breno A. Guimarães-Souza; Alex Enrich-Prast (Oecologia, 2012)

Hg transfer from contaminated soils to plants and animals - S. M. Rodrigues; B. Henriques; A. T. Reis; A. C. Duarte; E. Pereira; P. F. A. M. Römkens (Environmental Chemistry Letters, 2012)

Olive oil mill wastewaters before and after treatment: a critical review from the ecotoxicological point of view - Celine I. L. Justino; Ruth Pereira; Ana C. Freitas; Teresa A. P. Rocha-Santos; Teresa S. L. Panteleitchouk; Armando C. Duarte (Ecotoxicology, 2012)

The field resistance of potato cultivars to foliar late blight and its relationship with foliage maturity type and skin type in Brazil - H. S. S. Duarte; L. Zambolim; E. S. G. Mizubuti; J. G. Pádua; J. I. Ribeiro Júnior; E. L. Carmo; A. F. Nogueira Júnior (Australasian Plant Pathology, 2012)

Kinetics of Mercury Bioaccumulation in the Polychaete Hediste diversicolor and in the Bivalve Scrobicularia plana, Through a Dietary Exposure Pathway - Patricia G. Cardoso; Eduarda Pereira; Tiago F. Grilo; Armando C. Duarte; Miguel A. Pardal (Water, Air, & Soil Pollution, 2012)

Differential Sex, Morphotype and Tissue Accumulation of Mercury in the Crab Carcinus maenas - Sónia Costa; Ivan Viegas; Eduarda Pereira; Armando C. Duarte; Carlos M. Palmeira; Miguel A. Pardal (Water, Air, & Soil Pollution, 2011)

Impact of Seasonal Fluctuations on the Sediment-Mercury, its Accumulation and Partitioning in Halimione portulacoides and Juncus maritimus Collected from Ria de Aveiro Coastal Lagoon (Portugal) - Naser A. Anjum; Iqbal Ahmad; Mónica Válega; Mário Pacheco; Etelvina Figueira; Armando C. Duarte; Eduarda Pereira (Water, Air, & Soil Pollution, 2011)

Vascular endothelial growth factor-A165 (VEGF-A165) stimulates the in vitro development and oocyte competence of goat preantral follicles - V. R. Araújo; G. M. Silva; A. B. G. Duarte; D. M. Magalhães; A. P. Almeida; R. F. B. Gonçalves; J. B. Bruno; T. F. P. Silva; C. C. Campello; A. P. R. Rodrigues; J. R. Figueiredo (Cell and Tissue Research, 2011)

A behavioral mechanism for dispersal in fiddler crab larvae (genus Uca ) varies with adult habitat, not phylogeny - Paola C. López-Duarte; John H. Christy; Richard A. Tankersley (Limnology and Oceanography, 2011)
The genus Uca (fiddler crabs) includes both estuarine and coastal species, the zoeae of which must travel varying distances to reach the sea. Rapid seaward transport following hatching may be facilitated by tidal currents through an ebb‐phased circatidal rhythm in vertical swimming by larvae. Assuming there is a cost to vertical swimming, we predicted that endogenous swimming rhythms would be stronger in zoeae of species that live far up estuaries (oligohaline and mesohaline areas) and weaker or absent in coastal species and that adult ecology, not phylogeny, would best explain interspecific variation in vertical swimming rhythms. Both predictions were confirmed. Ovigerous females of 15 Uca species in 4 subgenera were collected from 10 locations along the Atlantic and Gulf Coasts of the United States and the Pacific and Caribbean coasts of Panama. Swimming activity of zoeae‐1 larvae was recorded under constant conditions for 72 h. Regardless of subgenus, estuarine species exhibited ebb‐phased circatidal swimming rhythms that persisted for several cycles and matched the tidal patterns at the collection sites, while the swimming of coastal species was arrhythmic. Species‐specific differences in the proximity of adult habitats and hatching areas to the sea accounted for differences in larval behavior that promotes seaward transport. Vertical swimming rhythms of larvae may have evolved together with other traits that permit estuarine living.

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Dinucleotide microsatellite markers in the genus Caulerpa - Elena Varela-Álvarez; Travis C. Glenn; Ester A. Serrão; Carlos M. Duarte; Beatriz Martínez-Daranas; Myriam Valero; Núria Marbá (Journal of Applied Phycology, 2011)

Steady-state level of epidermal growth factor (EGF) mRNA and effect of EGF on in vitro culture of caprine preantral follicles - Juliana Jales H. Celestino; Jamily B. Bruno; Márcia Viviane A. Saraiva; Rebeca M. P. Rocha; Ivina R. Brito; Ana Beatriz G. Duarte; Valdevane R. Araújo; Cleidson M. G. Silva; Maria Helena T. Matos; Claudio C. Campello; José Roberto V. Silva; José Ricardo Figueiredo (Cell and Tissue Research, 2011)

The small nuclear ribonucleoprotein U1A interacts with NS5 from yellow fever virus - Roberta V. M. Bronzoni; Maria C. F. S. Madrid; Danilo V. B. Duarte; Vanessa O. A. Pellegrini; Carolina C. Pacca; Ana C. V. Carmo; Cleslei F. Zanelli; Sandro R. Valentini; Carolina Santacruz-Pérez; João A. R. G. Barbosa; Carol S. Lutz; Paula Rahal; et al. (Archives of Virology, 2011)

Kinetics of Mercury Accumulation and Its Effects on Ulva lactuca Growth Rate at Two Salinities and Exposure Conditions - Sónia Costa; Daniel Crespo; Bruno M. G. Henriques; Eduarda Pereira; Armando C. Duarte; Miguel A. Pardal (Water, Air, & Soil Pollution, 2011)

Evaluation of the Sub-lethal Toxicity of Bleached Kraft Pulp Mill Effluent to Carassius auratus and Dicentrarchus labrax - Mário S. Diniz; Ruth Pereira; Ana C. Freitas; Teresa A. P. Rocha-Santos; Luisa Castro; Isabel Peres; Armando C. Duarte (Water, Air, & Soil Pollution, 2011)

Stable isotope and mineralogical investigation of the genesis of amethyst geodes in the Los Catalanes gemological district, Uruguay, southernmost Paraná volcanic province - Lauren C. Duarte; Leo A. Hartmann; Luiz H. Ronchi; Zsolt Berner; Thomas Theye; Hans J. Massonne (Mineralium Deposita, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Assessment of Mercury in Water, Sediments and Biota of a Southern European Estuary (Sado Estuary, Portugal) - Ana I. Lillebø; Pedro J. Coelho; Pedro Pato; Mónica Válega; Rui Margalho; Mário Reis; José Raposo; Eduarda Pereira; Armando C. Duarte; Miguel A. Pardal (Water, Air, & Soil Pollution, 2011)

The impact of ice melting on bacterioplankton in the Arctic Ocean - Maria Montserrat Sala; Jesús M. Arrieta; Julia A. Boras; Carlos M. Duarte; Dolors Vaqué (Polar Biology, 2010)

Effect of ice melting on bacterial carbon fluxes channelled by viruses and protists in the Arctic Ocean - Julia A. Boras; M. Montserrat Sala; Jesus M. Arrieta; Elisabet L. Sà; Jorge Felipe; Susana Agustí; Carlos M. Duarte; Dolors Vaqué (Polar Biology, 2010)

The role of arctic zooplankton in biogeochemical cycles: respiration and excretion of ammonia and phosphate during summer - M. Alcaraz; R. Almeda; A. Calbet; E. Saiz; C. M. Duarte; S. Lasternas; S. Agustí; R. Santiago; J. Movilla; A. Alonso (Polar Biology, 2010)

Mycotoxin food and feed regulation and the specific case of ochratoxin A: a review of the worldwide status - S.C. Duarte; C.M. Lino; A. Pena (Food Additives & Contaminants: Part A, 2010)

Are Great Tits (Parus major) Inhabiting the Vicinity of a Pulp Mill Healthy? Impacts on Physiology and Breeding Performance - Ana Cláudia Norte; B. C. Sheldon; J. P. Sousa; P. C. Tavares; M. E. Pereira; A. C. Duarte; J. A. Ramos (Archives of Environmental Contamination and Toxicology, 2010)

Antioxidant system breakdown in brain of feral golden grey mullet (Liza aurata) as an effect of mercury exposure - C. L. Mieiro; I. Ahmad; M. E. Pereira; A. C. Duarte; M. Pacheco (Ecotoxicology, 2010)

Comparative Analysis of Stability—Genetic Diversity in Seagrass (Posidonia oceanica) Meadows Yields Unexpected Results - Sophie Arnaud-Haond; Núria Marbà; Elena Diaz-Almela; Ester A. Serrão; Carlos M. Duarte (Estuaries and Coasts, 2010)

The metal-binding properties of the blue crab copper specific CuMT-2: a crustacean metallothionein with two cysteine triplets - Montserrat Serra-Batiste; Neus Cols; Luis A. Alcaraz; Antonio Donaire; Pilar González-Duarte; Milan Vašák (JBIC Journal of Biological Inorganic Chemistry, 2010)

Evolution of fluid geochemistry at the Turrialba volcano (Costa Rica) from 1998 to 2008 - O. Vaselli; Franco Tassi; E. Duarte; E. Fernandez; R. J. Poreda; A. Delgado Huertas (Bulletin of Volcanology, 2010)

Long-Term CO2 Variability in Two Shallow Tropical Lakes Experiencing Episodic Eutrophication and Acidification Events - Humberto Marotta; Carlos M. Duarte; Frederico Meirelles-Pereira; Luiz Bento; Francisco A. Esteves; Alex Enrich-Prast (Ecosystems, 2010)

Conformational studies of peptides representing a segment of TM7 from H+-VO-ATPase in SDS micelles - Afonso M. S. Duarte; Edwin R. de Jong; Rob B. M. Koehorst; Marcus A. Hemminga (European Biophysics Journal, 2010)

Effect of viruses and protists on bacteria in eddies of the Canary Current region (subtropical northeast Atlantic) - Julia A. Boras; M. Montserrat Sala; Federico Baltar; Javier Arístegui; Carlos M. Duarte; Dolors Vaqué (Limnology and Oceanography, 2010)
The effect of oceanic eddies on microbial processes, with emphasis on bacterial losses due to protists and phages, was examined in the Canary Current region (subtropical northeast Atlantic) through the water column (down to 1000 m) during August 2006. Sampling stations were located in cyclonic and anticyclonic eddies, as well as in regions situated outside the influence of the eddy field (far‐field stations). In the euphotic zone, in cyclonic eddies losses of bacteria due to viruses and protists were from 25.6% to 69.8%, and from not detected to 46.8% of bacterial production (BP) d −1 , respectively. In anticyclonic eddies, these values ranged from 20.6% to 90.2% of BP d −1 for viruses, and from 8.0% to 79.4% of BP d −1 for protists. At far‐field stations, losses of bacteria ranged from 48.7% to 66.9% for viruses, and from not detected to 44.8% for protists. In addition, covering all stations and depths (from the epipelagic to the bathypelagic layer), bacterial losses due to viruses were significantly higher than losses by protists, and did not differ significantly among depths except for the stations situated in anticyclonic eddies, where they were significantly higher in the epipelagic layer. Lysogenic infection was more frequent at anticyclonic stations, where the highest pressure of protists on bacteria was observed. Because of the importance of viral activity, we suggest that lysis products from bacteria may be a source of regenerated nutrients in the surface of the oligotrophic ocean, in addition to the input of nutrients upwelled by eddies.

Genetic structure in the Mediterranean seagrass Posidonia oceanica : disentangling past vicariance events from contemporary patterns of gene flow - I. A. SERRA; A. M. INNOCENTI; G. DI MAIDA; S. CALVO; M. MIGLIACCIO; E. ZAMBIANCHI; C. PIZZIGALLI; S. ARNAUD-HAOND; C. M. DUARTE; E. A. SERRAO; G. PROCACCINI (Molecular Ecology, 2010)

Effects of sulfated polysaccharide and alcoholic extracts from green seaweed Ulva fasciata on anthracnose severity and growth of common bean (Phaseolus vulgaris L.) - R. Paulert; V. Talamini; J. E. F. Cassolato; M. E. R. Duarte; M. D. Noseda; A. Smania; M. J. Stadnik (Journal of Plant Diseases and Protection, 2009)

What is the impact of wind farms on birds? A case study in southern Spain - M. A. Farfán; J. M. Vargas; J. Duarte; R. Real (Biodiversity and Conservation, 2009)

Effects of ECF-Kraft pulp mill effluent treated with fungi (Rhizopus oryzae) on reproductive steroids and liver CYP1A of exposed goldfish (Carassius auratus) - M. S. Diniz; I. Peres; L. Castro; A. C. Freitas; T. A. P. Rocha-Santos; P. M. Costa; R. Pereira; A. C. Duarte (Ecotoxicology, 2009)

Ochratoxin A exposure assessment of the inhabitants of Lisbon during winter 2007/2008 through bread and urine analysis - S.C. Duarte; J.M.V. Bento; A. Pena; C.M. Lino (Food Additives & Contaminants: Part A, 2009)

Identification of up-regulated genes in flag leaves during rice grain filling and characterization of OsNAC5, a new ABA-dependent transcription factor - Raul A. Sperotto; Felipe K. Ricachenevsky; Guilherme L. Duarte; Tatiana Boff; Karina L. Lopes; Edilena R. Sperb; Michael A. Grusak; Janette Palma Fett (Planta, 2009)

Mercury pollution in Ria de Aveiro (Portugal): a review of the system assessment - M. E. Pereira; A. I. Lillebø; P. Pato; M. Válega; J. P. Coelho; C. B. Lopes; S. Rodrigues; A. Cachada; M. Otero; M. A. Pardal; A. C. Duarte (Environmental Monitoring and Assessment, 2009)

Spatial Variability of Trace Metals and Inorganic Nutrients in Surface Waters of Todos Santos Bay, México in the Summer of 2005 During a Red Tide Algal Bloom - M. L. Lares; S. G. Marinone; I. Rivera-Duarte; A. Beck; S. Sañudo-Wilhelmy (Archives of Environmental Contamination and Toxicology, 2009)

Lap4, a vacuolar aminopeptidase I, is involved in cadmium-glutathione metabolism - Paula D. B. Adamis; Sergio C. Mannarino; Cristiano J. Riger; Giselle Duarte; Ana Cruz; Marcos D. Pereira; Elis C. A. Eleutherio (BioMetals, 2009)

Fraction images derived from Terra Modis data for mapping burnt areas in Brazilian Amazonia - Y. E. Shimabukuro; V. Duarte; E. Arai; R. M. Freitas; A. Lima; D. M. Valeriano; I. F. Brown; M. L. R. Maldonado (International Journal of Remote Sensing, 2009)

Rejoinder to: Influence of river discharge in the tropical and subtropical North Atlantic Ocean - Antonio Tovar-Sanchez; Carlos M. Duarte; Adam B. Kustka; Susana Agustí; Jordi Dachs; David A. Hutchins; Douglas G. Capone; Sergio A. Sañudo-Wilhelmy (Limnology and Oceanography, 2009)

Characteristics and economic contribution of a developing recreational fishery in southern Angola - W. M. POTTS; A.‐R. CHILDS; W. H. H. SAUER; A. D. C. DUARTE (Fisheries Management and Ecology, 2009)
The characteristics and contribution of a developing recreational fishery to the local, regional and national economy of Angola were evaluated in 2006. Annual angling effort was 13 435 h, while the estimated total catch of the three target species [leerfish, Lichia amia (L.), west coast dusky kob, Argyrosomus coronus (Griffiths & Heemstra) and shad, Pomatomus saltatrix (L.)], was 5913 fish with a mass of 27 975 kg. Catch per unit effort (CPUE) for all teleost species combined was 0.44 fish per angler h −1 and 2.08 kg per angler h −1 . Total harvest of the three species was 576 fish with a total mass of 2221.6 kg. The total contribution of this recreational fishery (mostly anglers from South Africa) to the local economy was US$ 1007 per harvested fish and US$ 243 per harvested kg. This equated to a contribution to the local, regional and national economies of US$ 151 685, US$ 44 767 and US$ 344 364 respectively. Although the regional contribution was less than half of the national contribution, it was regionally significant when the low population density and the general absence of other formal sector employment opportunities are considered. As a result of the largely undisturbed nature of the southern Angolan coastline, the catch, effort and CPUE information was considered suitable as a baseline for a cost‐effective method of future fisheries monitoring in the region.

Foliar application of potassium silicate reduces the intensity of soybean rust - F. A. Rodrigues; H. S. S. Duarte; G. P. Domiciano; C. A. Souza; G. H. Korndörfer; L. Zambolim (Australasian Plant Pathology, 2009)

Environmental processes, water quality degradation, and decline of waterbird populations in the Rio Cruces wetland, Chile - Nelson A. Lagos; Pedro Paolini; Eduardo Jaramillo; Charlotte Lovengreen; Cristian Duarte; Heraldo Contreras (Wetlands, 2008)

Effect of hydrogen peroxide on secretory response, calcium mobilisation and caspase-3 activity in the isolated rat parotid gland - António Mata; Duarte Marques; María A. Martínez-Burgos; João Silveira; Joana Marques; Maria F. Mesquita; José A. Pariente; Gines M. Salido; Jaipaul Singh (Molecular and Cellular Biochemistry, 2008)

Metabolic activity interferometer: description and calibration of an interferometric method to measure growth of mycobacteria - R. R. P. Machado; E. S. Lima Filho; D. F. Jardim; M. A. A. Ferreira; C. G. de Faria; R. S. Duarte; B. Lesche (European Biophysics Journal, 2008)

Trophic Transfers from Seagrass Meadows Subsidize Diverse Marine and Terrestrial Consumers - Kenneth L. Heck; Tim J. B. Carruthers; Carlos M. Duarte; A. Randall Hughes; Gary Kendrick; Robert J. Orth; Susan W. Williams (Ecosystems, 2008)

Biogeochemical modelling of Ria Formosa (South Portugal) - P. Duarte; B. Azevedo; M. Guerreiro; C. Ribeiro; R. Bandeira; A. Pereira; M. Falcão; D. Serpa; J. Reia (Hydrobiologia, 2008)

The Influence of Diet on Mercury Intake by Little Tern Chicks - Vitor H. Paiva; Paula C. Tavares; Jaime A. Ramos; Eduarda Pereira; Sandra Antunes; Armando C. Duarte (Archives of Environmental Contamination and Toxicology, 2008)

Genetic differentiation and secondary contact zone in the seagrass Cymodocea nodosa across the Mediterranean–Atlantic transition region - Filipe Alberto; Sónia Massa; Pablo Manent; Elena Diaz‐Almela; Sophie Arnaud‐Haond; Carlos M. Duarte; Ester A. Serrão (Journal of Biogeography, 2008)
Aim A central question in evolutionary ecology is the nature of environmental barriers that can limit gene flow and induce population genetic divergence, a first step towards speciation. Here we study the geographical barrier constituted by the transition zone between the Atlantic Ocean and the Mediterranean Sea, using as our model Cymodocea nodosa , a seagrass distributed throughout the Mediterranean and in the Atlantic, from central Portugal to Mauritania. We also test predictions about the genetic footprints of Pleistocene glaciations. Location The Atlantic–Mediterranean transition region and adjacent areas in the Atlantic (Mauritania to south‐west Portugal) and the Mediterranean. Methods We used eight microsatellite markers to compare 20 seagrass meadows in the Atlantic and 27 meadows in the Mediterranean, focusing on the transition between these basins. Results Populations from these two regions form coherent groups containing several unique, high‐frequency alleles for the Atlantic and for the Mediterranean, with some admixture west of the Almeria–Oran Front (Portugal, south‐west Spain and Morocco). These are populations where only one or a few genotypes were found, for all but Cadiz, but remarkably still show the footprint of a contact zone. This extremely low genotypic richness at the Atlantic northern edge contrasts with the high values (low clonality) at the Atlantic southern edge and in most of the Mediterranean. The most divergent populations are those at the higher temperature range limits: the southernmost Atlantic populations and the easternmost Mediterranean, both potential footprints of vicariance. Main conclusions A biogeographical transition region occurs close to the Almeria–Oran front. A secondary contact zone in Atlantic Iberia and Morocco results from two distinct dispersal sources: the Mediterranean and southernmost Atlantic populations, possibly during warmer interglacial or post‐glacial periods. The presence of high‐frequency diagnostic alleles in present‐day disjunct populations from the southernmost Atlantic region indicates that their separation from all remaining populations is ancient, and suggests an old, stable rear edge.

Evaluation of the microbial diversity in a horizontal-flow anaerobic immobilized biomass reactor treating linear alkylbenzene sulfonate - I. C. S. Duarte; L. L. Oliveira; N. K. D. Saavedra; F. Fantinatti-Garboggini; V. M. Oliveira; M. B. A. Varesche (Biodegradation, 2008)

First assessment of microbial diversity in faecal microflora of Eurasian otter (Lutra lutra Linnaeus, 1758) in Portugal - M. Oliveira; T. Sales-Luís; A. Duarte; S. F. Nunes; C. Carneiro; T. Tenreiro; R. Tenreiro; M. Santos-Reis; L. Tavares; C. L. Vilela (European Journal of Wildlife Research, 2008)

Evaluation of tests to assess the quality of mine-contaminated soils - P. Alvarenga; P. Palma; A. P. Gonçalves; R. M. Fernandes; A. de Varennes; G. Vallini; E. Duarte; A. C. Cunha-Queda (Environmental Geochemistry and Health, 2008)

Sardine early survival, physical condition and stress after introduction to captivity - A. Marçalo; P. Pousão‐Ferreira; L. Mateus; J. H. Duarte Correia; Y. Stratoudakis (Journal of Fish Biology, 2008)
The main factors that affect early survival, physical damage and stress reactions of sardine Sardina pilchardus after live capture and introduction to captivity were examined. A total of 2800 sardines were captured alive from commercial purse seiners in five trials off southern Portugal and monitored for 4 weeks in aquaculture tanks. Survival rates varied considerably between trials (from 80% after a month), with most deaths occurring in the first 5 days. Sardine early survival was affected by factors related to conditions at sea (catch composition, sea temperature and transportation density), during introduction to captivity (magnitude of thermal shock, land transportation duration and use of antibacterial treatment) and, possibly, their interaction. Physical damage was related to the probability of dying, with fish that died during the first week showing significantly higher scale loss and larger caudal fin erosion that those that were alive in the same period. For all stress variables measured (blood haematocrit, cortisol, glucose and ions in the plasma), the most extreme values were attained during introduction to captivity or in the first hours after. After 2 weeks in captivity, most variables had returned to levels close to those observed at the onset of purse‐seine fishing, suggesting that maintenance conditions were adequate to permit a rapid recovery from fishing and transport stress.

Intra-genotypic resolution of African swine fever viruses from an East African domestic pig cycle: a combined p72-CVR approach - Baratang A. Lubisi; Armanda Duarte Slager Bastos; Rahana M. Dwarka; Wilna Vosloo (Virus Genes, 2007)

Standardizing methods to address clonality in population studies - S. ARNAUD‐HAOND; C. M. DUARTE; F. ALBERTO; E. A. SERRÃO (Molecular Ecology, 2007)
Although clonal species are dominant in many habitats, from unicellular organisms to plants and animals, ecological and particularly evolutionary studies on clonal species have been strongly limited by the difficulty in assessing the number, size and longevity of genetic individuals within a population. The development of molecular markers has allowed progress in this area, and although allozymes remain of limited use due to their typically low level of polymorphism, more polymorphic markers have been discovered during the last decades, supplying powerful tools to overcome the problem of clonality assessment. However, population genetics studies on clonal organisms lack a standardized framework to assess clonality, and to adapt conventional data analyses to account for the potential bias due to the possible replication of the same individuals in the sampling. Moreover, existing studies used a variety of indices to describe clonal diversity and structure such that comparison among studies is difficult at best. We emphasize the need for standardizing studies on clonal organisms, and particularly on clonal plants, in order to clarify the way clonality is taken into account in sampling designs and data analysis, and to allow further comparison of results reported in distinct studies. In order to provide a first step towards a standardized framework to address clonality in population studies, we review, on the basis of a thorough revision of the literature on population structure of clonal plants and of a complementary revision on other clonal organisms, the indices and statistics used so far to estimate genotypic or clonal diversity and to describe clonal structure in plants. We examine their advantages and weaknesses as well as various conceptual issues associated with statistical analyses of population genetics data on clonal organisms. We do so by testing them on results from simulations, as well as on two empirical data sets of microsatellites of the seagrasses Posidonia oceanica and Cymodocea nodosa . Finally, we also propose a selection of new indices and methods to estimate clonal diversity and describe clonal structure in a way that should facilitate comparison between future studies on clonal plants, most of which may be of interest for clonal organisms in general.

Magnesium–calcium signalling in rat parotid acinar cells: effects of acetylcholine - Antonio Mata; Duarte Marques; María A. Martínez-Burgos; João Silveira; Joana Marques; Maria F. Mesquita; José A. Pariente; Gines M. Salido; Jaipaul Singh (Molecular and Cellular Biochemistry, 2007)

Effects of receptor density on Nociceptin/OrphaninFQ peptide receptor desensitisation: studies using the ecdysone inducible expression system - T. A. Barnes; J. McDonald; D. J. Rowbotham; T. L. Duarte; D. G. Lambert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Feed-backs between genetic structure and perturbation-driven decline in seagrass (Posidonia oceanica) meadows - Elena Diaz-Almela; Sophie Arnaud-Haond; Mirjam S. Vliet; Elvira Álvarez; Núria Marbà; Carlos M. Duarte; Ester A. Serrão (Conservation Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Circatidal swimming behavior of brachyuran crab zoea larvae: implications for ebb-tide transport - Paola C. López-Duarte; Richard A. Tankersley (Marine Biology, 2007)

Vicariance patterns in the Mediterranean Sea: east–west cleavage and low dispersal in the endemic seagrass Posidonia oceanica - Sophie Arnaud‐Haond; Marianna Migliaccio; Elena Diaz‐Almela; Sara Teixeira; Mirjiam Susanne Van De Vliet; Filipe Alberto; Gabriele Procaccini; Carlos M. Duarte; Ester A. Serrão (Journal of Biogeography, 2007)
Aim The seagrass, Posidonia oceanica is a clonal angiosperm endemic to the Mediterranean Sea. Previous studies have suggested that clonal growth is far greater than sexual recruitment and thus leads to low clonal diversity within meadows. However, recently developed microsatellite markers indicate that there are many different genotypes, and therefore many distinct clones present. The low resolution of markers used in the past limited our ability to estimate clonality and assess the individual level. New high‐resolution dinucleotide microsatellites now allow genetically distinct individuals to be identified, enabling more reliable estimation of population genetic parameters across the Mediterranean Basin. We investigated the biogeography and dispersal of P. oceanica at various spatial scales in order to assess the influence of different evolutionary factors shaping the distribution of genetic diversity in this species. Location The Mediterranean. Methods We used seven hypervariable microsatellite markers, in addition to the five previously existing markers, to describe the spatial distribution of genetic variability in 34 meadows spread throughout the Mediterranean, on the basis of an average of 35.6 (± 6.3) ramets sampled. Results At the scale of the Mediterranean Sea as a whole, a strong east–west cleavage was detected ( amova) . These results are in line with those obtained using previous markers. The new results showed the presence of a putative secondary contact zone at the Siculo‐Tunisian Strait, which exhibited high allelic richness and shared alleles absent from the eastern and western basins. F statistics (pairwise θ ranges between 0.09 and 0.71) revealed high genetic structure between meadows, both at a small scale (about 2 to 200 km) and at a medium scale within the eastern and western basins, independent of geographical distance. At the intrameadow scale, significant spatial autocorrelation in six out of 15 locations revealed that dispersal can be restricted to the scale of a few metres. Main conclusions A stochastic pattern of effective migration due to low population size, turnover and seed survival is the most likely explanation for this pattern of highly restricted gene flow, despite the importance of an a priori seed dispersal potential. The east–west cleavage probably represents the outline of vicariance caused by the last Pleistocene ice age and maintained to this day by low gene flow. These results emphasize the diversity of evolutionary processes shaping the genetic structure at different spatial scales.

Plumbing the Global Carbon Cycle: Integrating Inland Waters into the Terrestrial Carbon Budget - J. J. Cole; Y. T. Prairie; N. F. Caraco; W. H. McDowell; L. J. Tranvik; R. G. Striegl; C. M. Duarte; P. Kortelainen; J. A. Downing; J. J. Middelburg; J. Melack (Ecosystems, 2007)

Light regulation of benthic sulfate reduction rates mediated by seagrass (Thalassia testudinum) metabolism - Maria Li. Calleja; Cristina Barrón; Jason A. Hale; Thomas K. Frazer; Carlos M. Duarte (Estuaries and Coasts, 2006)

Resource translocation within seagrass clones: allometric scaling to plant size and productivity - Núria Marbà; Marten A. Hemminga; Carlos M. Duarte (Oecologia, 2006)

Genetic structure at range edge: low diversity and high inbreeding in Southeast Asian mangrove ( Avicennia marina ) populations - S. ARNAUD‐HAOND; S. TEIXEIRA; S. I. MASSA; C. BILLOT; P. SAENGER; G. COUPLAND; C. M. DUARTE; E. A. SERRÃO (Molecular Ecology, 2006)
Understanding the genetic composition and mating systems of edge populations provides important insights into the environmental and demographic factors shaping species’ distribution ranges. We analysed samples of the mangrove Avicennia marina from Vietnam, northern Philippines and Australia, with microsatellite markers. We compared genetic diversity and structure in edge (Southeast Asia, and Southern Australia) and core (North and Eastern Australia) populations, and also compared our results with previously published data from core and southern edge populations. Comparisons highlighted significantly reduced gene diversity and higher genetic structure in both margins compared to core populations, which can be attributed to very low effective population size, pollinator scarcity and high environmental pressure at distribution margins. The estimated level of inbreeding was significantly higher in northeastern populations compared to core and southern populations. This suggests that despite the high genetic load usually associated with inbreeding, inbreeding or even selfing may be advantageous in margin habitats due to the possible advantages of reproductive assurance, or local adaptation. The very high level of genetic structure and inbreeding show that populations of A. marina are functioning as independent evolutionary units more than as components of a metapopulation system connected by gene flow. The combinations of those characteristics make these peripheral populations likely to develop local adaptations and therefore to be of particular interest for conservation strategies as well as for adaptation to possible future environmental changes.

Determination of Organic Mercury in Biota, Plants and Contaminated Sediments Using a Thermal Atomic Absorption Spectrometry Technique - M. Válega; S. Abreu; P. Pato; L. Rocha; A. R. Gomes; M. E. Pereira; A. C. Duarte (Water, Air, & Soil Pollution, 2006)

Effects of dust deposition and river discharges on trace metal composition of Trichodesmium spp. in the tropical and subtropical North Atlantic Ocean - Antonio Tovar-Sanchez; Sergio A. Sañudo-Wilhelmy; Adam B. Kustka; Susana Agustí; Jordi Dachs; David A. Hutchins; Douglas G. Capone; Carlos M. Duarte (Limnology and Oceanography, 2006)
We present the elemental composition (Al, Cd, Co, Cu, Fe, Mn, Mo, Ni, V, Zn, and P) of field‐collected Trichodesmium populations. To distinguish the effects of river discharges (Amazon and Niger Rivers) and Saharan dust deposition on metal concentrations in the colonies, samples were collected both in the western (February 2001, July‐August 2001, and April‐May 2003) and eastern (May‐June 2003) basins of the North Atlantic. Metal composition (medians normalized to P) in Trichodesmium ranged from 0.011 mmol mol −1 for Co to 39 mmol mol −1 for Fe and varied over an order of magnitude among different locations. A comparison of metal ratios measured in the Trichodesmium colonies with ratios reported for the potential sources suggests that the most important sources of trace metals to the tropical and subtropical Atlantic during our sampling were the Amazon and Niger Rivers, rather than dust deposition from the Sahara.

Allometric laws and prediction in estuarine and coastal ecology - Lora A. Harris; Carlos M. Duarte; Scott W. Nixon (Estuaries and Coasts, 2006)

Physiological synecology of tree species in relation to geographic distribution and ecophysiological parameters at the Atlantic forest periphery in Brazil: an overview - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; H. Rennenberg; U. Lüttge (Trees, 2006)

A comparative study of responses in plankton food web structure and function in contrasting European coastal waters exposed to experimental nutrient addition - Y. Olsen; S. Agustí; T. Andersen; C. M. Duarte; J. M. Gasol; I. Gismervik; A.-S. Heiskanen; E. Hoell; P. Kuuppo; R. Lignell; H. Reinertsen; U. Sommer; et al. (Limnology and Oceanography, 2006)
We quantify, compare, and generalize responses of experimental nutrient loadings (L N ) on planktonic community structure and function in coastal waters. Data were derived from three mesocosm experiments undertaken in Baltic (BAL), Mediterranean (MED), and Norwegian (NOR) coastal waters. A planktonic model with seven functional compartments and 30–32 different carbon flows fit to all three experiments was used as a framework for flow‐rate estimation and comparison. Flows were estimated on the basis of time series of measured biomass, some measured flows, and inverse modeling. Biomass and gross uptake rate of carbon of most groups increased linearly with increasing L N in the nutrient input range of 0–1 µmol N L −1 d −1 at all locations. The fate of the gross primary production (GPP) was similar in all systems. Autotrophic biomass varied by two orders of magnitude among locations, with the lowest biomass and response to nutrient addition in MED waters. The variation of GPP among sites was less than one order of magnitude. Mesozooplankton dominated by doliolids (Tunicata), but not those dominated by copepods, presumably exerted efficient control of the autotrophic biomass, thereby buffering responses of autotrophs to high nutrient input. Among the many factors that can modify the responses of autotrophs to nutrients, the time scale over which the enrichment is made and the precise mode of nutrient enrichment are important. We suggest a general concept that may contribute to a scientific basis for understanding and managing coastal eutrophication.

Novel hydrolase diversity retrieved from a metagenome library of bovine rumen microflora - Manuel Ferrer; Olga V. Golyshina; Tatyana N. Chernikova; Amit N. Khachane; Dolores Reyes‐Duarte; Vitor A. P. Martins Dos Santos; Carsten Strompl; Kieran Elborough; Graeme Jarvis; Alexander Neef; Michail M. Yakimov; Kenneth N. Timmis; et al. (Environmental Microbiology, 2005)
Summary A metagenome expression library of bulk DNA extracted from the rumen content of a dairy cow was established in a phage lambda vector and activity‐based screening employed to explore the functional diversity of the microbial flora. Twenty‐two clones specifying distinct hydrolytic activities (12 esterases, nine endo‐β‐1,4‐glucanases and one cyclodextrinase) were identified in the library and characterized. Sequence analysis of the retrieved enzymes revealed that eight (36%) were entirely new and formed deep‐branched phylogenetic lineages with no close relatives among known ester‐ and glycosyl‐hydrolases. Bioinformatic analyses of the hydrolase gene sequences, and the sequences and contexts of neighbouring genes, suggested tentative phylogenetic assignments of the rumen organisms producing the retrieved enzymes. The phylogenetic novelty of the hydrolases suggests that some of them may have potential for new applications in biocatalysis.

Unidirectional Sodium Fluxes and Gill CYP1A Induction in an Amazonian Fish (Hyphessobrycon erythrostigma) Exposed to a Surfactant and to Crude Oil - A. Y. O. Matsuo; R. M. Duarte; A. L. Val (Bulletin of Environmental Contamination and Toxicology, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE-Brazil II. Spatial and ontogenetic dynamics in Andira legalis, a deciduous legume tree - A. Geβler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; F. R. Scarano; H. L. T. Zaluar; H. Rennenberg (Trees, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE Brazil I. Performance of three different species of Clusia in an array of plant communities - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; M. Nahm; H. Rennenberg; H. L. T. Zaluar; U. Lüttge (Trees, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE—Brazil III. Three legume trees in a semi-deciduous dry forest - A. Geßler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; P. J. F. P. Rodrigues; F. R. Scarano; H. Rennenberg (Trees, 2005)

Physiological synecology of tree species in relation to geographic distribution and ecophysiological parameters at the Atlantic forest periphery in Brazil: an overview - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; H. Rennenberg; U. Lüttge (Trees, 2005)

Explosive activity and generation mechanisms of pyroclastic flows at Arenal volcano, Costa Rica between 1987 and 2001 - P. D. Cole; E. Fernandez; E. Duarte; A. M. Duncan (Bulletin of Volcanology, 2005)

Within‐population spatial genetic structure, neighbourhood size and clonal subrange in the seagrass Cymodocea nodosa - FILIPE ALBERTO; LICÍNIA GOUVEIA; SOPHIE ARNAUD‐HAOND; JOSÉ L. PÉREZ‐LLORÉNS; CARLOS M. DUARTE; ESTER A. SERRÃO (Molecular Ecology, 2005)
The extent of clonality within populations strongly influences their spatial genetic structure (SGS), yet this is hardly ever thoroughly analysed. We employed spatial autocorrelation analysis to study effects of sexual and clonal reproduction on dispersal of the dioecious seagrass Cymodocea nodosa . Analyses were performed both at genet level (i.e. excluding clonal repeats) and at ramet level. Clonal structure was characterized by the clonal subrange, a spatial measure of the linear limits where clonality still affects SGS. We show that the clonal subrange is equivalent to the distance where the probability of clonal identity approaches zero. This combined approach was applied to two meadows with different levels of disturbance, Cadiz (stable) and Alfacs (disturbed). Genotypic richness, the proportion of the sample representing distinct genotypes, was moderate (0.38 Cadiz, 0.46 Alfacs) mostly due to dominance of a few clones. Expected heterozygosities were comparable to those found in other clonal plants. SGS analyses at the genet level revealed extremely restricted gene dispersal in Cadiz ( Sp = 0.052, a statistic reflecting the decrease of pairwise kinship with distance), the strongest SGS found for seagrass species, comparable only to values for selfing herbaceous land plants. At Cadiz the clonal subrange extended across shorter distances (20–25 m) than in Alfacs (30–35 m). Comparisons of sexual and vegetative components of gene dispersal suggest that, as a dispersal vector within meadows, clonal spread is at least as important as sexual reproduction. The restricted dispersal and SGS pattern in both meadows indicates that the species follows a repeated seedling recruitment strategy.

In situ measurements of carbon and nitrogen distribution and composition, photochemical efficiency and stable isotope ratios in Araucaria angustifolia - A. C. Franco; H. M. Duarte; A. Geβler; E. A. de Mattos; M. Nahm; H. Rennenberg; K. T. Ribeiro; F. R. Scarano; U. Lüttge (Trees, 2005)

Population age structure and rhizome growth of Cymodocea nodosa in the Ria Formosa (southern Portugal) - A. H. Cunha; C. M. Duarte (Marine Biology, 2005)

Use of supplementary genotypes in AMMI analysis - R. M. Pacheco; J. B. Duarte; R. Vencovsky; J. B. Pinheiro; A. B. Oliveira (Theoretical and Applied Genetics, 2005)

Effect of a high-altitude expedition to a Himalayan peak (Pumori, 7,161m) on plasma and erythrocyte antioxidant profile - Jos Magalhes; Antnio Ascenso; Franklim Marques; Jos M. C. Soares; Rita Ferreira; Maria J. Neuparth; Jos A. Duarte (European Journal of Applied Physiology, 2005)

Effects of chronic quercetin treatment in experimental renovascular hypertension - Mara Francisca Garca-Saura; Milagros Galisteo; Inmaculada Concepcin Villar; Almudena Bermejo; Antonio Zarzuelo; Flix Vargas; Juan Duarte (Molecular and Cellular Biochemistry, 2005)

Variation of Mercury Contamination in Chicks of Little Tern Sterna albifrons in Southwest Europe: Brood, Age, and Colony Related Effects - P. C. Tavares; L. R. Monteiro; R. J. Lopes; M. E. Pereira; A. C. Duarte; R. W. Furness (Bulletin of Environmental Contamination and Toxicology, 2005)

A case of eumycetoma due to Madurella grisea in northern Brazil - Raquel Vilela; Olga M. V. Duarte; Carlos A. Rosa; Joao G. F. Castro; Sandra Lyon; Roberta L. Motta; Ana C. L. Moura (Mycopathologia, 2004)

Synchronous Scan and Excitation-Emission Matrix Fluorescence Spectroscopy of Water-Soluble Organic Compounds in Atmospheric Aerosols - Regina M.B.O. Duarte; Casimiro A. Pio; Armando C. Duarte (Journal of Atmospheric Chemistry, 2004)

Acute and severe hypobaric hypoxia-induced muscle oxidative stress in mice: the role of glutathione against oxidative damage - Jos Magalhes; Jos M. C. Soares; Maria J. Neuparth; Rita Ferreira; Jos Oliveira; Francisco Amado; Jos A. Duarte; Antnio Ascenso (European Journal of Applied Physiology, 2004)

A novel hydrophilic support, CoFoam, for enzyme immobilization - P.T. Vasudevan; N. López-Cortés; H. Caswell; D. Reyes-Duarte; F.J. Plou; A. Ballesteros; K. Como; T. Thomson (Biotechnology Letters, 2004)

Modeling the mass balance and fate of copper in San Diego Bay - D. B. Chadwick; A. Zirino; I. Rivera-Duarte; C. N. Katz; A. C. Blake (Limnology and Oceanography, 2004)
Because of its presence in antifouling coatings, stormwater, and industrial and municipal discharges, copper is a ubiquitous contaminant in estuarine and coastal environments. We integrated a system‐wide field program with a one‐dimensional model to evaluate the overall mass balance of copper in a representative coastal harbor, San Diego Bay, California. Field results from four surveys over 1 yr showed remarkably similar distributions of total copper, with a general increase from the ocean into the Bay followed by a slight decrease in the inner Bay. Total copper concentrations ranged from 5 nmol L ‐1 to nearly 60 nmol L ‐1 . Highest levels for both total and dissolved copper were observed during the winter. Results from a one‐dimensional model accounting for the balance of sources, flushing, and losses to the sediment illustrated the importance of accounting for losses of copper to the sediment, without which water column concentrations are overestimated by as much as a factor of five. The time scale for the loss term is on the order of 8‐10 d. The model reproduced the field measurements quite well with a loss term controlled by partitioning and settling parameters. The overall balance of total copper in the Bay appears to be split between losses to the ocean via tidal flushing and losses to the sediments via settling. Settling plays an important role in the fate of copper in the Bay, and the sediments are a key endpoint for copper.

Aflatoxin Binders II: Reduction of aflatoxin M1 in milk by sequestering agents of cows consuming aflatoxin in feed - Duarte E. Diaz; Winston M. Hagler; John T. Blackwelder; Julie A. Eve; Brinton A. Hopkins; Kevin L. Anderson; Frank T. Jones; Lon W. Whitlow (Mycopathologia, 2004)

Biotechnological applications of peroxidases - Carlos Regalado; Blanca E. García-Almendárez; Miguel A. Duarte-Vázquez (Phytochemistry Reviews, 2004)

Aflatoxin Binders I: In vitro binding assay for aflatoxin B1 by several potential sequestering agents - Duarte E. Diaz; Winston M. Hagler; Brinton A. Hopkins; Lon W. Whitlow (Mycopathologia, 2003)

Cerebral Toxoplasmosis After Autologous Peripheral Blood Stem Cell Transplantation - M. Lpez-Duarte; A. Insunza; E. Conde; A. Iriondo; F. Mazorra; A. Zubizarreta (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Movement sway: changes in postural sway during voluntary shifts of the center of pressure - Mark L. Latash; Sandra S. Ferreira; Silvana A. Wieczorek; Marcos Duarte (Experimental Brain Research, 2003)

Addition of nutrients induce a fast loss of flocculation in starved cells of Saccharomyces cerevisiae - Eduardo V. Soares; Abel A. Duarte (Biotechnology Letters, 2002)

Phylogenetic analysis of five Portuguese strains of FIV - A. Duarte; M. I. Marques; L. Tavares; M. Fevereiro (Archives of Virology, 2002)

Interference with the GABAergic system in the dorsolateral telencephalon and modulation of the electric organ discharge frequency in the weakly electric fish Gymnotus carapo - Santana U.; Roque-da-Silva A.; Duarte T.; Corrêa S. (Journal of Comparative Physiology A, 2001)

Storage and export of mercury from a contaminated bay (Ria de Aveiro, Portugal) - E. Ramalhosa; P. Monterroso; S. Abreu; E. Pereira; C. Vale; A. Duarte (Wetlands Ecology and Management, 2001)

Pests and diseases in agroforestry systems of the humid tropics - G. Schroth; U. Krauss; L. Gasparotto; J. A. Duarte Aguilar; K. Vohland (Agroforestry Systems, 2000)

Quantitation of plasmid DNA in aqueous two-phase systems by fluorescence analysis - Sofia C. Ribeiro; Gabriel A. Monteiro; Gaspar Martinho; Joaquim M.S. Cabral; Duarte M.F. Prazeres (Biotechnology Letters, 2000)

Age and growth of the fan mussel Pinna nobilis from south-east Spanish Mediterranean seagrass ( Posidonia oceanica ) meadows - C. A. Richardson; H. Kennedy; C. M. Duarte; D. P. Kennedy; S. V. Proud (Marine Biology, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Conservation genetics of the endangered Pampas deer ( Ozotoceros bezoarticus ) - S. GONZÁLEZ; J. E. MALDONADO; J. A. LEONARD; C. VILÀ; J. M. BARBANTI DUARTE; M. MERINO; N. BRUM‐ZORRILLA; R. K. WAYNE (Molecular Ecology, 1998)
The Pampas deer ( Ozotoceros bezoarticus L. 1758) is the most endangered neotropical cervid, and in the past occupied a wide range of open habitats including grassland, pampas, savanna, and cerrado (Brazil) from 5° to 41° S. To better understand the effect of habitat fragmentation on gene flow and genetic variation, and to uncover genetic units for conservation, we examined DNA sequences from the mitochondrial control region of 54 individuals from six localities distributed throughout the present geographical range of the Pampas deer. Our results suggest that the control region of the Pampas deer is one of the most polymorphic of any mammal. This remarkably high variability probably reflects large historic population sizes of millions of individuals in contrast to numbers of fewer than 80 000 today. Gene flow between populations is generally close to one migrant per generation and, with the exception of two populations from Argentina, all populations are significantly differentiated. The degree of gene flow was correlated with geographical distance between populations, a result consistent with limited dispersal being the primary determinant of genetic differentiation between populations. The molecular genetic results provide a mandate for habitat restoration and reintroduction of Pampas deer so that levels of genetic variation can be preserved and historic patterns of abundance can be reconstructed. However, the source of individuals for reintroduction generally should be from populations geographically closest to those now in danger of extinction.

Biomass distribution in marine planktonic communities - Josep M. Gasol; Paul A. del Giorgio; Carlos M. Duarte (Limnology and Oceanography, 1997)
Patterns in primary production and carbon export from the euphotic zone suggest that the relative contribution of planktonic heterotrophs to community biomass should decline along gradients of phytoplankton biomass and primary production. Here, we use an extensive literature data survey to test the hypothesis that the ratio of total heterotrophic (bacteria + protozoa + mesozooplankton) biomass to total autotrophic biomass (H : A ratio) is not constant in marine plankton communities but rather tends to decline with increasing phytoplankton biomass and primary production. Our results show that the plankton of unproductive regions are characterized by very high relative heterotrophic biomasses resulting in inverted biomass pyramids, whereas the plankton of productive areas are characterized by a smaller contribution of heterotrophs to community biomass and a normal biomass pyramid with a broad autotrophic base. Moreover, open‐ocean communities support significantly more heterotrophic biomass in the upper layers than do coastal communities for a given autotrophic biomass. These differences in the biomass structure of the community could be explained by the changes in the biomass‐specific rates of phytoplankton production that seem to occur from ultraoligotrophic to eutrophic marine regions, but other factors could also generate them. The patterns described suggest a rather systematic shift from consumer control of primary production and phytoplankton biomass in open ocean to resource control in upwelling and coastal areas.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Seasonal variability in mercury inputs into the Ria de Aveiro, Portugal - M. E. Pereira; A. C. Duarte; G. E. Millward (Aquatic Ecology, 1995)